Polyimide bead material and method for producing the same
By preparing silicon-containing nanoporous carbon materials, the problems of limited capacity of lithium-ion battery anode materials and silicon volume expansion are solved, and electrode materials with high capacity and cycle stability are achieved.
Patent Information
- Application Number
- CN202180047002.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-25
- Filing Date
- 2021-08-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-08-23
AI Technical Summary
The graphite capacity of the anode material of traditional lithium-ion battery packs is limited, and the volume expansion of silicon as an alternative material is severely during lithiation, which limits its use in the electrode.
A method is used to prepare granular carbon compositions, including a mixture that provides polyanide anterior and silicon -based materials. It triggers amine to form a mixture of amine, carbonized after drying, prepare after drying, prepare for preparation It contains nano -porous carbon materials with a silicon greater than 10 %.
The prepared nano -porous carbon materials have excellent pore structure and mechanical strength, which can effectively solve the problem of silicon volume expansion and improve the capacity and cycle stability of the electrode.
Smart Images

Figure CN115768722B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Patent Application No. 17 / 408,841, filed on August 23, 2021, and U.S. Provisional Patent Application No. 63 / 070,230, filed on August 25, 2020, and is related to U.S. Patent Application No. 16 / 803,348, filed on February 27, 2020, which claims priority to U.S. Provisional Patent Application No. 62 / 811,230, filed on February 27, 2019, each of which is hereby incorporated by reference in its entirety, with any definitions of terms in this application governing. Technical Field
[0003] The present disclosure generally relates to nanoporous carbon-based materials and methods of making the same. Background Art
[0004] Aerogels are solid materials that include a highly porous network of micropores and mesopores. Depending on the precursor materials used and the treatments performed, the pores of the aerogels can typically account for more than 90% of the volume when the density of the aerogel is about 0.05 g / cc. Aerogels are typically prepared by removing solvent from a gel (a solid network containing its solvent) in a manner that causes minimal or no gel shrinkage due to capillary forces at the surface of the gel. Methods for solvent removal include, but are not limited to, supercritical drying (or drying with a supercritical fluid so that the low surface tension of the supercritical fluid is exchanged with a temporary solvent within the gel), solvent exchange with a supercritical fluid, solvent exchange with a fluid that subsequently transitions to a supercritical state, subcritical or near-critical drying, and sublimation of the frozen solvent during freeze drying, see, for example, PCT Patent Application Publication No. WO2016127084A1. It should be noted that when dried under ambient conditions, gel shrinkage may occur as the solvent evaporates, and a xerogel may be formed. Therefore, the preparation of aerogels by sol-gel or other polymerization processes is generally carried out in a series of steps: dissolving the solute in the solvent, forming a sol / solution / mixture, forming a gel (which may involve additional cross-linking), and removing the solvent by supercritical drying techniques or any other method that removes the solvent from the gel without causing pore collapse.
[0005] Aerogels can be formed from inorganic and / or organic materials. When formed from organic materials, such as phenol, resorcinol-formaldehyde (RF), phloroglucinol furfural (PF), polyacrylonitrile (PAN), polyimide (PI), polyurethane (PU), polybutadiene, polydicyclopentadiene, and precursors or polymer derivatives thereof, for example, the aerogels can be carbonized (e.g., by pyrolysis) to form carbon aerogels that can have properties that are different or overlapping from one another (e.g., pore volume, pore size distribution, morphology, etc.), depending on the precursor materials and methods used.
[0006] However, in all cases, certain drawbacks exist based on the materials and applications, such as low pore volume, wide pore size distribution, low mechanical strength, etc. Recently, much effort has been devoted to developing and characterizing carbon aerogels as electrode materials with improved properties that can be applied in energy storage devices such as lithium-ion batteries (LIBs).
[0007] LIBs have been widely used in a variety of applications, from handheld electronics to automobiles. They are a type of rechargeable battery in which lithium ions move from the anode to the cathode during discharge and from the cathode to the anode during charge. Typically, the cathode is formed of lithium metal (e.g., cobalt, nickel, manganese) oxide, while the anode is formed of graphite, in which the lithium ions are intercalated within the graphite layers during charge (energy storage). Graphite is widely used because lithium intercalates into graphite at a higher rate than other known carbons.
[0008] While the demand for higher capacity anode and cathode materials continues to increase, the main drawback of conventional lithium-ion battery packs is the limited capacity of graphite; in other words, graphite can only hold a limited amount of lithium. It is well known that silicon has a greater affinity for lithium than graphite (carbon) and is able to store significantly higher amounts of lithium than graphite during charging, theoretically allowing for higher capacities on the anode side of LIBs. In comparison, the theoretical capacity of graphite combined with lithium is 372mAh / g, while silicon has a theoretical capacity of 4200mAh / g. These numbers have led to a desire to place as much silicon as possible inside the anode. However, a considerable problem with silicon is that when fully lithiated, it expands 3-4 times its volume (and often breaks or cracks), which greatly limits the amount of silicon that can be placed inside the electrode.
[0009] Therefore, it would be desirable in the art to provide an improved nanoporous carbon material comprising a functional morphology and an optimal pore structure while solving at least one of the above-mentioned problems.
[0010] Although certain aspects of conventional technology have been discussed to facilitate the disclosure of the present invention, applicants in no way disclaim these aspects of technology and contemplate that the claimed invention may encompass one or more of the conventional technology aspects discussed herein, particularly in combination with the innovative aspects described herein.
[0011] The present invention can solve one or more of the problems and defects discussed above in the art. However, it is expected that the present invention may prove useful in solving other problems and defects in many technical fields. Therefore, the claimed invention need not be interpreted as being limited to solving any specific problem or defect discussed herein.
[0012] In this specification, when a document, act or item of knowledge is cited or discussed, such citation or discussion does not constitute an admission that the document, act or item of knowledge or any combination thereof was publicly available, known to the public, part of the common general knowledge, or otherwise constituted prior art under applicable law as of the priority date; or was known to be relevant to attempts to solve any problem involved in this specification. Summary of the invention
[0013] Embodiments of the present disclosure now satisfy the long-standing but heretofore unmet need for improved nanoporous carbon materials.
[0014] The first general aspect relates to a method of forming or making a granular carbon composition. In an exemplary embodiment, a method includes providing a mixture of a polyimide precursor and a silicon-based material, chemically or thermally initiating imidization of the mixture, such as by adding an imidization catalyst or by heating; combining the mixture with a medium that is immiscible with the mixture to form droplets of the imidized mixture, drying the droplets of the imidized mixture to produce a granular porous polyimide silicon composite material; and carbonizing, such as pyrolyzing, the granular porous polyimide silicon composite material to produce a granular carbon composition, the granular carbon composition containing greater than about 10% by weight silicon and a porosity between about 10% and about 90%. In some embodiments, the medium that is immiscible with the mixture, such as a dispersion medium, can form an emulsion with the imidized mixture as a dispersed phase. In any embodiment, the carbon composition can include a carbon aerogel and can be formed as a monolith or granules.
[0015] In an exemplary embodiment, the step of initiating imidization occurs before the step of combining the mixture with a medium that is immiscible with the mixture. In other embodiments, the imidization step may occur after the mixture is combined with the immiscible medium, for example, the imidization is performed while the mixture is in the immiscible medium. In an exemplary embodiment, the method may also include aging the particulate porous polyimide silicon composite material prior to carbonization.
[0016] Another general aspect relates to a particulate carbon composition, such as a powder. In an exemplary embodiment, the particulate carbon composition includes a composite material including a silicon-based material and carbon. Exemplary embodiments include a silicon-doped nanoporous carbon material including a pore structure comprising a fibrous morphology and an array of pores surrounding elemental silicon.
[0017] In any embodiment, the particulate carbon composition may have a particle size in a range of about 1 μm to about 15 μm. In some embodiments, the particulate carbon composition may have a particle size in a range of about 5 μm to about 10 μm.
[0018] In some embodiments, the granular carbon composition may have a carbon content of about 0.3 g / cm 3 To about 1.3g / cm 3 In some embodiments, the granular carbon composition may have a tap density of about 0.7 g / cm 3 The tap density.
[0019] In some embodiments, composite material includes greater than about 10% by weight of silicon-based materials. In certain embodiments, composite material includes about 20% by weight to about 60% by weight of silicon-based materials. In some embodiments, composite material includes about 10% by weight to about 90% by weight of silicon-based materials. For example, composite material may include about 10%, about 15%, about 20%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, about 90% or silicon-based materials in the range between any two of these values.
[0020] In some embodiments, the granular carbon composition comprises a granular carbon aerogel, such as a polyimide-derived carbon aerogel. In other embodiments, the granular carbon composition comprises a granular carbon xerogel, such as a polyimide-derived carbon xerogel. In any embodiment, the diameter of the particles can range from about 1 micron to about 50 microns.
[0021] In any embodiment, the pore structure of the carbon composition can be characterized in that the pores of the carbon material partially, substantially or completely surround the silicon-based material, such as by forming an interconnected structure around the silicon characterized by multiple connection points between the silicon and the pore walls. For example, the silicon-based material can be at least partially present within the pore structure of the carbon composition. For another example, the pore structure can include a fibrous morphology and an array of pores surrounding the silicon-based material.
[0022] In exemplary embodiments, the carbon material has one or more pore structures comprising a fibrous morphology, a Young's modulus of at least about 0.2 GPa, an electrical conductivity of at least about 10 S / cm, and a density between about 0.15 gcc and about 1.5 g / cc.
[0023] In another exemplary embodiment, the carbon composition includes a silicon-doped nanoporous carbon material having a silicon utilization of at least about 20%, wherein the carbon material is doped with silicon accounting for greater than about 25 weight % of the carbon material. Optionally, the carbon material may have an electrical conductivity of at least about 10 S / cm. Optionally, the carbon material may have a Young's modulus of at least about 0.2 GPa.
[0024] In another exemplary embodiment, the granular carbon composition includes a silicon-doped nanoporous carbon material having the following properties: a pore structure including a fibrous morphology, a Young's modulus of at least about 0.2 GPa, a density between about 0.15 g / cc and about 1.5 g / cc, and a silicon utilization of at least about 20%. Optionally, the carbon material may have an electrical conductivity of at least about 10 S / cm.
[0025] In another exemplary embodiment, the granular carbon composition includes a silicon-doped nanoporous carbon material having the following properties: a pore structure including a fibrous morphology, a conductivity of at least 10 S / cm, a density between about 0.15 g / cc and about 1.5 g / cc, and a silicon utilization of at least about 20%. Optionally, the carbon material may have a Young's modulus of at least about 0.2 GPa.
[0026] In any embodiment, the nanoporous carbon material can be doped with silicon in an amount of about 5% to 80% by weight of the carbon material. For example, the carbon material can include silicon in an amount of about 25% to about 65% by weight of the carbon material.
[0027] In any embodiment, the nanoporous carbon material may have a pore volume of at least 0.3 cc / g.
[0028] In any embodiment, the nanoporous carbon material may have a pre-lithiation porosity between about 10% and about 80%.
[0029] In any embodiment, the carbon material, such as a nanoporous carbon material, can include at least about 4 wt % residual nitrogen.
[0030] In any embodiment, the silicon-doped nanoporous carbon material may have a capacity of at least about 800 mAh / g. For example, the silicon-doped nanoporous carbon material may have a capacity of up to about 2000 mAh / g.
[0031] In any embodiment, the pore structure of the nanoporous carbon material can include a full width at half maximum of about 50 nm or less (ie, a narrow pore size distribution).
[0032] In any embodiment, the pore structure of the nanoporous carbon material may include a distributed full peak pore size of about 100 nm or less.
[0033] In any embodiment, the fibrous morphology of the nanoporous carbon material can include an average pillar width of about 2-10 nm, or, even more specifically, about 2-5 nm.
[0034] Another embodiment provides an electrode comprising the granular carbon composition. The electrode may be an anode. Another embodiment provides an electrochemical cell comprising the granular carbon composition, nanoporous carbon material and / or electrode. Another embodiment provides an energy storage device, such as a battery or more specifically a lithium ion battery, comprising the granular carbon composition, nanoporous carbon material and / or electrochemical cell.
[0035] In another aspect, there is provided a method of forming a porous carbon composition in the form of beads, the method comprising:
[0036] providing an organogel precursor in an organic solvent;
[0037] initiating gelation of an organogel precursor to obtain an organogel sol;
[0038] synthesizing the organogel sol with a medium that is immiscible with the organic solvent to form organogel droplets;
[0039] separation of organogel droplets;
[0040] drying the droplets to produce porous organogel composite beads; and
[0041] The porous organogel composite beads are pyrolyzed to produce a porous carbon composition, wherein the porous carbon composition has a porosity between about 10% and about 90%.
[0042] In some embodiments, gelation is initiated prior to combining the organogel sol with the medium.
[0043] In some embodiments, the organogel precursor is a polyamic acid. In some embodiments, the polyamic acid comprises a tetracarboxylic acid and a polyfunctional amine.
[0044] In some embodiments, the tetracarboxylic acid is selected from benzene-1,2,4,5-tetracarboxylic acid, [1,1'-biphenyl]-3,3',4,4'-tetracarboxylic acid, 4,4'-oxydiphthalic acid, 4,4'-sulfonyldiphthalic acid, 4,4'-carbonyldiphthalic acid, 4,4'-(propane-2,2-diyl)diphthalic acid, 4,4'-(perfluoropropane-2,2-diyl)diphthalic acid, naphthalene-1,4,5,8-tetracarboxylic acid, 4-(2-(4-(3,4-dicarboxyphenoxy)phenyl)propan-2-yl)phthalic acid, perylenetetracarboxylic acid, and combinations thereof.
[0045] In some embodiments, the multifunctional amine is an alkane diamine or an aryl diamine. In some embodiments, the alkane diamine is ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, or a combination thereof. In some embodiments, the aryl diamine is 1,4-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-methylenedianiline, or a combination thereof.
[0046] In some embodiments, gelation is chemical imidization, thermal imidization, or a combination of chemical imidization and thermal imidization. In some embodiments, chemical imidization includes adding a dehydrating agent and an amine base. In some embodiments, the dehydrating agent is acetic anhydride. In some embodiments, the amine base is pyridine.
[0047] In some embodiments, the organic solvent is N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, or ethyl acetate. In some embodiments, the organic solvent is N,N-dimethylacetamide.
[0048] In some embodiments, the organic solvent further comprises water in an amount of about 100 to about 1500 parts per million (ppm). In some embodiments, the organic solvent further comprises water in an amount of about 500 to about 1200 ppm or about 500 to about 700 ppm.
[0049] In some embodiments, the medium has a viscosity of about 100 to about 150 cP.
[0050] In some embodiments, the medium is mineral oil, silicone oil, or a C5-C12 hydrocarbon.
[0051] In some embodiments, the method further comprises adding one or more surfactants to the medium.
[0052] In some embodiments, the organogel precursor solution has a viscosity of about 5 to about 30 cP.
[0053] In some embodiments, the ratio of the viscosity of the medium to the viscosity of the organogel precursor solution is from about 3 to about 30, or from about 5 to about 20.
[0054] In some embodiments, the method further comprises adding a low viscosity solvent to the medium. In some embodiments, the low viscosity solvent is added in a single portion in an amount up to about 10% by volume of the medium. In some embodiments, the low viscosity solvent is added in two or more portions, including a first portion and further one or more portions of an amount up to about 10% by volume of the medium, wherein the total amount of the low viscosity solvent added is up to about 50% by volume of the medium. In some embodiments, the low viscosity solvent is added in a continuous manner, wherein the total amount of the low viscosity solvent added is up to about 50% by volume of the medium. In some embodiments, the low viscosity solvent is a C1 to C3 alcohol.
[0055] In some embodiments, combining comprises agitating the organogel precursor solution under high shear conditions.
[0056] In some embodiments, drying comprises freeze-drying the organogel, exposing the organogel to elevated temperature conditions, or contacting the organogel with supercritical fluid CO2, or contacting the organogel with liquid CO2 and evaporating the liquid CO2 into a gas.
[0057] In some embodiments, the method further comprises aging the porous organogel composite material prior to pyrolyzing.
[0058] In some embodiments, the porous carbon composition comprises a carbon aerogel. In some embodiments, the porous carbon composition comprises a carbon xerogel.
[0059] In some embodiments, the diameter of the porous carbon composition beads ranges from about 1 micron to about 50 microns or from about 1 to about 15 microns.
[0060] In some embodiments, the porous carbon composition is a porous carbon-silicon composition comprising greater than about 10 wt % silicon, based on the total weight of the composition, and the method further comprises providing a mixture of an organogel precursor and silicon in an organic solvent.
[0061] In some embodiments, the porous carbon-silicon composition comprises from about 20 wt % to about 65 wt % silicon, based on the total weight of the composition.
[0062] In some embodiments, the porous carbon-silicon composition comprises a pore structure, and the silicon resides at least partially within the pore structure. In some embodiments, the pore structure comprises a fibrous morphology and an array of pores surrounding the silicon.
[0063] In some embodiments, the porous carbon-silicon composition has a capacity of at least about 800 mAh / g.
[0064] In some embodiments, the porous carbon-silicon composition has a silicon utilization efficiency of at least about 20%.
[0065] In another aspect, a porous carbon composition in the form of beads is provided, the porous carbon composition comprising a composite material including carbon, the diameter of the beads being in the range of about 1 μm to about 15 μm, and the tap density being about 0.3 g / cm 3 To about 1.3g / cm 3 within the range.
[0066] In some embodiments, the carbon comprises a carbon aerogel or a carbon xerogel.
[0067] In some embodiments, the composite material further comprises silicon in an amount greater than about 10 wt % based on the total weight of the composite material. In some embodiments, the composite material comprises silicon in an amount from about 25 wt % to about 65 wt % based on the total weight of the composite material.
[0068] In some embodiments, the carbon has a pore structure, and the silicon resides at least partially within the pore structure.
[0069] In some embodiments, the composite material has a silicon utilization efficiency of at least about 20%.
[0070] In some embodiments, the silicon has a particle size of less than about 150 nm. In some embodiments, the silicon has a particle size in the range of about 150 nm to about 500 nm. In some embodiments, the silicon has a particle size greater than about 500 nm.
[0071] In some embodiments, the composite material comprises silicon in a range of about 25 to about 65 weight percent based on the total weight of the composite material, wherein the particle size of the silicon is in a range of about 100 nm to about 800 nm; and wherein the tap density of the beads is about 0.2 g / cm 3 To about 1.5g / cm 3 diameter in the range of about 1 μm to about 15 μm; an average pore size in the range of about 10 nm to about 50 nm; and a BET surface area in the range of about 0 to about 500 m 2 / g range.
[0072] In some embodiments, the porous carbon-silicon composition has a capacity of at least about 800 mAh / g.
[0073] In another aspect, an energy storage device comprising a porous carbon composition as disclosed herein is provided. In some embodiments, the energy storage device is a lithium-ion battery.
[0074] The present disclosure includes, but is not limited to, the following embodiments.
[0075] Embodiment 1: A method of forming a porous carbon composition in the form of beads, the method comprising:
[0076] providing an organogel precursor in an organic solvent;
[0077] Initiating gelation of the organogel precursor to obtain an organogel sol;
[0078] combining the organogel sol with a medium that is immiscible with the organogel sol to form droplets of the organogel;
[0079] separating droplets of the organogel;
[0080] drying the droplets to produce porous organogel beads; and
[0081] The porous organogel beads are pyrolyzed to produce a porous carbon composition in the form of the beads, wherein the porous carbon composition has a porosity between about 10% and about 90%.
[0082] Embodiment 2: The method of embodiment 1, wherein initiating gelation occurs before combining the mixture with the medium.
[0083] Embodiment 3: The method of Embodiment 1 or 2, wherein the organogel precursor is polyamic acid.
[0084] Embodiment 4: The method as described in any one of Embodiments 1-3, wherein the gelation is chemical imidization, thermal imidization, or a combination of chemical imidization and thermal imidization.
[0085] Embodiment 5: The method of any one of Embodiments 1-4, wherein the polyamic acid comprises a tetracarboxylic acid and a multifunctional amine.
[0086] Embodiment 6: A method as described in any one of Embodiments 1-5, wherein the tetracarboxylic acid is selected from the group consisting of: benzene-1,2,4,5-tetracarboxylic acid, [1,1'-biphenyl]-3,3',4,4'-tetracarboxylic acid, 4,4'-oxydiphthalic acid, 4,4'-sulfonyldiphthalic acid, 4,4'-carbonyldiphthalic acid, 4,4'-(propane-2,2-diyl)diphthalic acid, 4,4'-(perfluoropropane-2,2-diyl)diphthalic acid, naphthalene-1,4,5,8-tetracarboxylic acid, 4-(2-(4-(3,4-dicarboxyphenoxy)phenyl)propane-2-yl)phthalic acid, perylenetetracarboxylic acid and combinations thereof.
[0087] Embodiment 7: The method of any one of Embodiments 1-6, wherein the polyfunctional amine is an alkane diamine or an aryl diamine.
[0088] Embodiment 8: The method of any one of Embodiments 1-7, wherein the alkanediamine is ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, or a combination thereof.
[0089] Embodiment 9: The method of any one of Embodiments 1-8, wherein the aryl diamine is 1,4-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-methylenedianiline, or a combination thereof.
[0090] Embodiment 10: The method of any one of Embodiments 1-9, wherein the chemical imidization comprises adding a dehydrating agent and an amine base.
[0091] Embodiment 11: The method of any one of Embodiments 1-10, wherein the dehydrating agent is acetic anhydride.
[0092] Embodiment 12: The method of any one of Embodiments 1-11, wherein the amine base is pyridine.
[0093] Embodiment 13: The method as described in any one of Embodiments 1-12, wherein the organic solvent is N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran or ethyl acetate.
[0094] Embodiment 14: The method of any one of Embodiments 1-13, wherein the organic solvent is N,N-dimethylacetamide.
[0095] Embodiment 15: The method of any one of Embodiments 1-14, wherein the organic solvent further comprises water in an amount of about 100 to about 1500 parts per million (ppm).
[0096] Embodiment 16: The method of any one of Embodiments 1-3, wherein the organic solvent further comprises water in an amount of about 500 to about 1200 ppm or about 500 to about 700 ppm.
[0097] Embodiment 17: The method of any one of Embodiments 1-16, wherein the medium has a viscosity of about 100 to about 150 cP.
[0098] Embodiment 18: A method as described in any one of Embodiments 1-17, wherein the medium is mineral oil, silicone oil or C5-C12 hydrocarbon.
[0099] Embodiment 19: The method of any one of Embodiments 1-18, further comprising adding one or more surfactants to the medium.
[0100] Embodiment 20: The method of any one of Embodiments 1-19, wherein the organogel sol has a viscosity of about 5 to about 30 cP.
[0101] Embodiment 21: The method of any one of Embodiments 1-20, wherein the ratio of the viscosity of the medium to the viscosity of the organogel is from about 3 to about 30, or from about 5 to about 20.
[0102] Embodiment 22: The method of any one of Embodiments 1-21, further comprising adding a low viscosity solvent to the medium.
[0103] Embodiment 23: The method of any one of Embodiments 1-22, wherein the low viscosity solvent is added all at once in an amount of up to about 10% by volume of the medium.
[0104] Embodiment 24: A method as described in any of Embodiments 1-23, wherein the low viscosity solvent is added in two or more parts, including a first part in an amount of up to about 10 volume % of the medium and one or more additional parts, wherein the total amount of the low viscosity solvent added is up to about 50 volume % of the medium.
[0105] Embodiment 25: The method of any one of Embodiments 1-24, wherein the low viscosity solvent is added in a continuous manner, wherein the total amount of the low viscosity solvent added is at most about 50% by volume of the medium.
[0106] Embodiment 26: The method of any one of Embodiments 1-25, wherein the low viscosity solvent is a C1 to C3 alcohol.
[0107] Embodiment 27: The method of any one of Embodiments 1-26, wherein combining comprises stirring under high shear conditions.
[0108] Embodiment 28: A method as described in any one of Embodiments 1-27, wherein drying comprises freeze-drying the organogel beads, exposing the organogel beads to elevated temperature conditions, contacting the organogel beads with supercritical fluid CO2, or contacting the organogel beads with liquid CO2 and evaporating the CO2 as a gas.
[0109] Embodiment 29: The method of any one of Embodiments 1-28, further comprising aging the porous organogel beads prior to pyrolysis.
[0110] Embodiment 30: A method as described in any one of Embodiments 1-29, wherein the porous carbon composition comprises a carbon aerogel.
[0111] Embodiment 31: A method as described in any one of Embodiments 1-30, wherein the porous carbon composition comprises a carbon xerogel.
[0112] Embodiment 32: A method as described in any of Embodiments 1-31, wherein the beads of the porous carbon composition have a diameter in a range from about 1 micron to about 50 microns.
[0113] Embodiment 33: A method as described in any of Embodiments 1-32, wherein the porous carbon composition is a porous carbon-silicon composition having greater than about 10 weight percent silicon based on the total weight of the composition, and the method further includes providing silicon mixed with the organic gel precursor in the organic solvent.
[0114] Embodiment 34: A method as described in any of Embodiments 1-33, wherein the porous carbon-silicon composition comprises about 20 wt% to about 65 wt% silicon based on the total weight of the composition.
[0115] Embodiment 35: The method of any one of Embodiments 1-34, wherein the porous carbon-silicon composition comprises a pore structure, and wherein the silicon is at least partially present within the pore structure.
[0116] Embodiment 36: A method as described in any of Embodiments 1-35, wherein the pore structure includes a fibrous morphology and an array of pores surrounding the silicon.
[0117] Embodiment 37: The method of any one of Embodiments 1-36, wherein the porous carbon-silicon composition has a capacity of at least about 800 mAh / g.
[0118] Embodiment 38: The method of any one of Embodiments 1-37, wherein the porous carbon-silicon composition has a silicon utilization efficiency of at least about 20%.
[0119] Embodiment 39: A porous carbon composition in the form of beads, the porous carbon composition comprising a composite material including carbon, wherein the diameter of the beads is in the range of about 1 μm to about 15 μm, and the tap density is about 0.3 g / cm 3 To about 1.3g / cm 3 within the range.
[0120] Embodiment 40: A porous carbon composition as described in Embodiment 39, wherein the carbon comprises carbon aerogel or carbon xerogel.
[0121] Embodiment 41: A porous carbon composition as described in Embodiment 39 or 40, wherein the composite material further comprises silicon in an amount greater than about 10 weight percent based on the total weight of the composition.
[0122] Embodiment 42: A porous carbon composition as described in any of Embodiments 39-41, wherein the composite material comprises about 25 weight percent to about 65 weight percent silicon based on the total weight of the composition.
[0123] Embodiment 43: A porous carbon composition as described in any of Embodiments 39-42, wherein the carbon comprises a pore structure, and wherein the silicon is at least partially present within the pore structure.
[0124] Embodiment 44: A porous carbon composition as described in any of Embodiments 39-43, wherein the composite material has a silicon utilization efficiency of at least about 20%.
[0125] Embodiment 45: A porous carbon composition as described in any of Embodiments 39-44, wherein the silicon has a particle size of less than about 150 nm.
[0126] Embodiment 46: The porous carbon composition of any one of Embodiments 39-45, wherein the silicon has a particle size in a range from about 150 nm to about 500 nm.
[0127] Embodiment 47: A porous carbon composition as described in any of Embodiments 39-46, wherein the particle size of the silicon is greater than about 500 nm.
[0128] Embodiment 48: A porous carbon composition as described in any of Embodiments 39-47, wherein the composite material comprises silicon in the range of about 25 to about 65 weight percent, and the particle size of the silicon is in the range of about 30 nm to about 800 nm; and
[0129] The beads have:
[0130] At about 0.2g / cm 3 To about 1.5g / cm 3 Tap density within the range;
[0131] a diameter ranging from about 1 μm to about 15 μm;
[0132] An average pore size in the range of about 10 nm to about 50 nm; and
[0133] From about 0 to about 500m 2 The BET surface area is in the range of / g.
[0134] Embodiment 49: The porous carbon composition of any one of Embodiments 39-49, having a capacity of at least about 800 mAh / g.
[0135] Embodiment 50: An energy storage device comprising the porous carbon composition as described in any one of Embodiments 39 to 49.
[0136] Embodiment 51: The energy storage device as described in Embodiment 50 is a lithium-ion battery pack.
[0137] These and other features, aspects and advantages of the present disclosure will become apparent by reading the following specific embodiments and the accompanying drawings briefly described below. The present invention includes any combination of two, three, four or more of the above-described embodiments and any combination of two, three, four or more features or elements set forth in the present disclosure, regardless of whether these features or elements are clearly combined in the specific embodiment description herein. The present disclosure is intended to be read as a whole, so that any separable features or elements of the disclosed invention, in any of its various aspects and embodiments, should be deemed to be intended to be combinable, unless the context clearly dictates otherwise.
[0138] Accordingly, the present invention comprises the structural features, combination of elements and arrangement of parts which will be exemplified in the disclosure set forth hereinafter and the scope of the invention will be indicated in the claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0139] In order to provide an understanding of the embodiments of the present technology, reference is made to the accompanying drawings which are not necessarily drawn to scale. The accompanying drawings are exemplary only and should not be interpreted as limitations of the technology. The disclosure described herein is illustrated in the accompanying drawings by way of example and not by way of limitation.
[0140] Figure 1 is a flow chart illustrating the formation of a carbon aerogel for use in battery applications.
[0141] Figure 2 The discharge capacity over several cycles is plotted, comparing silicon-doped monoliths and silicon particles doped via conventional slurry processing.
[0142] Figure 3 is a flow chart illustrating the formation of polyimide-derived carbon aerogel.
[0143] Figure 4 The density of carbonized polyimide (CPI) composites is plotted as a function of compressed thickness (initial thickness is about 250 microns).
[0144] Figure 5 The density of the CPI composite is plotted as a function of compressed thickness (initial thickness was approximately 580 microns).
[0145] Fig. 6A is a scanning electron microscope (SEM) image of the Si-doped uncompressed PI aerogel (LS1).
[0146] Figure 6Bis the SEM image of the Si-doped compressed PI aerogel (LS2).
[0147] Figure 7 The discharge capacity (half-cell battery test, 0.1°C rate) of the compressed composite for each dopant (silicon, LS2; graphite; LG2) is depicted.
[0148] Figure 8 Surface area and micropore area as a function of silicon content in CPI monoliths are plotted.
[0149] Fig. 9 The pore size distribution of Si-doped CPI monoliths is depicted.
[0150] Fig.10 The discharge capacity of the CPI composites at the 5th cycle is plotted as a function of Si content.
[0151] Fig.11A is a SEM image of the CPI composite, and the Si loading in the composite is 27% Si.
[0152] Fig. 11B is a SEM image of the CPI composite, the Si loading in the composite is 46% Si.
[0153] Fig. 11C is a SEM image of the CPI composite, and the Si loading in the composite is 64% Si.
[0154] Fig. 12A The cycling capacity based on 27% Si content (S27) is depicted.
[0155] and Fig. 12A compared to, Fig. 12B The electrode-based cycling capacity is described.
[0156] Fig. 12C The cycling capacity based on 46% Si content (S46) is depicted.
[0157] and Fig. 12C compared to, Fig.12D The electrode-based cycling capacity is described.
[0158] Fig.12E The cycling capacity based on 64% Si content (S64) is depicted.
[0159] and Fig.12E compared to, Fig.12F The electrode-based cycling capacity is described.
[0160] Fig.13A is a SEM image of a CPI composite material with a thickness of about 337 μm.
[0161] Fig. 13B is a SEM image of a CPI composite material with a thickness of about 180 μm.
[0162] Fig.14A The discharge capacity based on the electrode weight (thickness of about 323 μm) is plotted.
[0163] Fig. 14B The discharge capacity based on the electrode weight (thickness of about 170 μm) is plotted.
[0164] Fig.15A is a pre-pyrolysis SEM image of the CPI composite (C45) prepared without dispersant.
[0165] Fig. 15B yes Fig.15A SEM images of the composites after pyrolysis.
[0166] Fig.16A is a SEM image of a CPI composite prepared without a dispersant (C45-control).
[0167] Fig. 16B is a SEM image of a CPI composite (B45) prepared using BYK 384 dispersant.
[0168] Fig. 16C is a SEM image of a CPI composite (P45) prepared using Pluronic F87 dispersant.
[0169] Fig.17A Depicted Fig.16A Discharge capacity of the C45 composite material.
[0170] Fig. 17B Depicted Fig. 16B Discharge capacity of the B45 composite material.
[0171] Fig. 17C Depicted Fig. 16C Discharge capacity of the P45 composite material.
[0172] Fig.18 The density of the P45 CPI composites is plotted as a function of thickness.
[0173] Fig.19 The electrical conductivity of CPI composites doped with various Si levels is plotted as a function of density.
[0174] Fig. 20 is a schematic diagram depicting the formation of polyamic acid.
[0175] Fig.21Isotherms for four (4) CPI samples are depicted.
[0176] Fig. 22 Depicted Fig.21 Pore size distribution of CPI samples.
[0177] Fig.23 is a SEM image of MT material (uncompressed).
[0178] Fig.24 is a SEM image of MT material (compression).
[0179] Fig.25A Depicted are the cycling capacity of compressed CPI samples based on Si content (left) and electrode (right).
[0180] Fig.25B The cycling capacity of the uncompressed CPI samples based on Si content (left) and the electrode (right) are depicted.
[0181] Fig.26A Depicted are the cycling capacity of a compressed CPI sample containing 29 wt% silicon per total solids based on Si content (left) and the electrode (right).
[0182] Fig.26B Depicted are the cycling capacity of an uncompressed CPI sample containing 29 wt% silicon per total solids based on Si content (left) and the electrode (right).
[0183] Fig. 27 Depicts carbon / Si infiltrated carbon fiber (10g / m 2 ) in properties and micrographs.
[0184] Fig.28 Depicts carbon / Si infiltrated carbon fiber (4g / m 2 ) in properties and micrographs.
[0185] Fig.29 Depicts carbon / Si infiltrated carbon fiber (2g / m 2 ) in properties and micrographs.
[0186] Fig.30 The cycling capacity of C / Si reinforced with carbon fibers is depicted based on Si content (left) and electrode (right).
[0187] Fig.31 Depicted are the cycling capacities of C / Si reinforced with cellulose fibers based on Si content (left) and electrode (right).
[0188] Fig.32 is a SEM image of a thick composite (~0.6 mm) where Si and PI were mixed for 16 hours.
[0189] Fig.33 is a SEM image of a thin composite (~0.12 mm) where Si and PI were mixed for 16 hours.
[0190] Fig.34 is the SEM image of a monolithic sample in which Si and PI were mixed for 16 h.
[0191] Fig.35 These are SEM cross-sectional images of C / Si monoliths, where Si and PI are mixed for 16 hours in the left image and for 4-6 minutes in the right image.
[0192] Fig.36 These are SEM cross-sectional images of C / Si composite materials, where Si and PI were mixed for 16 hours in the left image and for 4-6 minutes in the right image.
[0193] Fig.37 The cycling capacity of uncompressed C / Si (mixed for 16 hours) based on Si content (left) and electrodes (right) are depicted.
[0194] Fig.38 The cycling capacity of compressed C / Si (mixed for 16 hours) based on Si content (left) and electrode (right) are depicted.
[0195] Fig.39 Depicted are compressed and circular Si / C electrodes made using a die cutter on aerogel.
[0196] Fig.40 Depicted are the cycling capacities of uncompressed and round C / Si aerogels based on Si content (left) and electrodes (right).
[0197] Fig.41 Depicted are the cycling capacities of compressed and circular C / Si aerogels based on Si content (left) and electrodes (right).
[0198] Fig.42 Depicted is a C / Si aerogel sample produced from a PF / Si aerogel.
[0199] Fig.43 Depicted is a SEM image of a C / Si aerogel (produced from a PF / Si aerogel).
[0200] Fig.44 The cycling capacity of the PF aerogel composite with Si based electrodes is depicted.
[0201] Fig.45 The effect of silicon content on Young's modulus in samples tested by nanoindentation is depicted.
[0202] Fig.46 Depicted is the effect of density on Young's modulus in samples tested by nanoindentation.
[0203] Fig.47 is a SEM image of a granular C / Si aerogel sample according to embodiments disclosed herein.
[0204] Fig.48 Depicted are the cycling performance of electrodes including CPI silicon beads according to embodiments disclosed herein.
[0205] Fig.49A The flow chart of FIG. 1 illustrates a non-limiting process for forming an organogel material in bead form according to an embodiment of the present disclosure.
[0206] Fig.49B The flow chart of FIG. 1 illustrates a non-limiting process for forming an organogel-silicon composite in bead form according to an embodiment of the present disclosure.
[0207] Fig.50 is a SEM image of C / Si aerogel beads according to embodiments disclosed herein.
[0208] Fig.51A and Fig.51B are SEM images showing the outer and inner surfaces, respectively, of C / Si aerogel beads according to embodiments disclosed herein.
[0209] Fig.52 is a SEM image of C / Si xerogel beads according to embodiments disclosed herein.
[0210] Fig.53A and Fig.53B is a micrograph of polyimide / Si composite gel beads according to embodiments disclosed herein.
[0211] Fig.54A and Fig.54B are SEM images showing the outer and inner surfaces, respectively, of C / Si aerogel beads according to embodiments disclosed herein.
[0212] Fig.55 is a SEM image of C / Si xerogel beads according to embodiments disclosed herein.
[0213] Fig.56A and Fig.56B are SEM images showing the outer and inner surfaces, respectively, of C / Si xerogel beads according to embodiments disclosed herein.
[0214] Fig.57A and Fig.57B are SEM images showing the outer and inner surfaces, respectively, of C / Si aerogel beads according to embodiments disclosed herein.
[0215] Fig.58A and Fig.58B are SEM images showing the outer and inner surfaces, respectively, of C / Si xerogel beads according to embodiments disclosed herein.
[0216] Fig.59A and Fig.59B are SEM images showing the outer and inner surfaces, respectively, of C / Si aerogel beads according to embodiments disclosed herein.
[0217] Fig.60 is a graph showing the particle size distribution of aerogel beads according to embodiments disclosed herein. DETAILED DESCRIPTION
[0218] In the following detailed description of the invention, reference is made to the accompanying drawings which form a part hereof, and in which is shown by way of illustration specific embodiments in which the invention may be practiced. It is to be understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the invention.
[0219] definition
[0220] With respect to terms used in this disclosure, the following definitions are provided. This application will use the following terms, as defined below, unless the context of the text in which the term appears requires a different meaning.
[0221] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally used in its sense including "and / or" unless the context clearly dictates otherwise.
[0222] As used herein, "about" means approximately or close to, and in the context of a given numerical value or range, means ±15% of the numerical value. In an embodiment, the term "about" may include traditional rounding according to the significant figures of the numerical value. In addition, the phrase "about 'x' to 'y'" includes "about 'x' to about 'y'".
[0223] In the context of the present disclosure, the term "framework" or "framework structure" refers to a network of interconnected oligomers, polymers or colloidal particles that form the solid structure of a gel, aerogel or xerogel. The diameter of the polymers or particles that make up the framework structure is typically about 100 angstroms. However, the framework structure of the present disclosure may also include a network of interconnected oligomers, polymers or colloidal particles of all diameter sizes that form the solid structure in the gel, aerogel or xerogel.
[0224] As used herein, the term "aerogel" or "aerogel material" refers to a solid object, regardless of its shape or size, comprising a framework of interconnected solid structures, a corresponding network of interconnected pores incorporated within the framework, and which contains a gas, such as air, dispersed in an interstitial medium. Thus, an aerogel is an open non-fluid colloid or polymer network, the entire volume of which is expanded by a gas, and is formed by removing all of the swelling agent from the corresponding wet gel without significant volume reduction or network compression. Aerogels are generally characterized by the following physical and structural properties attributed to aerogels (according to nitrogen porosity testing and helium pycnometry): (a) an average pore size ranging from about 2 nm to about 100 nm; (b) a porosity of at least 60% or more, and (c) a surface area of about 100 m2 as measured by nitrogen adsorption analysis. 2 / g or higher, such as about 100 to about 600m 2 / g. It will be appreciated that the addition of additives, such as reinforcing materials or electrochemically active materials, such as silicon, can reduce the porosity and surface area of the resulting aerogel composite. Densification can also reduce the porosity of the resulting aerogel composite. The aerogel materials (e.g., polyimide and carbon aerogel) disclosed herein include any aerogel that meets the definition elements set forth in the previous paragraph.
[0225] Thus, aerogel materials of the present disclosure include any aerogel or other open-cell compound that meets the defining elements set forth in the preceding paragraphs, including compounds that may otherwise be classified as xerogels, cryogels, amphoteric gels, microporous materials, and the like.
[0226] In the context of the present disclosure, the term "aerogel composition" refers to any composite material that includes an aerogel material as a component of the composite material. Examples of aerogel compositions include, but are not limited to, fiber reinforced aerogel composites; aerogel composites that include additive elements such as opacifiers and electrochemically active materials; aerogel foam composites; aerogel polymer composites; and composites in which aerogel particles, granules, pellets, beads or powders are incorporated into a solid or semi-solid material, such as an adhesive, resin, cement, foam, polymer or similar solid material.
[0227] In the context of the present disclosure, the term "enhanced aerogel composition" refers to an aerogel composition comprising a reinforcing phase in an aerogel material, which is not a part of an aerogel framework or can be modified in a covalently bonded manner to an aerogel framework. The reinforcing phase can be any material that increases the flexibility, elasticity, compliance or structural stability of the aerogel material. Examples of well-known reinforcing materials include, but are not limited to, open-cell foam reinforcing materials, closed-cell foam reinforcing materials, open-cell membranes, honeycomb reinforcing materials, polymer reinforcing materials and fiber-reinforced materials such as discrete fibers, woven materials, nonwoven materials, cotton wool, mesh, mats and felts. In addition, the reinforcement can be combined with one or more other reinforcing materials and can be continuously oriented throughout the composition or in a limited preferred portion of the composition. In other embodiments, if the aerogel material and / or the aerogel framework itself is structurally stable (i.e., self-sustaining), the reinforcing phase can be completely omitted. As this specification continues to unfold, this self-sustaining property of some carbon aerogels will become clearer.
[0228] As used herein, the term "xerogel" refers to a gel comprising an open, non-fluid colloid or polymer network formed by removing all swelling agents from the corresponding gel without taking any precautions to avoid significant volume loss or to delay compression. In contrast to aerogels, xerogels generally comprise a dense structure. Xerogels experience a significant reduction in volume during drying at ambient pressure and have a surface area of 0-100 m2 as measured by nitrogen adsorption analysis. 2 / g, for example, about 0 to about 20 m 2 / g.
[0229] As used herein, the term "gelation" or "gel transition" refers to the formation of a wet gel from a polymer system such as a polyimide or polyamic acid as described herein. At a point in the polymerization or dehydration reaction as described herein (this point is defined as the "gel point"), the sol loses fluidity. Without intending to be bound by any particular theory, the gel point can be regarded as a point at which a gelled solution exhibits resistance to flow. In this context, gelation begins from an initial sol state (in the sol state, the solution mainly comprises an amine salt of a polyamic acid), passes through a fluid colloidal dispersion state, and reaches the gel point until enough polyimide is formed. Thereafter, gelation can continue to produce a polyimide wet gel dispersion with increased viscosity. The amount of time it takes for a polymer in a solution (i.e., polyamic acid and / or polyimide) to transform into a gel that is no longer in a flowing form is referred to as a "phenomenological gel time". Formally, the gel time is measured using rheology. At the gel point, the elasticity of the solid gel begins to dominate the viscosity of the fluid sol. The formal gel time approximates the time at which the real and imaginary parts of the complex modulus of the gelled sol cross. These two moduli are monitored as a function of time using a rheometer. The time is counted from the moment the last component of the sol is added to the solution. For example, see the discussion of gelation in: HH Winter〝Can the Gel Point of a Cross-linking Polymer Be Detected by the G'-G"Crossover? "Polym. Eng. Sci., 1987, 27, 1698–1702; S.-Y. Kim, D.-G. Choi and S.-M. Yang "Rheological analysis of thegelation behavior of tetraethylorthosilane / vinyltriethoxysilane hybrid solutions" Korean J. Chem. Eng., 2002, 19, 190-196; and M. Muthukumar "Screening effect on viscoelasticity near the gel point" Macromolecules, 1989, 22, 4656-4658.
[0230] In the context of the present disclosure, the term "wet gel" refers to a gel in which the mobile interstitial phase within the interconnected pore network consists primarily of a liquid phase (e.g., a conventional solvent), a liquefied gas (e.g., liquid carbon dioxide), or a combination thereof. Aerogels typically require the production of a wet gel followed by processing and extraction to replace the mobile interstitial liquid phase in the gel with air or other gas. Examples of wet gels include, but are not limited to, alcohol gels, hydrogels, keto gels, carbon gels, and any other wet gels known to those skilled in the art.
[0231] In the context of the present disclosure, the term "additive" or "additive element" refers to a material that can be added to the composition before, during, or after production of the composition. Additives can be added, for example, to change or improve desired properties in the aerogel composition, or to offset or mitigate undesirable properties in the aerogel composition. Additives are typically added to the aerogel composition before or during gelation. Additives can also be added to the aerogel composition by atomic layer deposition or chemical vapor deposition (CVD). A specific example of an additive is an electrochemically active material, such as silicon, such as silicon particles.
[0232] In the context of the present disclosure, the term "average particle size" is synonymous with D50, meaning that half of the particles have a particle size above the point and half are below the point. Particle size can be measured by laser scattering techniques or by microscopy. The D90 particle size distribution indicates that 90% of the particles (by number) have a Feret diameter below a specific size as measured by scanning electron microscopy (SEM) or transmission electron microscopy (TEM). The D10 particle size distribution indicates that 10% of the particles (by number) have a Feret diameter below a specific size as measured by scanning electron microscopy (SEM) or transmission electron microscopy (TEM).
[0233] In the context of the present disclosure, the term "conductivity" refers to a measure of a material's ability to conduct an electric current or other ability to allow electrons to pass through or flow therein. Conductivity is specifically measured as the conductivity / susceptance / admittance of a material per unit size of a material. It is usually recorded as S / m (Siemens / meter) or S / cm (Siemens / centimeter). The conductivity or resistivity of a material can be determined by methods known in the art, such as, but not limited to: in-line four-point resistivity (using the dual configuration test method of ASTM F84-99). In the context of the present disclosure, the measurement of conductivity is obtained according to ASTM F84 - the resistivity (R) measurement is obtained by measuring the voltage (V) divided by the current (I), unless otherwise stated. In certain embodiments, the electrical conductivity of the aerogel materials or compositions of the present disclosure is about 10 S / cm or more, 20 S / cm or more, 30 S / cm or more, 40 S / cm or more, 50 S / cm or more, 60 S / cm or more, 70 S / cm or more, 80 S / cm or more, or in a range between any two of these values.
[0234] In the context of the present disclosure, the term "electrochemically active material" refers to an additive that can accept and release ions in an energy storage device. Taking LIB as an example, the electrochemically active material in the anode accepts lithium ions during charging and releases lithium ions during discharge. The electrochemically active material can be stabilized in the anode by direct / physical connection with nanoporous carbon (e.g., carbon-silicon composite aerogel beads). In certain embodiments, the nanoporous carbon network forms an interconnected structure around the electrochemically active material. The electrochemically active material is connected to the nanoporous carbon at multiple points. An example of an electrochemically active material is silicon, which, as previously described, expands and may crack or break when lithiation occurs. However, because silicon has multiple connection points to nanoporous carbon (e.g., carbon aerogel), silicon can be retained and remain active within the nanoporous structure, for example, retained in a pore or otherwise surrounded by the structure, even when broken or cracked.
[0235] In the context of the present disclosure, the terms "compressive strength", "flexural strength" and "tensile strength" refer to the ability of a material to resist fracture or rupture under compression, flexure or bending, and tension or pulling, respectively. These strengths are specifically measured as the amount of load / force per unit area that resists the load / force. Usually recorded as pounds per square inch (psi), megapascals (MPa) or gigapascals (GPa). The compressive strength, flexural strength and tensile strength of a material, in particular, jointly affect the structural integrity of the material, which is beneficial, for example, to withstand the volume expansion of silicon particles during LIB lithiation. With specific reference to Young's modulus as an indication of mechanical strength, the modulus can be determined by methods known in the art, such as, but not limited to: Standard Test Practice for Instrumented Indentation Testing (ASTM E2546, ASTM International, West Conshocken, PA); or Standardized Nanoindentation (ISO 14577, International Organization for Standardization, Switzerland). In the context of the present disclosure, the measured values of Young's modulus are obtained according to ASTM E2546 and ISO 14577, unless otherwise stated. In certain embodiments, the Young's modulus of the aerogel material or composition of the present disclosure is about 0.2 GPa or more, 0.4 GPa or more, 0.6 GPa or more, 1 GPa or more, 2 GPa or more, 4 GPa or more, 6 GPa or more, 8 GPa or more, or in a range between any two of these values.
[0236] In the context of the present disclosure, the term "pore size distribution" refers to the statistical distribution or relative amount of each pore size within a sample volume of a porous material. A narrower pore size distribution refers to a relatively large proportion of pores within a narrower pore size range, thereby optimizing the number of pores that can surround the electrochemically active material and maximizing the use of the pore volume. In contrast, a wider pore size distribution refers to a relatively small proportion of pores within a narrow pore size range. Therefore, the pore size distribution is typically measured as a function of pore volume and recorded as the unit size of the half-maximum full width of the major peak in the pore size distribution graph. The pore size distribution of a porous material can be determined by methods known in the art, such as, but not limited to, surface area and porosity analyzers by nitrogen adsorption and desorption, from which the pore size distribution can be calculated. In the context of the present disclosure, the measured values of the pore size distribution are obtained according to this method, unless otherwise stated. In certain embodiments, the pore size distribution (full width at half maximum) of the aerogel materials or compositions of the present disclosure is relatively narrow, being about 50 nm or less, 45 nm or less, 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 20 nm or less, 15 nm or less, 10 nm or less, 5 nm or less, or in a range between any two of these values.
[0237] In the context of the present disclosure, the term "pore volume" refers to the total volume of pores within a porous material sample. Pore volume is specifically measured as the volume of void space within a porous material, where the void space may be measurable and / or may be measured by another material, such as an electrochemically active material such as silicon particles. It is usually reported as cubic centimeters per gram (cm 3 / g or cc / g). The pore volume of a porous material can be determined by methods known in the art, such as, but not limited to, surface area and porosity analyzers by nitrogen adsorption and desorption, from which the pore volume can be calculated. In the context of the present disclosure, the measured values of pore volume are obtained according to this method unless otherwise stated. In certain embodiments, the pore volume of the aerogel material or composition of the present disclosure (without incorporation of an electrochemically active material, such as silicon) is relatively large, about 1 cc / g or more, 1.5 cc / g or more, 2 cc / g or more, 2.5 cc / g or more, 3 cc / g or more, 3.5 cc / g or more, 4 cc / g or more, or in a range between any two of these values. In other embodiments, the pore volume of the aerogel materials or compositions of the present disclosure (incorporating electrochemically active materials, such as silicon) is about 0.3 cc / g or more, 0.6 cc / g or more, 0.9 cc / g or more, 1.2 cc / g or more, 1.5 cc / g or more, 1.8 cc / g or more, 2.1 cc / g or more, 2.4 cc / g or more, 2.7 cc / g or more, 3.0 cc / g or more, 3.3 cc / g or more, 3.6 cc / g or more, or in a range between any two of these values.
[0238] In the context of the present disclosure, the term "porosity" when used for the porous carbon and carbon-silicon composite materials disclosed herein refers to the volume ratio of pores that do not contain another material (e.g., an electrochemically active material such as silicon particles) bound to the pore walls. For the purpose of clarification and illustration, it should be noted that in the specific implementation of silicon-doped carbon aerogel as the main anode material in LIBs, the porosity refers to the void space after the silicon particles are included. Therefore, when the anode is in a pre-lithiation state (to accommodate ion transport and silicon expansion), the porosity can be, for example, about 10%-70%, and when the anode is in a post-lithiation state (to accommodate ion transport), the porosity can be about 1%-50%. More generally, porosity can be determined by methods known in the art, such as, but not limited to, the ratio of the pore volume of the aerogel material to its bulk density. In the context of the present disclosure, the measured values of porosity are obtained according to this method unless otherwise stated. In certain embodiments, the porosity of the aerogel materials or compositions of the present disclosure is about 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or within a range between any two of these values.
[0239] It should be noted that pore volume and porosity are different measures of the same property of the pore structure (i.e., the "empty space" within the pore structure). For example, when silicon is used as the electrochemically active species contained within the pores of a nanoporous carbon material (e.g., a porous carbon-silicon composite bead as described herein), the pore volume and porosity refer to the "empty" space, i.e., space not utilized by silicon or carbon. As will be seen, densification (e.g., by compression) of a pre-carbonized nanoporous material (e.g., a polyimide gel material) can also have an effect on the pore volume and porosity, as well as other properties.
[0240] In the context of the present disclosure, the term "pore size at max peak from distribution" refers to the value at the discernible peak on a graph illustrating a pore size distribution. The pore size at max peak from distribution is specifically measured as the pore size at which the maximum percentage of pores is formed. It is typically recorded as any unit length of pore size, such as micrometers or nanometers (nm). The pore size at max peak from distribution can be determined by methods known in the art, such as, but not limited to, surface area and porosity analyzers by nitrogen adsorption and desorption, from which the pore size distribution can be calculated and the full peak pore size can be determined. In the context of the present disclosure, the measured value of the pore size at max peak from distribution is obtained according to this method, unless otherwise stated. In certain embodiments, the aerogel materials or compositions of the present disclosure have a distribution of full peak pore size of about 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, 50 nm or less, 40 nm or less, 30 nm or less, 20 nm or less, 10 nm or less, 5 nm or less, 2 nm or less, or in a range between any two of these values.
[0241] In the context of this disclosure, the term "BET surface area" has its ordinary meaning and refers to the Brunauer-Emmett-Teller method for determining surface area by N2 adsorption measurements. 2 The BET surface area expressed as % / g is a measure of the total surface area of a porous material (e.g., a nanoporous carbon as described herein) per unit mass. Unless otherwise specified, "surface area" refers to the BET surface area. As an alternative to the BET surface area, the geometric external surface area of, for example, a polyimide or carbon bead can be calculated based on the diameter of the bead. Typically, such geometric external surface areas of the beads of the present disclosure are between about 3 and about 700 μm. 2 within the range.
[0242] In the context of the present disclosure, the term "pillar width" refers to the average diameter of the nanopillars, nanorods, nanofibers or nanowires that form an aerogel with a fibrous morphology. It is usually recorded as any unit length, such as micrometers or nm. The pillar width can be determined by methods known in the art, such as, but not limited to, scanning electron microscope image analysis. In the context of the present disclosure, the measured value of the pillar width is obtained according to this method, unless otherwise stated. In certain embodiments, the pillar width of the aerogel material or composition of the present disclosure is about 10nm or less, 9nm or less, 8nm or less, 7nm or less, 6nm or less, 5nm or less, 4nm or less, 3nm or less, 2nm or less, or in the range between any two of these values. The exemplary range of pillar width found in the following examples (and particularly seen in the SEM images in the figures) is about 2-5nm. Smaller pillar widths (such as these) allow a larger amount of support to be present in the network and thus contact the electrochemically active material, thereby allowing more electrochemically active materials to be present in the composite material. This increases conductivity and mechanical strength.
[0243] In the context of the present disclosure, the term "cycle life" refers to the number of complete charge / discharge cycles that an anode or battery (e.g., LIB) can support before its capacity drops below about 80% of its original rated capacity. Cycle life can be affected by a variety of factors that are not significantly affected over time, such as the mechanical strength of the underlying substrate (e.g., carbon aerogel), the connectivity of the silicon particles within the aerogel, and the maintenance of the interconnectivity of the aerogel. It should be noted that the fact that these factors remain relatively unchanged over time is a surprising aspect of certain embodiments of the present invention. Cycle life can be determined by methods known in the art, such as, but not limited to, cycle testing, in which battery cells are subjected to repeated charge / discharge cycles at a predetermined current rate and operating voltage. In the context of the present disclosure, measurements of cycle life are obtained according to this method unless otherwise stated. In certain embodiments of the present disclosure, the cycle life of an energy storage device such as a battery or an electrode thereof is about 25 cycles or more, 50 cycles or more, 75 cycles or more, 100 cycles or more, 200 cycles or more, 300 cycles or more, 500 cycles or more, 1000 cycles or more, or in a range between any two of these values.
[0244] In the context of the present disclosure, the term "capacity" refers to the amount of specific energy or charge that a battery can store. Capacity is specifically measured as the discharge current that can be provided by a battery per unit mass over time. It is usually recorded as ampere hours or milliampere hours per gram of total electrode mass, Ah / g or mAh / g. The capacity of a battery (especially an anode) can be determined by methods known in the art, such as, but not limited to: applying a fixed constant current load to a fully charged battery until the voltage of the battery reaches the limit discharge voltage value; the time to reach the discharge termination voltage multiplied by the constant current is the discharge capacity; by dividing the discharge capacity by the weight or volume of the electrode material, the specific capacity and volumetric capacity can be determined. In the context of the present disclosure, the measured value of capacity is obtained according to this method, unless otherwise stated. In certain embodiments, the capacity of the aerogel material or composition of the present disclosure is about 200 mAh / g or more, 300 mAh / g or more, 400 mAh / g or more, 500 mAh / g or more, 600 mAh / g or more, 700 mAh / g or more, 800 mAh / g or more, 900 mAh / g or more, 1000 mAh / g or more, 1200 mAh / g or more, 1400 mAh / g or more, 1600 mAh / g or more, 1800 mAh / g or more, 2000 mAh / g or more, 2400 mAh / g or more, 2800 mAh / g or more, 3200 mAh / g or more, or in a range between any two of these values. Unless otherwise stated, when the current nanoporous carbon material is used in a battery pack, the capacity is reported at the 10th cycle of the battery pack.
[0245] In the context of this disclosure, the term "silicon utilization efficiency" refers to the difference between the theoretical capacity of silicon lithiation and the measured capacity of the electrode based on the weight of silicon. Silicon utilization efficiency is specifically measured as the efficiency of the use of silicon within the electrode. It is recorded here as a percentage using the following equation:
[0246]
[0247] To calculate the utilization efficiency of silicon, the capacity of the electrode and the capacity of silicon are measured as described above. In certain embodiments, the silicon utilization of the aerogel material or composition of the present disclosure is about 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, or in a range between any two of these values, where a higher percentage indicates better or more efficient silicon utilization. Unless otherwise stated, when the current nanoporous carbon material (e.g., porous carbon-silicon composite beads) is used in a battery pack, the silicon utilization is reported at the 10th cycle of the battery pack.
[0248] The term "alkyl" as used herein refers to a straight or branched chain saturated hydrocarbon typically having 1 to 20 carbon atoms. Representative alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, n-butyl, n-pentyl, and n-hexyl; while branched alkyl groups include, but are not limited to, isopropyl, sec-butyl, isobutyl, tert-butyl, isopentyl, and neopentyl. Alkyl groups may be unsubstituted or substituted.
[0249] The term "alkenyl" as used herein refers to a hydrocarbon containing positive, secondary or tertiary carbon atoms, typically having 1 to 20 carbon atoms, having at least one unsaturated site, i.e., a carbon-carbon double bond. Examples include, but are not limited to, ethylene or vinyl, allyl, 1-butenyl, 2-butenyl, isobutenyl, 1-pentenyl, 2-pentenyl, 3-methyl-1-butenyl, 2-methyl-2-butenyl, 2,3-dimethyl-2-butenyl, etc. Alkenyl can be unsubstituted or substituted.
[0250] The term "alkynyl" as used herein refers to a hydrocarbon containing positive, secondary or tertiary carbon atoms, typically having 1 to 20 carbon atoms, with at least one site of unsaturation, i.e., a carbon-carbon triple bond. Examples include, but are not limited to, acetylene and propargyl. Alkynyl can be unsubstituted or substituted.
[0251] The term "aryl" as used herein refers to a carbocyclic aromatic group typically having 6 to 20 carbon atoms. Examples of aryl groups include, but are not limited to, phenyl, naphthyl, and anthracenyl. Aryl groups may be unsubstituted or substituted.
[0252] The term "cycloalkyl" as used herein refers to a saturated carbocyclic group, which may be monocyclic or bicyclic. Cycloalkyl includes rings having 3 to 7 carbon atoms as monocyclic or 7 to 12 carbon atoms as bicyclic. Examples of monocyclic cycloalkyls include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl and cyclooctyl. Cycloalkyl may be unsubstituted or substituted.
[0253] The term "substituted" as used herein and applied to any of the above alkyl, alkenyl, alkynyl, aryl, cycloalkyl, etc., means that one or more hydrogen atoms are each independently replaced by a substituent. Typical substituents include, but are not limited to, -X, -R, -OH, -OR, -SH, -SR, NH2, -NHR, -N(R)2, -N +(R)3, -CX3, -CN, -OCN, -SCN, -NCO, -NCS, -NO, -NO2, -N3, -NC(=O)H, -NC(=O)R, -C(=O)H, -C(=O)R, -C(=O)NH2, -C(=O)N (R)2, -SO3-, -SO3H, -S(=O)2R, -OS(=O)2OR, -S(=O)2NH2, -S(=O)2N(R)2, -S(=O)R, -OP(=O)(OH)2, -OP(=O)(OR)2, -P( =O)(OR)2, -PO3, -PO3H2, -C(=O)X, -C(=S)R, -CO2H, -CO2R, -CO2-, -C(=S)OR, -C(=O)SR, -C(=S)SR, -C(=O)NH2, -C(=O)N(R)2, -C(=S)NH2, -C(=S)N(R)2, -C(=NH)NH2, and -C(=NR)N(R)2; wherein each X is independently selected at each occurrence from F, Cl, Br, and I; and each R is independently selected at each occurrence from Cl-C 20 Alkyl and C6-C 20 Aryl. When a group is described as "optionally substituted," the group may be substituted independently at each occurrence with one or more of the above substituents.
[0254] It should be understood that some group naming conventions can include monoradicals or diradicals, depending on the context. For example, in the case where a substituent requires two points of attachment to the rest of the molecule, it should be understood that this substituent is a diradical. For example, a substituent identified as an alkyl group requiring two points of attachment includes a diradical, such as -CH2-, -CH2CH2-, -CH2CH(CH3)CH2-, etc. Other group naming conventions clearly indicate that a group is a diradical, such as "alkylene", "alkenylene", "arylene", etc.
[0255] In any case where a substituent is depicted as a biradical (ie, having two points of attachment to the rest of the molecule), it is understood that the substituent may be attached in any orientation configuration unless otherwise indicated.
[0256] In the context of the present disclosure, the term "self-supporting" refers to the ability of an aerogel material or composition to be flexible and / or resilient primarily based on the physical properties of the aerogel. The self-supporting aerogel material or composition of the present disclosure may be distinguished from other aerogel materials (e.g., coatings) that rely on an underlying substrate or reinforcement material to provide flexibility and / or resiliency to the material.
[0257] In the context of this disclosure, the term "density" refers to a measure of the mass of an aerogel material or composition per unit volume. The term "density" generally refers to the true density of an aerogel material, as well as the bulk density of an aerogel composition. Density is generally reported as kg / m 3 or g / cc. The density of an aerogel material or composition can be determined by methods known in the art, including, but not limited to, Standard Test Method for Dimensions and Density of Preformed Block and Board-Type Thermal Insulation (ASTM C303, ASTM International, West Conshohocken, Pa.); Standard Test Methods for Thickness and Density of Blanket or Batt Thermal Insulations (ASTM C167, ASTM International, West Conshohocken, Pa.); or Determination of the apparent density of preformed pipe insulation (ISO 18098, International Organization for Standardization, Switzerland). In the context of the present disclosure, density measurements are obtained according to ASTM C167 unless otherwise specified. Preferably, the aerogel material or composition of the present disclosure has a density of about 1.50 g / cc or less, about 1.40 g / cc or less, about 1.30 g / cc or less, about 1.20 g / cc or less, about 1.10 g / cc or less, about 1.00 g / cc or less, about 0.90 g / cc or less, about 0.80 g / cc or less, about 0.70 g / cc or less, about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, about 0.20 g / cc or less, about 0.10 g / cc or less, or in a range between any two of these values, for example, between about 0.15 g / cc and 1.5 g / cc, or, more specifically, 0.50 g / cc and 1.30 g / cc.
[0258] In the context of this disclosure, the term "tap density" of a material or composition (e.g., carbon-silicon composite beads) refers to the maximum density reached when the particulate material is vibrated or tapped under specific conditions. The tap density reflects the voids between particles (e.g., beads) created by random dense packing. The tap density is always lower than the bulk (or envelope) density of the particles. The formula M / V can be used. f Calculate the tap density, where M = mass (g), V f = Tap volume (ml). Tap density is usually measured by first gently introducing a known mass of sample into a graduated cylinder and carefully flattening the powder without compacting. The graduated cylinder is then mechanically tapped using a suitable mechanical tap density tester that provides a suitable fixed drop distance and nominal drop rate by raising the graduated cylinder and allowing it to fall under its own weight. Standard test methods for tap density measurements are described in MPIF-46, ASTM B-527, and ISO 3953. In some embodiments, the tap density of the material or composition of the present disclosure is about 1.50 g / cc or less, about 1.40 g / cc or less, about 1.30 g / cc or less, about 1.20 g / cc or less, about 1.10 g / cc or less, about 1.00 g / cc or less, about 0.90 g / cc or less, about 0.80 g / cc or less, about 0.70 g / cc or less, about 0.60 g / cc or less, about 0.50 g / cc or less, about 0.40 g / cc or less, about 0.30 g / cc or less, or about 0.20 g / cc or less. In some embodiments, the tap density is between about 0.2 g / cc and about 1.5 g / cc.
[0259] Method for forming organic aerogel beads
[0260] According to certain embodiments, the production of aerogels generally comprises the steps of: i) forming a solution comprising a gel precursor; ii) forming a gel from the solution; and iii) extracting the solvent from the gel material to yield a dried aerogel material.
[0261] According to certain embodiments, the production of aerogel beads follows the general process of producing aerogels and generally includes the following steps: i) forming a solution containing a gel precursor; ii) dispersing the gel precursor in a medium that is immiscible with the gel precursor; iii) forming gel beads from the gel precursor solution in the immiscible medium; iv) removing the gel beads from the medium; and v) extracting the solvent from the gel beads to obtain a dry aerogel material. These processes are discussed in more detail below, particularly in the context of forming organic aerogels such as polyimide aerogels. However, the specific examples and descriptions provided herein are not intended to limit the present disclosure to any particular type of aerogel and / or preparation method. The present disclosure may include any aerogel formed by any relevant preparation method known to those skilled in the art.
[0262] An exemplary solution for producing an organic aerogel is formed by combining at least one organogel precursor with a solvent. Suitable solvents for forming the solution include lower alcohols having 1 to 6 carbon atoms, preferably 2 to 4 carbon atoms, but other solvents known to those skilled in the art may also be used. Examples of useful solvents include, but are not limited to, methanol, ethanol, isopropanol, ethyl acetate, ethyl acetoacetate, acetone, dichloromethane, tetrahydrofuran, 1-methyl-2-pyrrolidone (NMP), dimethylacetamide (DMAC), formamide, and the like. Multiple solvents may also be combined to achieve the desired dispersion level or to optimize the properties of the gel material. Therefore, the optimal solvent selection for the polymerization and gel formation steps depends on the specific precursors, fillers, and additives added to the solution; as well as the target processing conditions for gelation and liquid phase extraction, and the desired properties of the final aerogel material.
[0263] An exemplary solution for producing a polyimide aerogel is formed by combining at least one diamine and at least one dianhydride in a common polar aprotic solvent. In some embodiments, the dianhydride component is dissolved in a solvent and then the diamine component is added to the solution. In the context of the present disclosure, adding the diamine to the dianhydride solution is referred to as a "standard addition" process. In other embodiments, the diamine component is dissolved in a solvent and then the dianhydride component is added. In the context of the present disclosure, adding the dianhydride to the diamine solution is referred to as a "reverse addition" process.
[0264] Additional details on the formation of polyimide gels / aerogels can be found in U.S. Pat. Nos. 7,074,880 and 7,071,287 to Rhine et al.; U.S. Pat. No. 6,399,669 to Suzuki et al.; U.S. Pat. No. 9,745,198 to Leventis et al.; Leventis et al., "Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP)," Chem. Mater. 2011, 23, 8, 2250-2261; Leventis et al., "Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides," MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01.doi:10.1557 / opl.2011.90; Chidambareswarapattar et al., "One-step room-temperature synthesis of fibrouspolyimide aerogels from anhydrides and isocyanates and conversion toisomorphic carbons," J.Mater.Chem., 2010, 20, 9666–9678; Guo et al., "PolyimideAerogels Cross-Linked through Amine Functionalized PolyoligomericSilsesquioxane," ACS Appl.Mater.Interfaces 2011, 3, 546–552; Nguyen et al., "Development of High Temperature, Flexible Polyimide Aerogels," American Chemical Society, proceedings published 2011; Meador et al., "Mechanically Strong, Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine," ACSAppl.Mater.Interfaces, 2012, 4(2), pp. 536–544; Meador et al., "Polyimide Aerogels with Amide Cross-Links: A Low Cost Alternative for Mechanically Strong Polymer Aerogels," ACS Appl. Mater. Interfaces 2015, 7, 1240-1249; Pei et al., "Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups," Langmuir 2014, 30, 13375-13383, each of which is incorporated herein by reference in its entirety. .
[0265] Instead of or in addition to diamines, triamines, tetraamines, pentamines, hexamines, etc. or combinations thereof may also be used to optimize the properties of the gel material. Instead of or in addition to dianhydrides, trianhydrides, tetraanhydrides, pentaanhydrides, hexaanhydrides or combinations thereof may also be used to optimize the properties of the gel material. Dehydrating agents and catalysts may be incorporated into the solution to initiate and drive imidization. The solution may include additional co-gelling precursors, as well as filler materials and other additives. Filler materials and other additives may be distributed into the solution at any time before or during gel formation. Filler materials and other additives may also be incorporated into the gel material after gelation by various techniques known to those skilled in the art. Preferably, the solution comprising gelling precursors, solvents, catalysts, water, filler materials and other additives is a homogeneous solution that is capable of effectively forming a gel under suitable conditions.
[0266] Once the solution is formed and optimized, the gel-forming components in the solution can be converted into a gel material. The process of converting the gel-forming components into a gel material includes an initial gel formation step, in which the gel solidifies until the gel point of the gel material. The gel point of the gel material can be regarded as the point at which the gelled solution exhibits resistance to flow and / or forms a substantially continuous polymer backbone throughout its volume. A range of gel formation techniques are known to those skilled in the art. Examples include, but are not limited to: keeping the mixture in a quiescent state for a sufficient period of time; adjusting the concentration of the catalyst; adjusting the temperature of the solution; directing a form of energy to the mixture (ultraviolet light, visible light, infrared, microwave, ultrasound, particle radiation, electromagnetic); or a combination thereof.
[0267] In some embodiments, the gel material (e.g., organic aerogel or carbon aerogel and xerogel) can be in a beaded form (i.e., a plurality of beads). As used herein, the term "bead" is intended to include discrete small units or blocks having a generally spherical shape. In some embodiments, the beads are substantially spherical. The composition of the beads is generally uniform, so that each bead in the plurality of beads contains approximately the same amount of the same component within the normal range of variation expected when preparing such beads. The size of the beads can vary depending on the desired properties and preparation methods.
[0268] The process of forming gel beads from a gel solution can include merging the solution with a medium that is immiscible with the solution, such as a dispersion medium. For example, silicone oil or mineral oil can be used as a dispersion medium. The gel solution can be added, for example, by pouring or otherwise merging with an immiscible dispersion medium. The stirring (e.g., by mixing) of the combined dispersion medium and gel precursor solution can be used to promote the formation of droplets (e.g., beads) before or during the process of the gel-forming components being transformed into a gel material. For example, the merging of a dispersion medium and a gel precursor can form an emulsion with a gel precursor solution as a dispersed phase. Exemplary methods for the generation of gel beads can be found in U.S. Patent Application Publication No. 2006 / 0084707 to Ou et al., which is incorporated herein by reference in its entirety.
[0269] Due to interfacial tension, spherical droplets of the gel precursor are formed in the dispersion medium. The droplets gel in the dispersion medium (e.g., silicone oil) and strengthen during this period. Agitation of the mixture is generally used to prevent the droplets from agglomerating. For example, the mixture of the gel precursor and the dispersion medium can be stirred to prevent the droplets from agglomerating.
[0270] Heat or radiation may also be provided to the dispersion medium to induce or enhance gelation of the droplets or to strengthen the gel beads to make them strong enough to withstand collisions. The production capacity of gel beads in a given space depends on precise control of the droplet gelation process.
[0271] The process further comprises removing the gel beads from a dispersion medium such as silicone oil, mineral oil or solvent oil. The gel beads are filtered out from the dispersion medium, and then washed or rinsed with a fluid such as alcohols such as ethanol, methanol, isopropanol or a higher alcohol. Hydrocarbon solvents such as heptane, hexane or octane can also be used. A basic requirement for the rinse fluid is that it can remove oil (or other dispersion media) without chemically reacting with the gel. After removing excess medium (e.g., silicone oil), the gel beads can be placed in a solvent for aging, as discussed in more detail below. For example, the gel beads can be aged in ethanol. The interstitial solvent can be removed from the gel beads using a supercritical fluid drying method such as discussed herein. They can also be dried under ambient conditions to prepare xerogels. Dry gel beads, such as aerogels or xerogel beads, can be heat treated and carbonized, as discussed in more detail below.
[0272] In an exemplary embodiment, the organogel beads are polyimide beads, and the polyimide beads are prepared by a three-step method, including the step of preparing a polyamic acid sol; optionally, the step of adding an electroactive material such as silicon to the polyamic acid sol; and the step of imidizing the polyamic acid sol (optionally, in a mixture with silicon) under shear conditions, such as high or low shear (or high or low rpm) mixing of the mixture. In certain exemplary embodiments, the polyamic acid sol is prepared at ambient temperature. N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAC) or N,N-dimethylformamide (DMF) solvents can be used to prepare polyimide precursors. In certain embodiments, starting monomers, such as aromatic dianhydrides and aromatic diamines, can be dissolved in the above-mentioned solvents and stirred under ambient conditions. In a preferred embodiment, the monomer solution can be prepared under an inert gas stream such as nitrogen or argon.
[0273] In some embodiments, silicon particles are incorporated into the composition disclosed herein during the sol-gel process. In a first embodiment, silicon particles are dispersed in a polyamic acid sol before imidization. In a second embodiment, silicon particles are dispersed in a solvent such as DMAC or other solvents compatible with the polyamic acid sol before the solvent is combined with the polyimide precursor. In a third embodiment, silicon particles are dispersed in a polyamic acid sol during the imidization process. In other embodiments, silicon particles are incorporated after imidization or even after carbonization of the organic gel.
[0274] In one aspect of the present disclosure, a porous carbon composition in the form of beads is provided. In one embodiment, the porous carbon composition is prepared according to a method generally comprising: providing an organogel precursor in an organic solvent; initiating gelation of the organogel precursor to form an organogel sol; combining the organogel sol with a medium that is immiscible with the organogel sol to form organogel droplets; separating the organogel droplets; drying the droplets to produce porous organogel beads; and pyrolyzing the porous organogel beads to produce porous carbon composition beads. Fig.49A A general non-limiting scheme for preparing porous organogel beads is provided in . Fig.49A , providing an organogel precursor in an organic solvent, initiating gelation, and combining the gel precursor (i.e., organogel sol) with a medium immiscible with the organogel sol. Then, gel droplets are generated by mixing under high shear conditions, and the droplets are separated and optionally further processed (e.g., washing, solvent exchange, drying, and pyrolysis).
[0275] In some embodiments, the organogel is a resorcinol-formaldehyde polymer, a phloroglucinol-formaldehyde polymer, a cellulosic polymer, a polyurea, a polyurethane, an alginate, or a polyacrylonitrile. Such organogel polymers are discussed further below.
[0276] In some embodiments, the organogel is a polyimide. In some embodiments, the organogel is a polyimide and the organogel precursor is a polyamic acid. In some embodiments, a preformed polyamic acid may be provided. For example, the polyamic acid may be purchased. Alternatively, the polyamic acid may be prepared by reacting a polyfunctional amine and a polyfunctional anhydride in an organic solvent. Thus, in some embodiments, the method includes reacting a polyfunctional amine and a polyfunctional anhydride with each other to form a polyamic acid as the organogel precursor.
[0277] As used herein, the term "polyfunctional anhydride" refers to a molecule having at least two dicarboxylic anhydride groups that can be used for reactions as described below. In some embodiments, the polyfunctional anhydride is a tetracarboxylic dianhydride. In some embodiments, instead of or in addition to tetracarboxylic dianhydride, trianhydrides, tetraanhydrides, pentaanhydrides, hexaanhydrides, etc. can be used to optimize the properties of the gel material.
[0278] In such embodiments, those skilled in the art will recognize that the polyamic acid includes an amino group containing a polyfunctional amine and an amide unit corresponding to a carboxylic acid group of a tetracarboxylic anhydride. Therefore, such polyamic acid may be described herein as "comprising a tetracarboxylic acid" and "comprising a polyfunctional amine" (e.g., a diamine).
[0279] The structure of the tetracarboxylic dianhydride can vary. In some embodiments, the tetracarboxylic dianhydride has a structure according to Formula I:
[0280]
[0281] Wherein L comprises alkyl, cycloalkyl, aryl or its combination, each as described above. In some embodiments, L comprises aryl. In some embodiments, L comprises phenyl, biphenyl or diphenyl ether. In some embodiments, the tetracarboxylic dianhydride of formula I has a structure selected from one or more structures provided in Table 1.
[0282] Table 1. Non-limiting list of potential tetracarboxylic dianhydrides
[0283]
[0284] In some embodiments, the tetracarboxylic dianhydride is selected from the group consisting of pyromellitic anhydride (PMDA), phthalic anhydride (BPDA), oxydiphthalic anhydride (ODPA), benzophenonetetracarboxylic dianhydride (BTDA), ethylenediaminetetraacetic dianhydride (EDDA), 1,4,5,8-naphthalenetetracarboxylic dianhydride, and combinations thereof. In some embodiments, the tetracarboxylic dianhydride is PMDA. Thus, the polyamic acid produced from such tetracarboxylic dianhydrides can be described as comprising a tetracarboxylic acid selected from the group consisting of benzene-1,2,4,5-tetracarboxylic acid, [1,1'-biphenyl]-3,3',4,4'-tetracarboxylic acid, 4,4'-oxydiphthalic acid, 4,4'-sulfonyldiphthalic acid, 4,4'-carbonyldiphthalic acid, 4,4'-(propane-2,2-diyl)diphthalic acid, 4,4'-(perfluoropropane-2,2-diyl)diphthalic acid, naphthalene-1,4,5,8-tetracarboxylic acid, 4-(2-(4-(3,4-dicarboxyphenoxy)phenyl)prop-2-yl)phthalic acid, perylenetetracarboxylic acid, and combinations thereof.
[0285] As used herein, the term "multifunctional amine" refers to a molecule having at least two primary amino groups that can be used for reactions as described below. In some embodiments, the multifunctional amine is a triamine, a tetramine, a pentamine, a hexamine, etc. In some embodiments, the multifunctional amine is a diamine. In some embodiments, in addition to diamines, triamines, tetramines, pentamines, hexamines, etc. can also be used to optimize the properties of the gel material. In some embodiments, the multifunctional amine includes triamines or is a triamine. Non-limiting examples of suitable triamines include propane-1,2,3-triamine, benzene-1,3,5-triamine, cyclohexane-1,3,5-triamine, 1,3,5-tris(4-aminophenoxy)benzene (TAPOB), tris(4-aminophenyl)methane and 1,3,5-triazine-2,4,6-triamine (melamine). In some embodiments, the multifunctional amine is 1,3,5-tris(4-aminophenoxy)benzene (TAPOB), tris(4-aminophenyl)methane, melamine or a combination thereof. In some embodiments, the multifunctional amine is melamine.
[0286] In a preferred embodiment, the multifunctional amine is a diamine. Thus, the polyamic acid produced from the diamine can be described as comprising such a diamine. The structure of the diamine can vary. In some embodiments, the diamine has a structure according to Formula II:
[0287]
[0288] Wherein Z is aliphatic (i.e., alkyl, alkenyl, alkynyl, or cycloalkyl) or aryl, each as described above. In some embodiments, Z is an alkyl, such as a C2 to C12 alkyl. In some embodiments, the diamine is an alkane diamine, such as a C2 to C6 alkane diamine. Suitable alkane diamines include, but are not limited to, ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, or 1,6-diaminohexane. In some embodiments, the C2 to C6 alkane diamine is substituted with one or more alkyl groups (e.g., methyl).
[0289] In some embodiments, Z is an aryl group and the multifunctional amine is an aryl diamine. In some embodiments, the aryl diamine is 1,4-phenylenediamine (PDA), 4,4'-diaminodiphenyl ether, 4,4'-methylenedianiline, or a combination thereof. In some embodiments, the diamine is PDA. In some embodiments, the diamine is 4,4'-diaminodiphenyl ether. In some embodiments, the diamine is 4,4'-methylenedianiline.
[0290] The molecular weight of polyamic acid and corresponding organogel (i.e., polyimide gel) can vary based on reaction conditions (e.g., concentration, temperature, reaction duration, properties of diamines and dianhydrides, etc.). The molecular weight is based on the number of polyamic acid repeating units. A repeating unit as defined herein is a portion of a polyamic acid or polyamide whose repetition will produce a complete polymer chain (except for the terminal amino groups) by continuously linking the repeating units together along the polymer chain.
[0291] The specific molecular weight range of the polyimide produced by the disclosed method can vary.Usually, the described reaction conditions can be changed to provide the polyimide with the required physical property, without special consideration of molecular weight.In some embodiments, a substitute of molecular weight can be provided in the viscosity of the polyamic acid solution, and the viscosity can be controlled by regulating the described variable (the presence of temperature, concentration, the mol ratio of the component, the reaction time, the solvent, the water, etc.), as further disclosed below.
[0292] The molar ratio of a multifunctional anhydride (e.g., tetracarboxylic dianhydride) to a multifunctional amine (e.g., diamine) can vary according to the desired reaction time, reagent structure, and desired material properties. In some embodiments, the molar ratio is from about 0.9 to about 3, such as from about 0.9 or about 1 to about 2 or about 3. In some embodiments, the ratio is about 1 (i.e., stoichiometric), such as from about 0.9 to about 1.1. In a specific embodiment, the ratio is from about 0.99 to about 1.01.
[0293] Typically, multifunctional amine (e.g., diamine) and multifunctional anhydride (e.g., tetracarboxylic dianhydride) are allowed to react for a period of time to complete the reaction between amino and anhydride groups, providing polyamic acid. Typically, the reaction is allowed to proceed until all available reactants (e.g., diamine and dianhydride) have reacted with each other. The time required to complete the reaction can vary based on reagent structure, concentration, temperature. In some embodiments, the reaction time is about 1 minute to about 1 week, such as about 15 minutes to about 5 days, about 30 minutes to about 3 days, or about 1 hour to about 1 day. In some embodiments, the reaction time is about 0.5 hour to about 17 hours. In some embodiments, the reaction time is about 1 hour to about 12 hours.
[0294] The organic solvent used can vary, but is typically a polar aprotic solvent. In some embodiments, the organic solvent is N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, or ethyl acetate. In some embodiments, the organic solvent is N,N-dimethylacetamide.
[0295] In some embodiments, the organic solvent is anhydrous, meaning that it is water-free or substantially water-free. In other embodiments, the organic solvent further comprises water. The amount of water present can vary based on a variety of factors, such as target density, viscosity, expected particle size, scale, etc. Surprisingly, it has been found according to the present disclosure that before gelation, the inclusion of low levels of water in the organic solvent provides smaller organogel droplets, resulting in smaller bead sizes (i.e., smaller organogel and corresponding porous carbon bead sizes). Without wishing to be bound by any particular theory, it is believed that the presence of water reduces the viscosity of the medium and delays the gelation of the organogel precursor (e.g., polyamic acid). In some embodiments, water is present in the organic solvent in an amount of about 100 parts per million (ppm) to about 1500ppm (e.g., about 500ppm to about 1200ppm, or about 500ppm to about 700ppm). In some embodiments, water is present in the organic solvent in an amount of about 500 ppm, about 600 ppm, about 700 ppm, about 800 ppm, about 900 ppm, about 1000 ppm, about 1100 ppm, or about 1200 ppm.
[0296] The temperature for reacting between a multifunctional anhydride (e.g., tetracarboxylic dianhydride) and a multifunctional amine (e.g., diamine) can vary. Suitable temperature ranges are typically between about 10° C. and about 100° C. In some embodiments, the reaction temperature is about 10° C. to about 100° C., or about 15° C. to about 60° C., or about 15° C. to about 50° C., or about 15° C. to about 25° C.
[0297] The concentration of the resulting polyamic acid in the solution may vary. For example, in some embodiments, the concentration of the polyamic acid (i.e., the density of the polyamic acid in the solution) is from about 0.01 to about 0.3 g / cm 3 In some embodiments, the volume of solvent is selected to provide a specific target density (T d Typically, the concentration of polyamic acid present in the solution is in the range of about 0.01 to about 0.3 g / cm 3 .
[0298] In some embodiments, the porous carbon composition is a porous carbon-silicon composition comprising greater than about 10% by weight silicon. In such embodiments, the method further comprises providing a mixture of an organogel precursor and silicon in an organic solvent. Typically, the silicon is in particulate form, and the silicon particles are incorporated in a sol-gel process. Fig.49B A general non-limiting scheme for preparing porous organogel-silica composite beads is provided. Fig.49B , the method includes providing a mixture of silicon and an organogel precursor in an organic solvent. In some embodiments, the silicon particles are dispersed in a solvent (e.g., a polar aprotic solvent) before being combined with the organogel precursor. In a non-limiting embodiment, the silicon particles are dispersed in a polyamic acid sol before imidization. In another non-limiting embodiment, the silicon particles are dispersed in a polyamic acid sol during imidization.
[0299] In the context of the present disclosure, the term "silicon particles" refers to silicon having a particle size range suitable for use in an organogel (e.g., polyimide) or carbon gel as disclosed herein. The silicon particles of the present disclosure may be nanoparticles, such as particles having two or three sizes in the range of about 1 nm to about 150 nm. The silicon particles of the present disclosure may be fine particles, such as micron-sized particles having a maximum dimension (e.g., the diameter of a substantially spherical particle) in the range of about 150 nm to about 10 microns or more. For example, the maximum dimension (e.g., the diameter of a substantially spherical particle) of the silicon particles of the present disclosure may be about 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 500 nm, 1 micron, 1.5 microns, 2 microns, 3 microns, 5 microns, 10 microns, 20 microns, 40 microns, 50 microns, 100 microns, or in a range between any two of these values. In some embodiments, the particle is a flat fragment shape, such as a small piece, with about 10nm, 50nm, 100nm, 150nm, 200nm, 500nm, 1 micron, 1.5 microns, 2 microns, 3 microns, 5 microns, 10 microns, 20 microns, 40 microns, 50 microns, 100 microns or two sizes (such as length and width) in the range between any two of these values. In some embodiments, the silicon particles can be monodisperse or substantially monodisperse. In other embodiments, the silicon particles can have a particle size distribution. In the context of the present disclosure, the size of the silicon particles is based on the median (i.e. D50) of the particle size distribution.
[0300] Silicon particles can be produced by various techniques, including electrochemical reduction and mechanical mixing, i.e., grinding. Wet or dry processes can be used for grinding. In the dry grinding process, the powder is added to a container together with the grinding media. The grinding media typically include balls or rods of zirconium oxide (yttrium-stabilized zirconium oxide), silicon carbide, silicon oxide, quartz or stainless steel. The particle size distribution of the resulting ground material is controlled by the energy applied to the system and by matching the starting material particle size with the grinding media size. However, dry grinding is an inefficient and energy-consuming process. Wet grinding is similar to dry grinding with the addition of grinding liquid. The advantage of wet grinding is that the energy consumption to produce the same result is 15%-50% lower than that of dry grinding. Another advantage of wet grinding is that the grinding liquid can protect the ground material from oxidation. It has also been found that wet grinding can produce finer particles and cause less particle agglomeration.
[0301] A wide variety of liquid components can be used for wet grinding. In an exemplary embodiment, a grinding liquid or a component contained in the grinding liquid is selected to reduce or eliminate chemical functionalization on the surface of silicon particles during or after grinding. In other embodiments, a grinding liquid or a component contained in the grinding liquid is selected to provide the desired surface chemical functionalization of particles (e.g., silicon particles) during or after grinding. The grinding liquid or a component contained in the grinding liquid can also be selected to control the chemical reactivity or crystalline morphology of particles (e.g., silicon particles). In an exemplary embodiment, the grinding liquid or a component contained in the grinding liquid can be selected based on the compatibility or reactivity with downstream materials, processing steps, or the use of particles (e.g., silicon particles). For example, the grinding liquid or a component contained in the grinding liquid can be compatible with a liquid or solvent in a process for forming or manufacturing an organic or inorganic aerogel material, can be used for the liquid or solvent, or is the same as the liquid or solvent. In yet another embodiment, the grinding liquid can be selected so that the grinding liquid or a component contained in the grinding liquid produces a coating or intermediate substance on the surface of the silicon particles, such as an aliphatic or aromatic hydrocarbon, or by cross-linking or generating a cross-functional compound that reacts with an organic or inorganic aerogel material.
[0302] The solvent or solvent mixture used for grinding can be selected to control the chemical functionalization of the particles during or after grinding. Using silicon as an example, and without being bound by theory, grinding silicon in an alcohol-based solvent (e.g., isopropanol) can functionalize the silicon surface and covalently bond the alkoxide surface groups (e.g., isopropanol) to the silicon particle surface. In an exemplary embodiment, grinding can be carried out in a polar aprotic solvent (e.g., DMSO, DMF, NMP, DMAC, THF, 1,4-dioxane, diglyme, acetonitrile, water, or any combination thereof), which has many advantages. For example, grinding in a solvent (e.g., the above-mentioned polar aprotic solvent) compatible with the process for making aerogel materials can eliminate the need to remove the grinding liquid from the particles before adding to the aerogel manufacturing process, because the grinding liquid is the same or compatible with the solvent used in the aerogel process. In other embodiments, the grinding liquid can include a monomer, an oligomer, or a polymer precursor. For example, the grinding liquid can include a polyimide precursor monomer, such as polyacrylic acid (PAA). For another example, the grinding liquid can include a sol-gel liquid. In these embodiments, the grinding liquid including the precursor component or the sol-gel liquid can impart sol-gel functionality to the surface of the particles (e.g., silicon particles). In other embodiments, the grinding liquid can be selected to impart surface functionality to the particles (e.g., silicon particles) so that the functionalized particles react or interact with each other during or after the grinding process.
[0303] The silicon particles of the present disclosure may be silicon wires, crystalline silicon, amorphous silicon, silicon alloys, coated silicon (e.g., carbon-coated silicon), and any combination of silicon particle materials disclosed herein. In some embodiments, the silicon particles may be substantially planar flakes, i.e., having a flat fragment shape, which may also be referred to as a flake shape. For example, the particles have two substantially flat main surfaces connected by a secondary surface that defines the thickness between the main surfaces. In other embodiments, the particles of silicon or other electroactive materials may be substantially spherical, cubic, oblong, elliptical, disc-shaped, or annular.
[0304] The amount of silicon (eg, silicon particles) present in the organic solvent solution of the organogel precursor can vary, but is generally selected so that the final porous carbon-silicon composition contains from about 20 weight percent to about 65 weight percent silicon.
[0305] Continue to refer Fig.49A and Fig.49B , after the reaction of forming or dissolving the organogel precursor is completed (for example, forming polyamic acid, or dissolving the preformed polyamic acid in an organic solvent), gelation begins. Typically, the initiation of gelation is carried out before merging the gelled organogel precursor or the mixture of the gelled organogel precursor and silicon with the immiscible medium. Gelation (and its initiation) can be carried out chemically, thermally or by a combination thereof. In some embodiments, the organogel precursor is polyamic acid, and initiation of gelation includes chemical imidization of the polyamic acid to form a corresponding polyimide gel. In some embodiments, carrying out chemical imidization of polyamic acid includes adding a dehydrating agent and an amine base to the polyamic acid sol. The presence of a dehydrating agent and an amine base initiates and drives the imidization of the polyamic acid carboxylic acid and amide groups, thereby forming a polyimide gel.
[0306] The structure of the dehydrating agent can vary, but it is generally a reagent that reacts with the carboxylate groups of polyamic acid and can drive the imidization of polyamic acid carboxyl and amide groups. A suitable example of a suitable dehydrating agent of a class is a carboxylic acid anhydride, such as acetic anhydride, propionic anhydride, etc. In some embodiments, the dehydrating agent is a carboxylic acid anhydride. In some embodiments, the carboxylic acid anhydride is acetic anhydride.
[0307] In some embodiments, the amount of dehydrating agent can be based on the amount of multifunctional anhydride (e.g., tetracarboxylic dianhydride) and change. For example, in some embodiments, dehydrating agent and dianhydride exist with different mol ratios. The mol ratio of dehydrating agent and tetracarboxylic dianhydride can change according to the required reaction time, reagent structure and required material properties. In some embodiments, the mol ratio is from about 2 to about 10, such as from about 2, about 3, about 4 or about 5, to about 6, about 7, about 8, about 9 or about 10. In some embodiments, the ratio is from about 3 to about 6 or from about 4 to about 5. In some embodiments, the ratio is 4.3.
[0308] The term "amine base" in the context of this disclosure refers to a molecule having a single amino group with a lone pair of electrons available to accept a proton. Suitable amine bases include tertiary alkylamines, tertiary cycloalkylamines, heteroaromatic amines, guanidine and quaternary ammonium hydroxides.
[0309] In some embodiments, the amine base is a tertiary alkylamine or a cycloalkylamine. "Tertiary" as used herein in the context of an amine means that the amine nitrogen atom has three organic (i.e., carbon) substituents attached thereto. In some embodiments, the tertiary amine is triethylamine, trimethylamine, tri-n-butylamine, N-methylpyrrolidine, N-methylpiperidine, or diisopropylethylamine.
[0310] In some embodiments, the amine base is a heteroaromatic amine. As used herein, the term "heteroaromatic amine" refers to an aromatic ring system in which one or more ring atoms are nitrogen. Heteroaromatic amines typically contain 2 to 20 carbon atoms and 1 to 3 heteroatoms selected from N, O, P and S, wherein at least one heteroatom is nitrogen. Heteroaromatic amines can be monocyclic rings with 3 to 7 ring members (selecting 2 to 6 carbon atoms and 1 to 3 heteroatoms) or bicyclic rings with 7 to 10 ring members (4 to 9 carbon atoms and 1 to 3 heteroatoms), such as bicyclic [4,5], [5,5], [5,6] or [6,6] systems. Heteroaromatic amines may be unsubstituted or substituted. Particularly suitable are heteroaromatic amines with a monocyclic structure comprising 5 carbon atoms and one nitrogen atom, such as pyridine. In some embodiments, the amine base is pyridine. In some embodiments, the amine base is pyridine with one or more alkyl substituents at appropriate positions of the aromatic ring. For example, suitable pyridines include those substituted with one or more methyl, tert-butyl or combinations thereof. Non-limiting examples include 2-methylpyridine, 3-methylpyridine and 4-methylpyridine, 2,6-lutidine, 2,6-di-tert-butylpyridine, etc. In some embodiments, the amine base is pyridine.
[0311] The amount of the amine base added can vary. The amount of the amine base added can be based on a molar ratio, for example, relative to a molar ratio of polyamic acid. The molar ratio of the amine base to the polyamic acid can vary according to the desired reaction time, reagent structure, and desired material properties. In some embodiments, the molar ratio is about 0.1 to about 8. In some embodiments, the molar ratio is about 0.1, about 0.2, about 0.3, about 0.43, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, or about 1 to about 2, about 3, about 4, about 5, about 6, about 7, or about 8.
[0312] Continue to refer Fig.49A and Fig.49B The process of forming the organogel beads includes combining an organogel precursor solution (eg, a polyamic acid solution) in which gelation has begun with a medium (eg, a dispersion medium) that is immiscible with the solution.
[0313] The dispersion medium may have a range of viscosities. In some embodiments, the medium has a viscosity of about 100 centipoise (cP) to about 150 centipoise. In some embodiments, the organic solvent solution of the organogel precursor (i.e., the organogel sol) has a viscosity in the range of about 5cP to about 30cP. In some embodiments, the medium has a viscosity of about 100cP to about 150cP, and the organic solvent solution of the organogel precursor (i.e., the organogel sol) has a viscosity in the range of about 5cP to about 30cP. Surprisingly, according to the present disclosure, it has been found that in some embodiments, merging a low viscosity organogel solution with a higher viscosity dispersion medium will produce droplets (i.e., beads) of small diameter, which may be desired in certain embodiments. Without wishing to be bound by any particular theory, it is believed that in some embodiments, the viscosity difference between the medium and the organogel sol can drive the reduction of the droplet size. Therefore, in some embodiments, the ratio of the viscosity of the medium to the viscosity of the organogel sol is between about 3 to about 50, or about 3 to about 30, for example, about 5 to about 20. In some embodiments, the ratio is about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10 to about 15, about 20, about 25, or about 30. In some embodiments, the ratio is about 3, about 4, about 5, about 6, about 7, about 8, about 9, about 10, about 11, about 12, about 13, about 14, about 15, about 16, about 17, about 18, about 19, about 20, about 21, about 22, about 23, about 24, about 25, about 26, about 27, about 28, about 29, or about 30.
[0314] In some embodiments, the medium is mineral oil, silicone oil or C5-C12 hydrocarbon. In some embodiments, the medium is aliphatic hydrocarbon, aromatic hydrocarbon or chlorinated hydrocarbon. In some embodiments, the medium is hexane or mineral spirits.
[0315] The gelling solution (i.e., the organogel sol) can be added by, for example, pouring, or can be combined with the immiscible dispersion medium by other means. In some embodiments, the immiscible dispersion medium and optionally a surfactant are added to the sol. In some embodiments, the sol is added to the immiscible dispersion medium and optionally a surfactant.
[0316] Before or during the process of converting the gel-forming components into the gel material, agitation (e.g., by mixing) of the combined dispersion medium and gelling solution can be used to promote droplet (e.g., bead) formation. For example, the combination of the dispersion medium and the gelling organogel sol can form an emulsion in which the organogel sol serves as the dispersed phase. Exemplary methods of gel bead generation can be found in U.S. Patent Application Publication No. 2006 / 0084707 to Ou et al., which is incorporated herein by reference in its entirety.
[0317] Exemplary embodiments of mixing to provide gel beads from the sol mixture in the dispersion medium include magnetic stirring (up to about 600rpm), mechanical mixing (up to about 800rpm) and homogenization (up to about 9000rpm). Mixing can be high shear or low shear. In some embodiments, mixing is high shear (e.g., speed is about 4000rpm to about 9000rpm). Spherical droplets of the organogel precursor are formed in the dispersion medium by means of interfacial tension. The droplets are gelled and enhanced in the dispersion medium at this time. The agitation of the mixture is generally used to prevent the droplets from agglomerating. For example, the combination of the organogel sol and the dispersion medium can be stirred for a period of time to prevent the droplets from agglomerating.
[0318] In some embodiments, the medium also includes one or more surfactants. As used herein, the term "surfactant" refers to a substance that helps emulsion formation and stability by promoting the dispersion of hydrophobic components and hydrophilic components (e.g., oil and water). When present, the surfactant can vary. Suitable surfactants are generally nonionic and include, but are not limited to, polyethylene glycol esters of fatty acids, propylene glycol esters of fatty acids, polysorbate esters, polyglycerol esters of fatty acids, sorbitan esters of fatty acids, and the like. Suitable surfactants have an HLB number ranging from about 0 to about 20. In some embodiments, the HLB number is about 3.5 to about 6. As understood by those skilled in the art, HLB is the hydrophilic-lipophilic balance of an emulsifier or surfactant, a measure of its hydrophilic or lipophilic degree. The HLB value can be determined by calculating the values for different regions of the molecule as described by Griffin in Griffin, William C. (1949), "Classification of Surface-Active Agents by 'HLB'" (PDF), Journal of the Society of Cosmetic Chemists, 1(5): 311–26, and Griffin, William C. (1954), "Calculation of HLB Values of Non-Ionic Surfactants" (PDF), Journal of the Society of Cosmetic Chemists, 5(4): 249–56, and by Davies in Davies JT (1957), "A quantitative kinetic theory of emulsion type, I. Physical chemistry of the emulsifying agent" (PDF), Gas / Liquid and Liquid / Liquid Interface, Proceedings of the International Congress of Surface Activity, pp. 426–38. The HLB value can be determined according to the industry standard textbook (i.e., "The HLB SYSTEM, a time-saving guide to emulsifier selection" ICI Americas Inc., published in 1976 and revised in March 1980).
[0319] Examples of suitable surfactants generally include, but are not limited to, polyoxyethylene-sorbitan-fatty acid esters; such as mono- and tri-lauryl esters, palmityl esters, stearyl esters, and oleyl esters; such as those known as polysorbates and available under the trade name Products of the type available commercially; polyoxyethylene fatty acid esters, such as those known and available under the trade name Polyoxyethylene stearates of commercially available types; polyoxyethylene ethers, such as those available under the trade name Those polyoxyethylene ethers obtained; polyoxyethylene castor oil derivatives, such as those known and can be Products of the type available commercially; sorbitan fatty acid esters, such as are known and may be referred to as (e.g. Span 80); polyoxyethylene-polyoxypropylene copolymers, such as those known and available or commercially available products; triacetin; and monoglycerides and acetylated monoglycerides, such as glycerol monodicocoate, 928), monocaprylic acid glyceryl ( 308) and monoacetylated and diacetylated monoglycerides. In some embodiments, one or more surfactants include those sold under the trade name Commercially available polymeric polyester-polyol surfactants of the type known as HYDROGEN(R) (Croda Industrial Chemicals; Edison, NJ, USA).
[0320] In some embodiments, the one or more surfactants include Tween 20, Tween 80, Span 20, Span 40, Span 60, Span 80, or a combination thereof. In some embodiments, the surfactant is Span 20, Tween 80, or a mixture thereof. In some embodiments, the one or more surfactants are B246SF. In some embodiments, the one or more surfactants are A70.
[0321] The concentration of the surfactant can vary. In some embodiments, the surfactant or mixture of surfactants is present in the medium in an amount of about 1 wt % to about 5 wt % (e.g., about 1 wt %, about 2 wt %, about 3 wt %, about 4 wt % or about 5 wt %).
[0322] In some embodiments, a low viscosity solvent is added. In some embodiments, the low viscosity solvent is C1 to C3 alcohol. In some embodiments, the low viscosity solvent is ethanol. When in use, after gelation, a low viscosity solvent (such as ethanol) is added to the mixture of droplets and dispersion medium. In some embodiments, adding produces smaller beads and reduces the agglomeration of large bead clusters. The amount and addition method of the low viscosity solvent added can vary. In some embodiments, the low viscosity solvent is added in a single portion in an amount of up to about 10% by volume of the medium. In some embodiments, the low viscosity solvent is added in two or more portions, including the first portion of an amount of up to about 10% by volume of the medium, and another portion or portions, wherein the total amount of the low viscosity solvent added is up to about 50% by volume of the medium. In some embodiments, the low viscosity solvent is added in a continuous manner, wherein the total amount of the low viscosity solvent added is up to about 50% by volume of the medium.
[0323] The process further includes removing the organogel beads from the dispersion medium (e.g., silicone oil). The organogel beads are filtered from the dispersion medium and then washed or rinsed with a fluid (e.g., a hydrocarbon solvent, such as heptane, and / or an alcohol, such as ethanol, methanol, isopropanol, or a higher alcohol). The basic requirements for the rinse fluid are that it removes the dispersion medium (e.g., oil or silicone oil) while not chemically reacting with the organogel and being sufficiently volatile so as to be subsequently easily removed from the organogel beads.
[0324] Prior to liquid phase extraction, the process of converting the gel-forming components into an organogel material may also include an aging step (also referred to as curing). Aging the organogel material after it reaches its gel point can further strengthen the gel framework by increasing the number of crosslinks in the network. The duration of gel aging can be adjusted to control various properties within the resulting aerogel material. This aging procedure can be used to prevent potential volume loss and shrinkage during liquid phase extraction. Aging can include: keeping the gel (before extraction) in a static state for a long time; keeping the gel at an elevated temperature; adding a crosslinking promoting compound; or any combination thereof. The preferred temperature for aging is generally between about 10°C and about 200°C. Aging of the gel material generally continues until liquid phase extraction of the wet gel material. In some embodiments, the organogel beads are aged in ethanol.
[0325] The time period for converting the gel-forming material into a gel material includes the duration of the initial gel formation (from the start of gelation to the gel point), and the duration of any subsequent solidification and aging of the gel material prior to liquid phase extraction (from the gel point to the start of liquid phase extraction). The total time period for converting the gel-forming material into a gel material is generally between about 1 minute and several days, preferably about 30 hours or less, about 24 hours or less, about 15 hours or less, about 10 hours or less, about 6 hours or less, about 4 hours or less, about 2 hours or less, about 1 hour or less, about 30 minutes or less, or about 15 minutes or less.
[0326] The resulting organogel material can be washed in a suitable secondary solvent to replace the primary reaction solvent present in the wet gel. Such secondary solvents can be linear monohydric alcohols having one or more aliphatic carbon atoms, dihydric alcohols having two or more carbon atoms, branched alcohols, cyclic alcohols, alicyclic alcohols, aromatic alcohols, polyols, ethers, ketones, cyclic ethers, or derivatives thereof.
[0327] After the organogel beads are removed from the dispersion medium, the gel beads can undergo an aging and rinsing process. In an exemplary embodiment, the first step includes rinsing the organogel beads with a solvent (e.g., ethanol, or a hydrocarbon solvent such as hexane or octane) under low vacuum filtration. The second step can include aging the organogel beads in a solvent (e.g., ethanol) for about 24 hours to 48 hours at a temperature in the range of about 50° C. to 70° C. The aging fluid bath can be changed during the aging period to remove unreacted compounds and replace the sol-gel solvent (e.g., DMAC) with an aging solvent (e.g., ethanol), referred to herein as a solvent exchange.
[0328] After the aging step, the organogel beads are generally clustered into wet gel agglomerates. In an exemplary embodiment, these agglomerates are dispersed in a solvent (e.g., ethanol) by ultrasonic treatment. For example, a probe sonicator can be used to disperse the agglomerated beads. In certain embodiments, after ultrasonic treatment, a decantation step can be used to remove fine non-settled beads from the top of the bead suspension. The remaining bead suspension can then be diluted with more ethanol and ultrasonicated again. The ultrasonic, decantation and dilution steps can be repeated until most of the organogel beads are dispersed. The dispersed beads can then be filtered to obtain a wet cake of organogel beads. The wet cake of organogel beads is then dried according to the embodiments disclosed herein.
[0329] The size of the wet gel beads can vary. In some embodiments, the wet gel beads have a diameter ranging from about 5 microns to about 500 microns, such as a diameter ranging from about 5 microns, about 10 microns, about 20 microns, about 30 microns, about 40 microns, or about 50 microns to about 60 microns, about 70 microns, about 80 microns, about 90 microns, about 100 microns, about 200 microns, about 300 microns, about 400 microns, or about 500 microns.
[0330] Although the methods for forming organogel beads and organogel-silica composite beads disclosed above have been described with specific reference to the imidization of polyamic acid organogel precursor materials with a dehydrating agent, other suitable methods for producing polyimide organogels and corresponding aerogels are also contemplated herein, such as those described in the following documents: U.S. Patent No. 6,399,669 to Suzuki et al.; U.S. Patent No. 9,745,198 to Leventis et al.; Leventis et al., Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP), Chem. Mater. 2011, 23, 8, 2250-2261; Leventis et al., Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides, MRS Proceedings,1306(2011),Mrsf10-1306-bb03-01.doi:10.1557 / opl.2011.90;Chidambareswarapattar et al., One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides andisocyanates and conversion to isomorphic carbons, J.Mater.Chem., 2010, 20, 9666–9678; Guo et al., Polyimide Aerogels Cross-Linked through Amine Functionalized Polyoligomeric Silsesquioxane, ACS Appl.Mater.Interfaces 2011, 3, 546–552; Nguyen et al., Development of High Temperature, Flexible Polyimide Aerogels, American Chemical Society, proceedings published 2011; Meador et al., Mechanically Strong, Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine,ACSAppl.Mater.Interfaces, 2012, 4(2), pp. 536–544; Meador et al., Polyimide Aerogels with Amide Cross-Links: A Low Cost Alternative for Mechanically Strong Polymer Aerogels, ACS Appl. Mater. Interfaces 2015, 7, 1240-1249; Pei et al., Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups, Langmuir 2014, 30, 13375-13383.
[0331] In addition, although the method disclosed above has been described with specific reference to polyamic acid as an organogel precursor material and the corresponding polyimide as an organogel, those skilled in the art will recognize that other suitable organogel precursor materials can be used in the present method. Therefore, gelation can be carried out under conditions suitable for any single organogel precursor. Examples of suitable organogels include, but are not limited to, resorcinol-formaldehyde (RF), phenol-formaldehyde (PF), polyamides, polyacrylates, polymethyl methacrylate, acrylate oligomers, polyoxyalkylenes, polyurethanes, polyphenols, polybutadiene, trialkoxysilyl-terminated polydimethylsiloxanes, polystyrenes, polyacrylonitrile, polyfurfural, melamine-formaldehyde, cresol formaldehyde, phenol-furfural, polyethers, polyols, polyisocyanates, polyhydroxybenzenes, polyvinyl alcohol dialdehydes, polycyanurates, polyacrylamides, various epoxy resins, agar, agarose, chitosan, and combinations and derivatives thereof. Any precursor of these materials can be used to produce and use the resulting material. For example, the organogel material can be formed by a synthetic polymer or a biopolymer precursor material. Synthetic polymers that can be used to produce organogels include phenolic resins, polymers formed by isocyanates or amines (e.g., polyimide compositions disclosed herein), polyolefins, and conductive polymers. Phenolic resins suitable for producing organogels include phenol-formaldehyde (PF), resorcinol-formaldehyde (RF), polyurea-crosslinked RF, phloroglucinol-formaldehyde (FPOL), cresol-formaldehyde, phenol-furfural, resorcinol-furfural, phloroglucinol-furfural (PF), phloroglucinol-terephthalaldehyde (TPOL), polybenzoxazine (PBO), and melamine-formaldehyde (MF). Isocyanates and amines suitable for producing organogels can include polyurethanes (PU), polyureas (PUA), polyimides (PI), and polyamides (PA). Polyolefins suitable for producing organogels include polydicyclopentadiene (PDCPD) and polyacrylonitrile (PAN). Conductive polymers suitable for producing organogels include polypyrrole (PPY). Benzimidazole can also be used to produce organogels. Biopolymers (such as polysaccharides and proteins) can also be used to produce organogels. For example, suitable polysaccharides that can be used to produce organogels include cellulose, chitin, chitosan, starch, pectin, and alginate.
[0332] A non-limiting list of suitable organogel precursors, gelling catalysts, and corresponding aerogel material types is provided in Table 2 below.
[0333] Table 2. Alternative organogel precursors
[0334] Precursor Gelling catalyst Type of organogel Resorcinol and formaldehyde Acid or base RF Phloroglucinol, furfural Acid or base PF Cellulose and isocyanate Amine base Modified cellulose Diisocyanates and polyamines Polyurea Diisocyanates and polyols Amine base or Lewis acid Polyurethane Sodium alginate Metal ions Cross-linked alginate Acrylonitrile - Polyacrylonitrile (PAN)
[0335] In some embodiments, the porous carbon or porous carbon-silicon composition in the form of beads is obtained from the pyrolysis of organogel beads (eg, xerogel or aerogel) comprising RF, PF, cellulose, polyurea, polyurethane, alginate, or polyacrylonitrile.
[0336] Method for forming aerogels and xerogels from organogels
[0337] In some embodiments, the porous carbon or porous carbon-silicon composition in the form of beads comprises a carbon aerogel. In some embodiments, the porous carbon or porous carbon-silicon composition in the form of beads comprises a carbon xerogel. In other words, in some embodiments, the initial porous organogel or organogel-silicon composite (e.g., polyimide or polyimide-silicon) material as described herein is converted into a corresponding aerogel or xerogel, and then pyrolyzed to provide a corresponding carbon or carbon-silicon composite in the form of an aerogel or xerogel bead composite.
[0338] Once an organogel material (e.g., an organogel or an organogel-silicon composite, such as polyimide or polyimide-silicon composite beads) has been formed and processed, an extraction method (including processing and extraction techniques) can then be used to at least partially extract the liquid phase of the organogel from the wet gel to form a porous or highly porous material, such as a xerogel or aerogel beads. Liquid phase extraction plays an important role in the characteristics of engineered aerogels, such as porosity and density, and related properties, such as thermal conductivity, among other factors.
[0339] In some embodiments, the method further includes converting the organic gel (e.g., polyimide or polyimide-silicon composite beads) obtained as described above into an organic aerogel or xerogel. Typically, when extracting the liquid phase from the gel in a manner that causes a porous network and low shrinkage of the framework of the wet gel, an aerogel is obtained. Aerogels (e.g., polyimide aerogels) are typically formed by removing the liquid mobile phase from a wet organic gel material at a temperature and pressure close to or above the critical point of the liquid mobile phase. Once a critical point (close to critical) or a critical point (supercritical) is reached (i.e., the pressure and temperature of the system are equal to or higher than the critical pressure and critical temperature, respectively), a new supercritical phase different from a liquid phase or a gas phase appears in the fluid. The solvent can then be removed without introducing a liquid-gas interface, capillary pressure, or any related mass transfer restrictions typically associated with a liquid-gas boundary. In addition, supercritical phases are typically more miscible with organic solvents and therefore have better extraction capabilities. Cosolvents and solvent exchange are also commonly used to optimize supercritical fluid drying processes.
[0340] If evaporation or extraction occurs below the supercritical point, the capillary forces generated by the evaporation of the liquid can cause shrinkage and pore collapse within the gel material. During solvent extraction, maintaining the mobile phase near or above the critical pressure and temperature reduces the negative effects of such capillary forces. In certain embodiments of the present disclosure, the use of near-critical conditions just below the critical point of the solvent system can allow the production of aerogel materials or compositions with sufficiently low shrinkage to produce a commercially viable final product.
[0341] As discussed herein, various techniques can be used to dry the wet gel beads to provide aerogel beads. In exemplary embodiments, the organogel beads can be dried under ambient pressure, subcritical conditions, or supercritical conditions.
[0342] Both room temperature and high temperature processes can be used to dry the beads at ambient pressure. In some embodiments, a slow ambient pressure drying process can be used, wherein the wet gel beads are spread into a thin layer and exposed to air in an open container for a period of time sufficient to remove the solvent from the beads, such as a period of time in the range of 24 hours to 36 hours. The thickness of the bead layer can be in the range of about 5 mm to about 15 mm. The beads can optionally be manually stirred or fluffed during the drying process to prevent the beads from fusing together during the drying process.
[0343] Fluidized bed methods can also be used for ambient temperature drying of gels. In an exemplary embodiment, a sintering funnel is fixed to the top of a filter flask, the wet cake or gel slurry is placed on the glaze, the top of the funnel is covered with a paper towel, and compressed air is connected to the filter flask inlet and allowed to enter through the pores of the glaze. The beads are maintained in a fluidized bed until the solvent is removed. The dry powder material can then be collected from the funnel.
[0344] In another embodiment, the organogel beads are dried by heating. For example, the gel beads can be heated in a convection oven. For another example, the gel beads can be spread out in layers and placed on a hot plate. The temperature of the hot plate can be 50°C to about 100°C, and the beads can be heated for a period of time in the range of about 2 minutes to about 5 minutes to evaporate most of the ethanol. After partial drying, the beads can be placed at ambient temperature for a period of time in the range of about 6 hours to about 12 hours to completely dry, or can be heated at a temperature of 50°C to about 100°C. Without being bound by theory, volatile solvents can act as fluidizers or separators, because the solvent quickly leaves the gel bead material, which causes the particles to agglomerate less.
[0345] Organic gel beads (e.g., polyimide or polyimide-silica composite gel beads) dried under ambient conditions can be referred to as xerogel beads. An exemplary polyimide xerogel with a target density of about 0.05 g / cc has a density between about 0.00 m / s. 2 / g to about 1.5m 2 / g, for example, between about 0.10m 2 / g to about 1.10m 2 / g, about 0.10m 2 / g to about 1.00m 2 / g, about 0.10m 2 / g to about 0.50m 2 / g, or about 0.10m 2 / g to about 0.20m 2 / g range of surface area.
[0346] Both supercritical and subcritical drying can be used to dry the beads. In an exemplary embodiment of supercritical drying, the beads are filtered, collected and fixed in a porous container having pores less than the size of the dried beads, such as 5 micron pores. The container with the beads can then be placed in a high pressure container to extract the solvent with supercritical CO2. After removing the solvent (e.g., ethanol), the container can be kept above the CO2 critical point for a period of time, such as about 30 minutes. After supercritical drying, the container is decompressed to atmospheric pressure.
[0347] In an exemplary embodiment of subcritical drying, the gel beads are dried at room temperature using liquid CO2 at a pressure in the range of about 800 psi to about 1200 psi. This operation is faster than supercritical drying, for example, ethanol can be extracted in about 15 minutes. In the context of the present disclosure, beads dried using subcritical drying are referred to as aerogel-like.
[0348] Several additional aerogel extraction techniques are known in the art, including a range of different methods for using supercritical fluids in drying aerogels, as well as ambient drying techniques. For example, Kistler (J. Phys. Chem. (1932) 36: 52-64) describes a simple supercritical extraction process in which the gel solvent is maintained above its critical pressure and temperature, thereby reducing evaporative capillary forces and maintaining the structural integrity of the gel network. U.S. Patent No. 4,610,863 describes an extraction process in which the gel solvent is exchanged with liquid carbon dioxide and then extracted under conditions in which the carbon dioxide is in a supercritical state. U.S. Patent No. 6,670,402 teaches the production of aerogels by extracting the liquid phase from the gel by rapid solvent exchange by injecting supercritical (but not liquid) carbon dioxide into an extractor that has been preheated and prepressurized to substantially supercritical conditions or above. U.S. Patent No. 5,962,539 describes a process for obtaining aerogels from polymer materials in sol-gel form in an organic solvent by exchanging the organic solvent for a fluid having a critical temperature below the decomposition temperature of the polymer and supercritically extracting the fluid / sol-gel. U.S. Patent No. 6,315,971 discloses a process for producing a gel composition comprising: drying a wet gel comprising gel solids and a desiccant to remove the desiccant under drying conditions sufficient to reduce shrinkage of the gel during drying. U.S. Patent No. 5,420,168 describes a process for making resorcinol / formaldehyde aerogels using a simple air drying procedure. U.S. Patent No. 5,565,142 describes a drying technique in which the surface of the gel is modified to be stronger and more hydrophobic so that the gel framework and pores can resist collapse during ambient drying or subcritical extraction. Other examples of extracting a liquid phase from a gel material can be found in U.S. Patent No. 5,275,796 and U.S. Patent No. 5,395,805.
[0349] A preferred embodiment of extracting the liquid phase from the wet gel uses supercritical conditions of carbon dioxide, including, for example: first fully exchanging the main solvent present in the gel pore network with liquid carbon dioxide; and then heating the wet gel (usually in an autoclave) above the critical temperature of carbon dioxide (about 31.06°C) and increasing the system pressure to a pressure greater than the critical pressure of carbon dioxide (about 1070psig). The pressure around the gel material can fluctuate slightly to facilitate the removal of the supercritical carbon dioxide fluid from the gel. The carbon dioxide can be recycled through the extraction system to facilitate the continuous removal of the main solvent from the wet gel. Finally, the temperature and pressure are slowly returned to ambient conditions to produce a dry aerogel material. The carbon dioxide can also be pretreated to a supercritical state before being injected into the extraction chamber. In other embodiments, the extraction can be performed using any suitable mechanism, such as changing the pressure, time and solvent discussed above.
[0350] In certain embodiments of the present disclosure, the dried polyimide aerogel composition may be subjected to one or more heat treatments for a duration of 3 hours or more, between 10 seconds and 3 hours, between 10 seconds and 2 hours, between 10 seconds and 1 hour, between 10 seconds and 45 minutes, between 10 seconds and 30 minutes, between 10 seconds and 15 minutes, between 10 seconds and 5 minutes, between 10 seconds and 1 minute, between 1 minute and 3 hours, between 1 minute and 1 hour, between 1 minute and 45 minutes, between 1 minute and 30 minutes, between 1 minute and 15 minutes, Between 1 minute and 5 minutes, between 10 minutes and 3 hours, between 10 minutes and 1 hour, between 10 minutes and 45 minutes, between 10 minutes and 30 minutes, between 10 minutes and 15 minutes, between 30 minutes and 3 hours, between 30 minutes and 1 hour, between 30 minutes and 45 minutes, between 45 minutes and 3 hours, between 45 minutes and 90 minutes, between 45 minutes and 60 minutes, between 1 hour and 3 hours, between 1 hour and 2 hours, between 1 hour and 90 minutes, or in a range between any two of these values.
[0351] Methods for forming porous carbon and carbon-silicon composites from organic gels
[0352] Porous carbon compositions and porous carbon-silicon compositions are provided herein, and the compositions may also be referred to as nanoporous carbon and silicon-doped nanoporous carbon materials, respectively. Such compositions may be in the form of xerogels or aerogel beads. Organic gel beads (e.g., polyimide gel beads as disclosed herein) may be converted into carbon materials. In some embodiments, dry xerogels or aerogels (e.g., polyimide xerogels or aerogels) as disclosed herein are pyrolyzed (i.e., carbonized), which means that the xerogels or aerogels are heated at a temperature and time sufficient to convert substantially all organic materials into carbon. Required time and temperature may vary. In some embodiments, the dried organic aerogel or xerogel is subjected to a treatment temperature of 400° C. or more, 600° C. or more, 800° C. or more, 1000° C. or more, 1200° C. or more, 1400° C. or more, 1600° C. or more, 1800° C. or more, 2000° C. or more, 2200° C. or more, 2400° C. or more, 2600° C. or more, 2800° C. or more, or a range between any two of these values, for carbonizing the aerogel or xerogel. Without being bound by theory, it is contemplated herein that the conductivity of the aerogel composition increases with the carbonization temperature.
[0353] Carbon xerogels and aerogels according to exemplary embodiments of the present disclosure (e.g., polyimide-derived carbon aerogels) may have a residual nitrogen content. For example, carbon aerogels according to embodiments disclosed herein may have a residual nitrogen content of at least about 0.1 wt%, at least about 0.5 wt%, at least about 1 wt%, at least about 2 wt%, at least about 3 wt%, at least about 4 wt%, at least about 5 wt%, at least about 6 wt%, at least about 7 wt%, at least about 8 wt%, at least about 9 wt%, at least about 10 wt%, or a range between any two of these values.
[0354] Alternative methods for forming porous carbon-silicon composites
[0355] As disclosed above, in some embodiments, silicon (e.g., silicon particles) is introduced into the carbon-silicon composite material before or during the gelation of the corresponding organogel precursor (e.g., polyamic acid). Alternatively, silicon can be generated, infiltrated, deposited, or otherwise formed within an organogel or carbon material (e.g., an organogel or an organogel-derived carbon xerogel or aerogel) as described herein.
[0356] In an exemplary alternative embodiment, silicon is produced within the pores of the carbon material (or its precursor material, such as an organogel material) by subjecting the material to high temperature in the presence of a silicon-containing gas, preferably silane (SiH4), to achieve silicon deposition / infiltration by processes such as chemical vapor deposition (CVD) or chemical vapor infiltration (CVI). In some embodiments, silicon can be co-deposited or co-infiltrated with other electroactive materials simultaneously or alternatively in sequence. For example, silicon and tin can be deposited or infiltrated into the material simultaneously or alternatively in sequence. For another example, silicon and germanium or a silicon and germanium alloy can be deposited or infiltrated into the material simultaneously or alternatively in sequence.
[0357] Silane gas may be mixed with other inert gases, such as nitrogen. The temperature and time of the treatment may vary, for example, the temperature may be between 300°C and 400°C, such as between 400°C and 500°C, such as between 500°C and 600°C, such as between 600°C and 700°C, such as between 700°C and 800°C, such as between 800°C and 900°C. The gas mixture may contain between 0.1% and 1% silane and the remainder inert gas. Alternatively, the gas mixture may contain between 1% and 10% silane and the remainder inert gas. Alternatively, the gas mixture may contain between 10% and 20% silane and the remainder inert gas. Alternatively, the gas mixture may contain between 20% and 50% silane and the remainder inert gas. Alternatively, the gas mixture may contain more than 50% silane and the remainder inert gas. Alternatively, the gas can be substantially 100% silane gas. The reactor in which the CVD process is performed is according to various designs as known in the art, such as a fluidized bed reactor, a fixed bed reactor, an elevator kiln, a rotary kiln, a box kiln or other suitable reactor types. As known in the art, the reactor material is suitable for the task. In a preferred embodiment, the carbon material is treated under conditions that provide uniform entry into the gas phase, such as a reactor in which particles of the carbon material are fluidized or otherwise stirred to provide said uniform gas entry.
[0358] In some embodiments, the CVD process is a plasma enhanced chemical vapor deposition (PECVD) process. This process is known in the art and is used to deposit thin films from a gaseous state (vapor) to a solid state on a substrate. A chemical reaction is involved in the process, which occurs after a plasma is generated by a reactive gas. Plasma is typically generated by a radio frequency (RF; i.e., AC) or DC discharge between two electrodes, the space between which is filled with a reactive gas. In certain embodiments, the PECVD process is used for porous carbon, which is coated on a substrate suitable for the purpose (e.g., a copper foil substrate). PECVD can be performed at various temperatures, such as between 300°C and 800°C, such as between 300°C and 600°C, such as between 300°C and 500°C, such as between 300°C and 400°C, such as at 350°C. As known in the art, the power can vary, such as 25W RF, and the silane gas flow required for the treatment can vary, and the treatment time can vary.
[0359] CVD / CVI is typically achieved by subjecting the carbon material or its precursor to an elevated temperature for a period of time in the presence of a suitable deposition gas containing carbon atoms. Suitable gases in this context include, but are not limited to, methane, propane, butane, cyclohexane, ethane, propylene, and acetylene. The temperature may vary, for example, between 350°C. and 1050°C., for example, between 350°C. and 450°C., for example, between 450°C. and 550°C., for example, between 550°C. and 650°C., for example, between 650°C. and 750°C., for example, between 750°C. and 850°C., for example, between 850°C. and 950°C., for example, between 950°C. and 1050°C. The deposition time may vary, for example, between 0 min and 5 min, for example, between 5 min and 15 min, for example, between 15 min and 30 min, for example, between 30 min and 60 min, for example, between 60 min and 120 min, for example, between 120 min and 240 min. In some embodiments, the deposition time is greater than 240 min. In certain embodiments, the deposition gas is methane, and the deposition temperature is greater than or equal to 950° C. In certain embodiments, the deposition gas is propane, and the deposition temperature is less than or equal to 750° C. In certain embodiments, the deposition gas is cyclohexane, and the deposition temperature is greater than or equal to 800° C.
[0360] In certain embodiments, the reactor itself can be stirred to stir the carbon material particles to be impregnated with silicon. For example, the impregnation process can be carried out in a static mode, in which the particles are not stirred, and the silicon-containing reactant flows on, around, or otherwise contacts the particles to be coated. In other exemplary modes, the particles can be fluidized, for example, they can be impregnated with silicon-containing reactants in a fluidized bed reactor. As is known in the art, a variety of different reactor designs can be used in this case, including (but not limited to) lift kilns, roller bottom kilns, rotary kilns, box kilns, and improved fluidized bed designs. Any additional or waste silicon (i.e., silicon that is not deposited in the carbon material) produced from the process disclosed herein can be separated and reused as input material.
[0361] Properties of porous carbon and carbon-silicon composites
[0362] As discussed above, the porous carbon and carbon-silicon compositions (e.g., silicon-doped nanoporous carbon materials) of the present disclosure can be in the form of xerogel or aerogel beads. As described above, the properties of the porous granular carbon-silicon compositions can vary depending on the specific combination of variables used in their production.
[0363] The diameter of the particle (i.e., bead) can vary. For example, in some embodiments, the bead of porous carbon or carbon-silicon composition has a diameter in the range of about 1 micron to about 50 microns, such as about 1 micron, about 2 microns, about 3 microns, about 4 microns, about 5 microns, about 6 microns, about 7 microns, about 8 microns, about 9 microns, about 10 microns, about 15 microns, about 20 microns, about 25 microns, about 30 microns, about 35 microns, about 40 microns, about 45 microns, about 50 microns, or between any two of these values. In certain embodiments, the bead has a diameter in the range of about 1 to about 15 μm. In some embodiments, the bead has a particle size D10 in the range of about 5 to about 15 μm or about 5 to about 10 μm. In some embodiments, the bead has a particle size D50 in the range of about 5 to about 25 μm or about 10 to about 15 μm. In some embodiments, the beads have a particle size D90 ranging from about 15 to about 35 μm, or from about 10 to about 20 μm.
[0364] The density of the beads can vary. In some embodiments, the beads have a density between about 0.2 g / cm 3 To about 1.5g / cm 3 , or from about 0.3 to about 1.3 g / cm 3 The tap density is within the range.
[0365] In some embodiments, the porous carbon-silicon composition includes a pore structure including a fibrous morphology and an array of pores around elemental silicon. In some embodiments, elemental silicon is at least partially present in the pore structure of carbon. In the context of the present disclosure, the term "fibrous morphology" refers to the structural morphology of nanoporous carbon (e.g., aerogel), including pillars, rods, fibers or filaments. For example, in one embodiment, the selection of a solvent (e.g., dimethylacetamide (DMAC)) can affect the generation of this morphology. In addition, in certain embodiments, when the carbon aerogel is derived from polyimide, the crystalline polyimide is produced by the polyimide forming a linear polymer. As will become clearer in the following examples, based on the known behavior of polyimide precursors, it is surprisingly observed that certain embodiments include fibrous morphology as an interconnected polymer structure, wherein a long linear structure is expected. In contrast, the product form of nanoporous carbon (e.g., porous carbon or carbon-silicon composite material) is essentially alternatively granular or powder, wherein the fibrous morphology of the carbon aerogel persists. As will become clearer as this specification proceeds, the fibrous morphology can provide certain benefits over the granular morphology, such as mechanical stability / strength and electrical conductivity, particularly when the nanoporous carbon is used in certain applications, such as as an anode material in a lithium-ion battery (LIB). It should be noted that this fibrous morphology can be found in nanoporous carbon in both bulk form and powder form; in other words, the bulk carbon can have a fibrous morphology, and the aerogel powder / granules / beads can have a fibrous morphology. In addition, in certain embodiments, when the nanoporous carbon material contains an additive (e.g., silicon or other substances), the inherent fibrous nanostructure of the carbon material is retained and acts as a bridge between the additive particles.
[0366] As described above, in some embodiments, the porous carbon composition further comprises silicon. The amount of silicon (e.g., elemental silicon) present in the composition (e.g., carbon-silicon composite aerogel beads) can vary. In some embodiments, the porous carbon-silicon composition contains greater than about 10% by weight of silicon. In some embodiments, the composition comprises about 25% to 65% by weight of silicon relative to the weight of the carbon material. In some embodiments, the composition comprises about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, or about 65% by weight of silicon.
[0367] The particle size of silicon (e.g., elemental silicon) present in the composition can vary. In some embodiments, the silicon has a particle size less than about 150 nm. In some embodiments, the silicon has a particle size within the range of about 150 nm to about 500 nm. In some embodiments, the silicon has a particle size greater than about 500 nm.
[0368] In some embodiments, the porous carbon-silicon composition in the form of beads comprises silicon in a range of about 25 wt % to about 65 wt %, wherein the silicon has a particle size in a range of about 100 nm to about 800 nm; and wherein the porous carbon-silicon composition beads have a particle size in a range of about 0.2 g / cm 3 To about 1.5g / cm 3 tap density in the range of about 1 μm to about 15 μm; bead diameter in the range of about 10 nm to about 50 nm; and average pore size in the range of about 0 to about 500 nm. 2 The BET surface area is in the range of / g.
[0369] Electrode materials and energy storage devices comprising porous carbon or carbon-silicon composites
[0370] In certain embodiments, the present invention relates to the formation and use of nanoporous carbon-based scaffolds or structures, such as carbon or carbon-silicon aerogels, as electrode materials within energy storage devices, for example, as primary anode materials in LIBs. The pores of the nanoporous scaffolds are designed, organized and structured to accommodate particles of silicon or other metalloids or metals, and the expansion of such particles, for example, after lithiation in a LIB. Alternatively, the pores of the nanoporous scaffolds can be filled with sulfides, hydrides, any suitable polymers or other additives, where it is beneficial to contact the additives with the conductive material (i.e., the scaffold / aerogel) to provide a more efficient electrode. A general process for utilizing silicon-doped carbon aerogels in battery applications can be found in Figure 1 .
[0371] To further expand the exemplary applications within LIBs, when carbon aerogel materials are used as primary anode materials such as in certain embodiments of the present invention, the aerogel nanoporous structure has a narrow pore size distribution and provides high conductivity, high mechanical strength, and morphology and sufficient pore volume (at final density) to accommodate the high weight percentage of silicon particles and their expansion. Structurally, certain embodiments of the present invention have a fibrous morphology with certain pillar sizes, which produces the above-mentioned properties of narrow pore size distribution, high pore volume, and enhanced connectivity.
[0372] In additional or alternative embodiments, the carbon aerogel itself acts as a current collector due to its conductivity and mechanical strength, thus, in a preferred embodiment, eliminating the need for a different current collector on the anode side (when the anode is formed from a carbon aerogel). It is worth noting that in conventional LIBs, copper foil is coupled to the anode as its current collector. However, depending on the application of the carbon aerogel, removing one or both of these components provides additional space for more electrode material, thereby obtaining a larger battery / single electrode capacity and an overall greater packaged battery system energy density. However, in certain embodiments, the existing current collector can be integrated with the anode materials of various other embodiments to enhance the current collection capability or capacity of the copper or aluminum foil.
[0373] In certain embodiments, the nanoporous carbon-based scaffold or structure and specifically the carbon aerogel as described herein can be used as a conductive network or collector on the anode side of the energy storage device. The fully interconnected carbon aerogel network is filled with electrochemically active materials, wherein the electrochemically active materials are directly in contact with or physically connected to the carbon network. The loading of the electrochemically active material is adjusted according to the pore volume and porosity to obtain a high and stable capacity, and improved energy storage device safety. When utilized on the anode side, the electrochemically active material may include, for example, silicon, graphite, lithium or other metalloids or metals. In yet another embodiment, the anode may include a nanoporous carbon-based scaffold or structure, and specifically carbon aerogel beads as disclosed herein.
[0374] In the context of the present disclosure, the term "no current collector" refers to the absence of a different current collector directly connected to the electrode. As described, in conventional LIBs, copper foil is typically coupled to the anode as its current collector. The electrode formed from a nanoporous carbon-based scaffold or structure (e.g., carbon or carbon-silicon composite aerogel as described herein) according to an embodiment of the present invention can be a freestanding structure, or conversely has the ability to be without a current collector because the scaffold or structure itself is used as a current collector due to its high conductivity. In an electrochemical cell, the current collector-free electrode can be connected to form a circuit by embedding a solid, mesh, or woven sheet (in the dissolution step of preparing continuous porous carbon); or by brazing, welding, or metal deposition wire to a portion of the porous carbon surface. Other mechanisms for contacting the rest of the carbon system are also contemplated herein. In alternative embodiments, the nanoporous carbon-based scaffold or structure, and specifically the carbon aerogel, can be dispersed on a dedicated current collecting substrate (e.g., copper foil, aluminum foil, etc.) or otherwise connected to a dedicated current collecting substrate (e.g., copper foil, aluminum foil, etc.). In this case, the carbon aerogel can be attached to a solid current collector using a conductive adhesive and applying varying amounts of pressure.
[0375] Furthermore, it is contemplated herein that the nanoporous carbon-based scaffold or structure and specifically the carbon aerogel as described herein can take the form of a monolithic structure. When monolithic in nature, the carbon aerogel eliminates the need for any binder; in other words, the anode can be binder-free. As used herein, the term "monolithic" refers to an aerogel material in which the majority of the aerogel (by weight) included in the aerogel material or composition is in the form of a single, continuous, interconnected aerogel nanostructure. Monolithic aerogel materials include aerogel materials that are initially formed to have a single interconnected gel or aerogel nanostructure but can subsequently be cleaved, broken or fragmented into non-single aerogel nanostructures. Monolithic aerogels can take the form of independent structures or reinforced (fiber or foam) materials. In contrast, taking silicon lithiation as an example, silicon incorporated into a monolithic aerogel can be more efficiently utilized relative to theoretical capacity than the same amount of silicon incorporated into a slurry using conventional processes (see Figure 2 ).
[0376] Monolithic aerogel materials are distinguished from particulate (e.g., bead) aerogel materials. The term "particulate aerogel material" refers to an aerogel material in which the majority (by weight) of the aerogel contained in the aerogel material is in the form of particles, granules, granules, beads, or powders, which can be combined together (i.e., via an adhesive, such as a polymer adhesive) or compressed together but lack interconnected aerogel nanostructures between individual particles. In general, this form of aerogel material will be referred to as having a powder, particulate, or bead form (as opposed to a monolithic form). It should be noted that although individual particles of the powder have a single structure, individual particles are not considered monolithic herein. Aerogel powders are integrated into electrochemical cells, typically a paste or slurry is prepared from the powder, cast and dried onto a substrate, and optionally calendering is included.
[0377] Particulate aerogel materials, such as aerogel beads, provide certain advantages. For example, particulate materials according to embodiments disclosed herein can be used as a direct replacement for other materials such as graphite in LIB anodes and anode manufacturing processes. Particulate materials according to embodiments disclosed herein can also provide increased lithium ion diffusion rates because the diffusion paths within the particulate material are shorter. Particulate materials according to embodiments disclosed herein can also allow electrodes with optimized packing density, such as by adjusting particle size and packing arrangement. Particulate materials according to embodiments disclosed herein can also provide improved access to silicon due to inter-particle and intra-particle porosity.
[0378] In the context of the present disclosure, the term "binder-free" or "binder-free" (or its derivatives) refers to a material that is substantially free of a binder or adhesive to bind the material together. For example, a monolithic nanoporous carbon material has no binder because its framework is formed as a single, continuous, interconnected structure. The advantages of being binder-free include avoiding any effects of the binder, such as on conductivity and pore volume. On the other hand, aerogel particles require a binder to be bound together to form a larger functional material; such larger materials are not considered monolithic in this article. In addition, this "binder-free" term does not exclude all uses of binders. For example, a monolithic aerogel according to the present invention can be fixed to another monolithic aerogel or non-aerogel material by placing an adhesive or adhesive on a major surface of the aerogel material. In this way, an adhesive is used to create a layered composite material, but the adhesive does not have the function of maintaining the stability of the monolithic aerogel framework itself.
[0379] In addition, the monolithic polymer aerogel material or composition of the present disclosure can be compressed to 95% strain without significantly damaging or cracking the aerogel framework, while making the aerogel dense and minimizing the porosity. In certain embodiments, the compressed polymer aerogel material or composition is subsequently carbonized using the various methods described herein to form a nanoporous carbon material. It is understood that the amount of compression affects the thickness of the resulting carbon material, wherein the thickness has an effect on the capacity, which will become clearer as this specification continues. The embodiments described below will illustrate various thicknesses formed and considered by the present invention, wherein the thickness is adjustable based on compression. Therefore, the thickness of the composite material (usually compressed) can be about 10-1000 microns, or in any narrower range therein based on the benefits required for the final composite material. The present invention also contemplates the powder or granular form of carbon aerogel, wherein binder and particle size optimization are required. The range of particle (such as bead) size can be about 1-50 microns.
[0380] In one embodiment, the invention is an anode of a LIB comprising a silicon-doped, polyimide-derived carbon aerogel as disclosed herein, wherein the silicon particles are at least partially contained within the pores of the carbon aerogel. The general reactions and processes for developing polyimide-derived carbon aerogels (i.e., without silicon) can be found in Figure 3 and further reference Fig.49B As described. As can be seen, the structure of the carbon aerogel pores can be adjusted to have different properties (e.g., pore volume, pore size distribution) as needed (e.g., the size or capacity of the electrode in the LIB). In another embodiment, the present invention is an electrode in a LIB or its electrochemical cell, including such an anode. In yet another embodiment, the present invention is a device or system incorporating such an energy storage device. Examples include, but are not limited to, electric vehicles and electronic devices (e.g., mobile devices and drones).
[0381] In certain embodiments, the present invention is a method of forming or making a continuous porous carbon-silicon composite material, such as a carbon aerogel. Polyimide precursors, such as diamines and dianhydrides, which may each include aromatic groups and / or aliphatic groups, are mixed in a suitable solvent (e.g., a polar, aprotic solvent). Before adding an imidization gel catalyst, silicon particles are mixed into the polyimide precursor in the solvent. The imidization gel catalyst is then added to initiate gelation of the mixture. Such embodiments are described above with reference to bead formation.
[0382] In an alternative embodiment, imidization can be achieved via thermal imidization, wherein any suitable temperature and time range is contemplated (e.g., about 100°C-200°C for about 20 minutes to about 8 hours, followed by heating at about 300°C-400°C for about 20 minutes to about 1 hour). The gelled mixture is then dried to produce a continuous porous polyimide silicon composite material, wherein the drying can be performed using subcritical and / or supercritical carbon dioxide. Optionally, the polyimide silicon composite material can be compressed, preferably uniaxially compressed (e.g., up to 95% strain), to increase the density, which can be adjusted to about 1.5 g / cc depending on the amount of compression. In an exemplary embodiment, the polyimide silicon composite material can be compressed to greater than about 80% strain prior to pyrolyzing the composite material. Whether or not compression occurs, the polyimide silicon composite material is pyrolyzed to produce a continuous porous carbon silicon composite material, wherein the resulting composite material contains greater than 0% by weight and less than about 95% by weight silicon, and contains a porosity of about 5%-99%. In certain embodiments, pyrolysis may be conducted at a maximum temperature of about 750°C to about 1600°C, optionally with graphitization at about 1600°C to about 3000°C.
[0383] In certain embodiments, the carbon-silicon composite material can be a monolithic or independent structure, can be prepared on or off a substrate, can be micronized into a powder form, or can be prepared as a particulate material, such as beads. In addition, the composite material can be reinforced with or without a non-woven or woven material (e.g., fiber, foam, etc.). Optionally, the composite material can be pre-doped with a metal or metal oxide, for example, including but not limited to tin, sulfur, phosphorus, nickel, cobalt, manganese, lithium, magnesium, iron, zinc, boron, titanium, aluminum oxide, titanium oxide, niobium oxide, molybdenum oxide, silicon dioxide and aluminosilicate. In addition, the silicon particles can be pre-doped with p-type receptors (e.g., boron, aluminum, gallium and indium) or n-type receptors (e.g., phosphorus, lithium, arsenic, antimony, bismuth).
[0384] In an alternative embodiment, the above method can be used to form or make a porous carbon-silicon composite material, except that instead of mixing silicon particles into a mixture of a polyimide precursor in a solvent, a silicate (e.g., silicon dioxide, aluminosilicate and / or halloysite) and a reducing agent (e.g., magnesium, lithium, sodium, potassium, aluminum, calcium, or a combination thereof) are mixed into a mixture of a polyimide precursor in a solvent. After drying, a continuous porous polyimide silicate and reducing agent composite material is formed, which can be optionally compressed to adjust the density. In this case (i.e., when a silicate and a reducing agent are used), the silicate and the reducing agent react in situ with hydrogen under inert conditions at a temperature greater than about 700° C. in the carbon composite material to form silicon.
[0385] In another alternative embodiment, the above method can be utilized, except that instead of adding silicon or silicate + reducing agent to the polyimide precursor, a continuous porous carbon (i.e., a polyimide precursor, imidized using a catalyst or heating, drying, and pyrolysis) can be formed first, and then silicon is deposited onto or into the porous carbon. In this case, silicon is deposited by dip coating the porous carbon into a silane precursor formed by silicon, and then heating under inert conditions to decompose the silane to form a conformal silicon coating within the porous carbon. This dip treatment can be performed multiple times to increase the thickness and silicon content by weight up to about 95%. In other embodiments, silicon can be deposited via atomic layer deposition or CVD.
[0386] In addition, this article also considers that the pore size of the porous carbon composite material can be adjusted as needed. This article teaches five main methods for adjusting the pore size. First, the amount of solid content, specifically the amount of polyimide precursor monomers (such as aromatic or aliphatic diamines and aromatic or aliphatic dianhydrides), can adjust the pore size. Smaller pore sizes are due to a larger amount of solids per unit volume of fluid because there is less space available, resulting in tighter interconnections. It should be noted that no matter how the amount of solids used, the pillar width will not change measurably. The amount of solids is more related to how dense the network is.
[0387] Another method of regulating pore size is to use radiation (e.g., radio waves, microwaves, infrared, visible light, ultraviolet light, X-rays, gamma rays) on the composite material in the polyimide or carbon state. Radiation has an oxidizing effect, resulting in an increase in surface area, an increase in pore size, and a broadening of the pore size distribution. Third, pore size is affected by macroscopic compression of the polyimide composite material. As demonstrated in the following examples, pore size decreases with compression.
[0388] Yet another method of regulating pore size is to ion bombard a composite material in a polyimide or carbon state. The effect of ion bombardment depends on the method specified. For example, there is additive ion bombardment (e.g., CVD), in which something is added that causes the pore size to decrease. There is also destructive ion bombardment, in which the pore size increases. Finally, in different gas environments, such as the presence of carbon dioxide or carbon monoxide, chemically active environments, hydrogen reduction environments, etc., the pore size can be adjusted (increased or decreased) by thermal treatment. For example, it is known that a carbon dioxide environment can produce activated carbon, in which, in the case of activation, agglomerates are removed, the pore size increases, and the surface area increases.
[0389] While each of the above methods of adjusting pore size are contemplated, this disclosure will focus more on varying the solid content (polyimide precursor) and compressing the polyimide composite followed by carbonization.
[0390] Example
[0391] The following examples are described for illustrative purposes only and are not intended to limit the scope of the various embodiments of the present invention in any way.
[0392] Example 1: Carbonized polyimide (CPI) composite material containing low level doping
[0393] A. CPI with 9% dopant dispersed in polyimide
[0394] Polyimide (PI) gels were prepared from 1:1 molar ratios of pyromellitic dianhydride (PMDA) and 1,4-phenylenediamine (PDA) in DMAC solvent at a target density of 0.06 g / cc. The precursors were mixed at room temperature for 3 hours, then acetic anhydride (AA) was added at a 4.3 molar ratio relative to PMDA and mixed with the solution for 2 hours. Powder dopants such as graphite CNGT0112 with a thickness of ~40 nm and a length of ~400-600 nm, and silicon BASIC005 with spherical particles of ~30-nm diameter were obtained from ACSMATERIALS. The solution was doped with graphite or silicon (Si) at 4.5% / total solids. The graphite was mixed with the solution for 10 minutes with a magnetic bar stirring, and the doped mixture and imidization were catalyzed with pyridine (Py). Based on visual assessment, the graphite was well dispersed. After stirring the silicon with the polyimide solution for 10 minutes, the dispersion was visually poor (i.e., there was evidence of sedimentation and / or particle agglomeration in the solution state), and the mixture was sonicated for an additional 3 minutes. Once the dispersion quality improved, pyridine catalyst was added to the mixture. The molar ratio of Py to PMDA was 4.0.
[0395] To prepare the PI composites, the solution was cast between glass plates with spacers on the edges to control the thickness. Other suitable methods of casting the solution are also considered herein. The spacers were made of 200-micron thick aluminum foil. Monolithic sheets of approximately 2 inches in diameter were also cast in Teflon containers. For graphite-doped samples, the gel time was ~11.5 minutes at ambient temperature, and for silicon-doped samples, it was ~15.5 minutes. The gel was cured overnight at room temperature and then subjected to 3 ethanol exchanges at 68°C, followed by supercritical CO2 extraction. The PI aerogel composites were compressed from approximately 250 microns to various thicknesses and pyrolyzed at 1050°C under an inert atmosphere for 2 hours to carbonize, thereby forming CPI composites. Based on the amount of dopant in the formulation and the weight of the composite retained after pyrolysis, the dopant % in CPI was calculated to be ~9%.
[0396] The density of the compressed CPI composites with thickness of 80-50 microns ranged from 0.24-0.36 g / cc (Table 3 and Figure 4 ).
[0397] Table 3. Properties of low-density CPI composites doped with 9% graphite or Si.
[0398]
[0399] The porosity was calculated based on the actual density and skeletal density of the CPI composites. Since the density of amorphous carbon ranges from ~2.0-2.3 g / cc and the density of silicon or graphite is ~2.3 g / cc, the skeletal density used in these calculations was ~2.2 g / cc for all composites. The calculated porosity for these low density composites was 84-89%.
[0400] B. CPI dispersed in solvent by mixing with 9% dopant
[0401] A similar experiment was performed using a solution of 0.10 g / cc polyimide target density. In this case, the dopant was mixed with part of the DMAC for 10 minutes and added to the mixture before catalysis. A 500-micron thick Teflon pad was used for casting. The molar ratio of Py to PMDA was 2.0. For the graphite-doped sample, the gelation time was ~2.5 minutes, and for the silicon-doped sample, it was ~4.0 minutes. The gel was extracted with supercritical CO2. The PI aerogel composite was compressed from about 580 microns to various thicknesses and pyrolyzed at 1050°C for 2 hours to carbonize to form a CPI composite.
[0402] The properties of the CPI composites are shown in Table 4. As expected, the more compressed composites showed lower porosity.
[0403] Table 4. Properties of high-density CPI composites doped with 9% graphite or Si.
[0404]
[0405] The density of the compressed CPI composites (~115-80 micron thickness) ranged from ~0.57-0.87 g / cc. The density of the silicon-doped CPI composites was slightly lower ( Figure 5 ).
[0406] The density and shrinkage of the doped PI aerogel monomers after pyrolysis are shown in Table 5. The density of the non-compressed monoliths (LS1 and LG1) is lower than that of the compressed composites (LS2 and LG2).
[0407] Table 5. Density and shrinkage of doped CPI aerogel monoliths.
[0408]
[0409] SEM images of the pyrolyzed composites doped with silicon are shown in Figure 2. Figure 6A-6B As shown; please note that Figure 6B The fibrous morphology of the Si-doped CPI composite is shown, with scattered Si clusters and Si nanowires embedded in the carbon matrix. Figure 7 Anode discharge capacity per dopant content in half-cell battery tests is shown. Silicon provides significantly higher initial capacity compared to graphite dopants. While the initial capacity decreases with cycling, its reversible capacity is still significantly higher than graphite alone in conventional anodes. Additionally, the capacity fade is likely due to the foil electrode used in these half-cell tests, which is not able to operate at the high capacities of silicon-containing electrodes.
[0410] Example 2: CPI loading material with high PI solids content and high level of silicon doping
[0411] A. CPI doped with 27% silicon dispersed in solvent by ultrasonic treatment
[0412] Polyimide gels were prepared using a 0.10 g / cc target density. PMDA and PDA precursors were mixed at room temperature for 3 hours. Separately, 30 nm particle size silicon powder was sonicated in DMAC solvent for 20 seconds and added to the mixture at 15.0% / total solids and stirred for 15 minutes. AA was added to the doped mixture at a 4.3 molar ratio relative to PMDA and mixed for 2 hours. Pyridine was used at a 2.0 molar ratio relative to PMDA to catalyze the mixture. The composite was cast between glass plates using a 500 micron thick Teflon spacer. A 2 inch diameter monolith was also cast in a Teflon container. The gelation time was ~3.5 minutes at ambient temperature. The gel was cured overnight at room temperature and then subjected to three (3) ethanol exchanges at 68°C and then supercritical CO2 extraction. The PI aerogel composite was compressed and pyrolyzed at 1050°C for 2 hours to carbonize to form a CPI composite.
[0413] B. CPI doped with 46% and 64% silicon dispersed in solvent by ultrasonic treatment
[0414] A polyimide gel with a target density of 0.08 g / cc was prepared. The PMDA and PDA precursors were mixed at room temperature for 4 hours. AA was then added and mixed with the solution for 2 hours. Separately, 30 nm particle size silicon powder was ultrasonically treated in DMAC solvent for 1 minute and added to the mixture 5 minutes before the addition of the pyridine catalyst. Silicon was added at ~29.7% and ~49.6% / total solids. A 3.2 molar ratio of Py:PMDA was used to catalyze the doping mixture. The composite was cast using a 500 micron thick gasket. The gelation time was ~6.5 minutes at ambient temperature. After processing and extraction, the PI aerogel composite was compressed and pyrolyzed at 1050°C for 2 hours to carbonize, thereby forming a CPI composite.
[0415] Table 6 and Figure 8 A comparison of surface area and porosimetry of pyrolyzed, non-compressed monoliths doped with different amounts of silicon is presented. As the silicon content in the CPI increases, the surface area, micropore area, and pore volume decrease.
[0416] Table 6. Density and porosity determination of CPI monoliths doped with different amounts of Si. In addition, the visible pore volume is at least About 1.5cc / g.
[0417]
[0418] The pore size distribution at the maximum peak depends on the silicon content and the way the silicon is dispersed ( Fig. 9 ). In general, by increasing the silicon content, the pore size at the maximum peak shifts from the distribution to larger pore sizes. A shift of the main peak at the maximum size distribution is observed from ~23 nm to ~26 nm to ~34 nm as the Si content increases from ~9% to ~46% to ~64%, respectively. The substrate pore size distribution also broadens with increasing silicon content.
[0419] However, compared to the Td 0.10 g / cc sample, the 27% Si monolith prepared by adding silicon before AA and mixing with the solution for a long time shows a shift in the main peak to ~15 nm pore size vs. ~23 nm (9% Si monolith prepared by short Si mixing with solution). The sample doped with 27% Si content shows a bimodal pore size distribution with another small broad band centered at 30 nm. This is likely due to incomplete dispersion of silicon in the high target density, high viscosity mixture. The same is true for the higher silicon content (64%) sample in the series, which also exhibits a bimodal pore size distribution.
[0420] The compressed pyrolyzed composites have higher density, smaller surface area and pore volume compared to their non-compressed monolithic counterparts (Table 7). Density was calculated as the average of six (6) samples.
[0421] Table 7. Density and porosity determination of CPI compressed composites with variable Si doping. In addition, the visible pore volume is at least about 0.3 cc / g.
[0422]
[0423] Half-cells (2032-button cells) were constructed with CPI composites as electrodes, lithium foil as counter electrode, and CELGARD 2500 as microporous separator between the electrodes. The electrolyte was 1.0M LiPF6 in EC:EMC (3:7) by weight. Unless otherwise stated, all cells were tested using an ARBIN BT2043 tester at a charge / discharge rate of 0.1C. The discharge capacity of the compressed CPI composites at the 5th cycle is given in Table 8.
[0424] Table 8. Discharge capacity of Si-doped compressed CPI composites (half-cell battery test).
[0425]
[0426] like Fig.10 As shown, the best performance of these samples is obtained at Si contents of 30-50% / CPI.
[0427] Figures 11A-11C SEM images of composites doped with high Si content are given in Figure 2, which also show the fibrous morphology of the composites. The silicon (lighter areas) is more dense in samples with higher doping levels. At high magnification, Si nanowires can be observed in all samples. As can be seen, there is direct contact and interpenetration of silicon with the carbon porous structure (darker areas).
[0428] Cycling capacity based on Si and electrode content Figures 12A-12F The original data is shown in Table 9. Increasing Si loading of the CPI composites resulted in a faster capacity decrease with cycling. That being said, the capacity fade could be due to the foil electrode used in these half-cell tests, which is therefore unable to operate at the high capacities of the silicon-containing electrodes.
[0429] Table 9. Data comparing the discharge capacity of silicon (at various concentrations) and whole electrodes.
[0430]
[0431] As can be seen from Table 9, the silicon utilization can be calculated to be about 20% to about 90%, depending on the amount of silicon incorporated into the electrode, or even more preferably about 50% to about 90%. Narrower ranges are also contemplated herein based on the desired benefit of the final composite material (e.g., the amount of silicon required). Overall, this broader range is significantly higher than that seen in the conventional art. In addition, the capacity at cycle 10 can be considered to vary depending on the concentration of silicon, although it may be beneficial to be about 800 mAh / g or greater.
[0432] Example 3: Silicon-doped CPI composite material with low PI solid content
[0433] A. CPI doped with 66% silicon dispersed in a solvent by ultrasonic treatment
[0434] A polyimide gel with a target density of 0.05 g / cc was prepared. PMDA and PDA precursors were mixed at room temperature for 3 hours. AA was then added and mixed with the solution for 2 hours. Separately, silicon powder with a particle size of ~30-nm was sonicated in DMAC solvent for 2 minutes and added to the mixture 30 minutes before the addition of the pyridine catalyst. Silicon was added at ~60.5% / total solids. The Py / PMDA molar ratio was 7.5. The gelation time was ~5.5 minutes at ambient temperature. The composite was cast using a 500 micron thick gasket. After processing and extraction, the PI aerogel composite was compressed and pyrolyzed at 1050°C for 2 hours to carbonize, thereby forming a CPI composite. The Si content / CPI was 66%.
[0435] The CPI composites compressed to different thicknesses were examined by SEM, e.g. Figures 16A-16B , which depicts the fibrous morphology of the CPI composite. No silicon nanowires were observed in these images. The properties of the low compression (LC) and high compression (MC) composites tested in half-cell batteries are shown in Table 10.
[0436] Table 10. Properties of CPI composites doped with 66% Si.
[0437]
[0438] Figures 14A-14B The thickness is shown to play a role in the performance of the anode. By reducing the thickness by about half, the electrode capacity is essentially doubled, and the 170 micron thick electrode shows a discharge capacity of over 1500 mAh / g after the 4th cycle. Although these high capacity CPI composites loaded with a large amount of silicon (66%) are not stable over multiple cycles, the capacity fade may be due to the foil electrode used in these half-cell battery tests, which is therefore unable to work at the high capacity of the silicon-containing electrode.
[0439] B. CPI doped with 45% silicon dispersed by mixing in solvent with or without dispersant
[0440] A polyimide gel with a target density of 0.05 g / cc was prepared. PMDA and PDA precursors were mixed at room temperature for 17 hours. AA was then added and mixed with the solution for 3 hours. Separately, 30 nm particle size silicon powder was mixed in DMAC solvent with or without a dispersant for 20 hours. The control C45 sample was prepared without a dispersant. BYK 384 was used as a dispersant in sample B45 at 20 wt% / Si weight. Pluronic F87 was used as a nonionic surfactant in sample P45 at 20 wt% / Si weight. The dispersion was added to the mixture 30 minutes before adding to the pyridine catalyst. Silicon was added at 27.3% / total solids. The Py / PMDA molar ratio was 7.0. The gelation time was about 11 minutes at ambient temperature. The composite was cast using a 500 micron thick gasket. After processing and extraction, the PI aerogel composite was compressed and pyrolyzed at 1050°C for 2 hours to carbonize to form a CPI composite. The Si content / CPI was about 45%.
[0441] SEM images of the compressed C45 polyimide composite before and after pyrolysis are shown in Figures 15A-15B ,in Fig. 15B The fibrous morphology of the CPI composite is also shown. The silicon nanowires are not visible in the unpyrolyzed composite, only in the CPI. SEM images of the CPI composites with and without dispersant are shown in Figure 2. Figures 16A-16C The properties of the CPI composites submitted for battery testing are shown in Table 11. Conductivities of ~26-27 S / cm were obtained for these samples.
[0442] Table 11. CPI composites prepared with and without dispersants for battery testing.
[0443]
[0444] The half-cell battery pack test results show that the P45 composite material has higher discharge capacity and lower irreversible capacity loss ( Figures 17A-17C ). Additionally, the capacity fade may be due to the foil electrode used in these half-cell tests, which is not able to operate at the high capacities of the silicon-containing electrodes.
[0445] Composites of the P45 formulation were cast at three (3) thicknesses: 780, 580, and 370 microns. Each of these PI batches was cut into approximately 0.5 x 0.5 square inch sheets of composite material, which were compressed at three (3) different levels using a hydraulic press and then pyrolyzed. The results are shown in Tables 12 and Fig.18 middle.
[0446] Table 12. Properties of P45 CPI composites compressed at different levels.
[0447]
[0448]
[0449] The density of Si-doped CPI composites varies between 0.3 and 1.0 g / cc at thicknesses of ~50-130 μm ( Fig.18 ). The density increases with the initial thickness of the PI composite. The porosity ranges from ~50-90%.
[0450] Electrical conductivity of silicon-doped CPI composites. The electrical conductivity of CPI composites pyrolyzed at 1050°C doped with various levels of silicon was measured using a Keithley 4-point probe apparatus. The conductivity of the samples varied from 5 to 80 S / cm (Table 13). The conductivity of the non-doped carbon composite was approximately 13.6 S / cm, which is within the expected range for amorphous carbon known in the art. The reported conductivity of silicon was 1.6 x 10 -5 S / cm, while silicon nanowires can exhibit conductivity three (3) orders of magnitude higher (0.03 S / cm) (Sabar D. Hutagalung, Mohammed M. Fadhali, Raed A. Areshi and Fui D. Tan, "Optical and Electrical Characteristics of Silicon Nanowires Prepared by Electroless Etching," Nanoscale Research Letters, 2017, 12:425).
[0451] Table 13. Density and conductivity of CPI composites at various Si concentrations .
[0452]
[0453] Generally, electrical conductivity increases with density. However, when silicon concentration exceeds 60%, the conductivity is lower than expected ( Fig.19). At such high silicon content, the connectivity of the carbon network is destroyed, resulting in a decrease in conductivity. The sample doped with 27%wt Si / CPI showed the highest conductivity, indicating optimal silicon dispersion to achieve high conductivity. A wider optimal range can be considered to be about 5% to about 80%wt Si / CPI, or more specifically, about 5% to about 50%wt Si / CPI. It can be seen from Tables 11 and 13 that varying the silicon content can adjust the conductivity to about 80S / cm. It is therefore contemplated that the conductivity may be higher than about 5S / cm, 10S / cm, 15S / cm, 25S / cm, 50S / cm and 75S / cm, with a wider range and more precise conductivity being adjustable based on the silicon content.
[0454] Example 4: Carbonized polyimide aerogel with high pore volume and narrow pore size distribution
[0455] The polyimide gel was prepared by reacting 6 g of PMDA with 3 g of PDA at room temperature for 2-24 hours to form polyamic acid in 100 mL of DMAC. Subsequently, 8.86 g of AA was added to the polyamic acid solution as a chemical imidization agent (see Fig. 20 ). The acidified polyamide solution is vigorously mixed for at least 2 hours. The resulting mixture is diluted with DMAC to the target density required for the PI aerogel. 1-4g Py / 100mL mixture is added to the final solution to promote gelation, which occurs within 4-25 minutes. Before gelation, the mixture is cast into a desired form (e.g., film, monolithic sheet, reinforcing fiber, etc.). The gel obtained is then aged in an oven at 65-70°C and washed / rinsed several times with ethanol before supercritical drying. The PI aerogel is converted into a carbon aerogel by pyrolysis at 1050°C for 2 hours in an inert environment (nitrogen flow). Without being bound by theory, the physical and structural properties of the carbonized PI aerogel depend on the precursor mixing time and the amount of Py.
[0456] The structural properties of the four CPI aerogels tested by nitrogen adsorption-desorption technique are reported in Table 14. The four samples differed in mixing time and Py amount. The target density was fixed at 0.05 g / cc. Interestingly, all samples showed relatively similar surface BET, but the pore size distribution and pore volume seemed to be affected by the synthesis parameters.
[0457] Table 14. Physical and structural properties of different CPI aerogels.
[0458]
[0459] 1: Mixing time of the two precursors.
[0460] 2: Amount of pyridine added for gelation (g / 100 mL of solution)
[0461] Example 5: Carbonized polyimide aerogel loaded with Si
[0462] Silicon particles (30nm) are added to polyamic acid solution with different concentrations.Solution synthesis is identical with the solution synthesis described in Example 4. However, in this composite material system (PI / Si), first silicon particles are dispersed in DMAC and continue at least 2 hours, and then it is blended with polyamic acid solution. In order to avoid Si sedimentation, the gel time of Si / polyamic acid solution keeps relatively short (4-6 minute). For this reason, 4g pyridine / 100mL mixture is used to meet the target gel time. Before gelation, the mixture is cast into required form (such as, film, monolithic or reinforcing fiber etc.). Then the gel obtained is aged in a baking oven at 65-70 ℃, and washed with ethanol / rinsed several times before supercritical drying.
[0463] A. 22-25 wt% Silicon in Polyimide Carbon Aerogel Composites
[0464] During the polymerization stage, the target density of the composite was fixed at 0.06 g / cc and the Si content was about 11.88 wt %. The silicon content was adjusted after pyrolysis of the polyimide aerogel at 1050°C for 2 hours, since no less than 50% weight loss was recorded for all samples. Composites with four different thicknesses were produced:
[0465] MT (medium thickness composite material ~ 0.3-0.4mm)
[0466] T (thick composite material ~ 0.6-0.8mm)
[0467] MTC (Medium Thickness Compression Composite ~ 0.07-0.09mm)
[0468] TC (thick compressed composite material ~ 0.12-0.16mm)
[0469] Different PI / Si samples were pyrolyzed at 1050°C for 2 hours and subjected to battery tests. The physical properties of the samples are listed in Table 15.
[0470] Table 15. Physical properties of different C / Si composites.
[0471]
[0472]
[0473] SEM images of pyrolyzed composite materials (MT materials) doped with ~25% Si can be found at Fig.23 Shown in Figure 2. SEM image showing some agglomeration of Si and Si nanowires embedded in the carbon substrate at high magnification.
[0474] Based on Si and electrode content, the cycling capacities of MTC5 and MT5 samples are shown in Figures 25A-25B As shown. Cycling was performed up to 400 cycles for MTC5 (compressed CPI aerogel) and up to 150 cycles for MT5 (non-compressed CPI aerogel). The two samples exhibited different behaviors. MTC5 exhibited relatively stable capacity discharge up to 200 cycles, after which the capacity dropped, likely due to the foil electrodes in the half-cell battery tests, as discussed previously.
[0475] B. 39 wt% Silicon in Polyimide Carbon Aerogel Composite
[0476] In the next round of synthesis, the Si content was increased to 39wt%, in the hope of reducing the capacity loss during the first discharge. A polyimide gel with a target density of 0.05g / cc was prepared. A polyamic acid solution was prepared over 16 hours by mixing PMDA and PDA precursors in DMAC. Separately, silicon powder was dispersed in DMAC for 2 hours and then added to the polyamic acid solution, followed by pyridine. After the addition of pyridine, a composite material was prepared between Teflon plates using a 500 micron spacer. The aerogel composite was compressed and then pyrolyzed at 1050°C for 2 hours. The silicon content was 39 wt% / total solids.
[0477] The properties of the compressed (PISi1NC(C)) and non-compressed (PISi7NC) composites tested in half-cell batteries are shown in Table 16.
[0478] Table 16. Physical characteristics of C / Si (Si ~ 39 wt%) composites.
[0479]
[0480]
[0481] Figures 26A-26B The discharge capacity is illustrated as a function of cycling for anodes made from two materials reported in Table 16. When the silicon content is increased from 25 wt% (previous materials, i.e., MT5 and MTC5) to 39 wt%, a clear improvement in the anode-based discharge capacity can be noticed.
[0482] Example 6: Fiber-reinforced C / Si aerogel
[0483] Three different sintered carbon foams with different surface densities (2, 4, 10 g / m 2) as reinforcement for C / Si aerogel. The synthesis and processing of PI / Si aerogel were the same as described previously, with one exception. During the gelation step, the mixture was cast into fibers. After supercritical drying, the carbon fiber reinforced PI / Si composites were cut into 15-mm (inner diameter (ID)) round samples with a dye cutter and pyrolyzed at 1050 °C for 2 h. Figure 27-29 Properties and micrographs of carbonized PI / Si / carbon fiber samples are shown.
[0484] After pyrolysis, 2- and 4-g / m 2 The carbon fiber reinforced samples experienced high carbon aerogel and enhanced shrinkage. Figure 28-29 The high void fractions that characterize both materials are shown to make them unsuitable for battery testing. Fig. 27 Medium, use 10-g / m 2 Carbon fiber reinforced C / Si showed better microstructure and no evidence of voids. However, the Si content was low (~21%) and the fiber density was high (>30 wt%). This composite was tested for charge and discharge capacity in such a system. Fig. 27 The cycling capacities of the samples shown, based on Si and electrode content, are reported in Fig.30 middle.
[0485] In another experiment, cellulose fibers were also tested as reinforcement for C / Si. The synthesis route was the same as that used for carbon fibers. Cellulose fibers accounted for 68% (by weight) of the C / Si composite, although most of this fiber decomposed after pyrolysis because the Si% increased from 6% to 24% after pyrolysis. The physical characteristics of C / Si reinforced with cellulose fibers are reported in Table 17.
[0486] Table 17. Physical characteristics and composition of C / Si reinforced with cellulose fibers.
[0487]
[0488] The cycling capacity of C / Si reinforced with cellulose fibers based on Si and electrode content was reported in Fig.31 The performance of this material is similar to that of C / Si reinforced with carbon fibers.
[0489] Example 7: Improvement of Silicon Dispersion in PI Aerogels
[0490] Polyimide composites and monolithic gels loaded with 47% silicon were prepared with a target density of 0.05 g / cc. A route for better dispersion of silicon in the polyimide matrix was carried out to avoid agglomeration. Starting from the synthesis of the solution, the silicon was dispersed and mixed with PMDA and PDA. The polyamic acid solution + silicon was mixed for 16 hours. Acetic anhydride was added and mixed with the solution for 4 hours. Rapid gelation (~4 min) was ensured by adding an appropriate amount of Py to the acidified polyamic acid / Si mixture. Composites and thick monoliths with a thickness of ~200-300 microns were cast. After supercritical drying, the PI / Si aerogel composites were compressed and then pyrolyzed at 1050°C for 2 hours.
[0491] Subsequently, a number of different samples (eg compressed, non-compressed, monolithic, etc.) were analyzed by SEM to evaluate the dispersion of silicon in the carbon matrix. Fig.32 Three cross-sectional SEM images of a thick non-compressed composite (0.60 mm) are shown. At low magnification (left image), uniform and well-distributed silicon is illustrated. Large silicon clusters are also shown. At higher magnification (right image), it can be seen that the high density of silicon is well embedded in the carbon matrix. Fig.33 Three cross-sectional SEM images of thin composites (0.12 mm) are shown. The same observations are made, namely good Si dispersion and proper impregnation into the carbon matrix. Cross-sectional SEM images of a single sheet ( Fig.34 ) clearly confirms the same structure shown in thick and thin composites.
[0492] Figure 35-36 A side-by-side comparison of two differently processed C / Si composites is shown. The left image (in both images) is for monoliths and composites cast from a Si / PA solution mixed for 16 hours (long contact). The right image is for monoliths and composites made from a Si / PA solution mixed for 4-6 minutes (short contact). In the two processes, the distribution of Si is observed to be different. Long contact ensures better Si dispersion than short contact.
[0493] Half-cell tests were performed on compressed and non-compressed C / Si composites. Both samples PISi3 (non-compressed) and PISi6C (compressed) have good Si dispersion in the carbon aerogel matrix. The physical properties of both samples are reported in Table 18.
[0494] Table 18. Physical properties of C / Si (mixed for 16 hours) submitted for half-cell testing .
[0495]
[0496] The charge-discharge cycles of the two samples are shown in Figure 37-38The samples performed surprisingly well, with the compressed sample (PISi6C) showing stable cycling performance.
[0497] Example 8: C / Si circular electrode fabrication
[0498] In the previous examples, the C / Si electrodes were square (~1 cm 2 ) and tested the battery pack performance in a round battery (ID = 15mm). For higher test efficiency and more reliable test results, it is necessary to test the round C / Si electrode. Therefore, a die-cutting machine is used to prepare the round electrode route.
[0499] A PI aerogel composite with a target density of 0.13 g / cc and loaded with 31.4% Si (using 16 hours of mixing) was produced. After extraction, the final aerogel density was measured to be approximately 0.213 g / cc. Using a die cutter, multiple round aerogel composites with an ID of 15 mm were produced (see Fig.39 ). The thickness of the sample is about 0.43 mm. Part of the sample was compressed and then pyrolyzed at 1050 °C for 2 hours. The characteristics of the pyrolyzed circular electrode are as follows:
[0500] Weight loss: ~41%
[0501] Non-compressed sample: ~0.261 g / cc (1.1 cm ID, 0.38 mm thick)
[0502] Compressed sample: ~0.652 g / cc (1.35 cm ID, 0.11 mm thick)
[0503] Compressed and uncompressed half-cell battery performance Figure 40-41 The capacity of the non-compressed sample appears to be higher than that of the compressed sample, although the non-compressed sample also produces a more volatile capacity.
[0504] Example 9. Carbonized phloroglucinol / formaldehyde (PF) aerogel loaded with Si
[0505] Carbon aerogels made from PF are also considered for C / Si aerogel electrode manufacturing. For PF systems, high target density (>0.7g / cc) aerogels can be achieved through synthetic routes. The obtained aerogels do not need to be compressed. The obtained aerogels do not need to be compressed. High-density PF gel composites were manufactured as follows. Phloroglucinol (22g) was dissolved in 100mL of ethanol, and 44mL of 2-furfural was added to the phloroglucinol solution. The obtained solution was mixed for 30 minutes. 5 wt% silicon was added to the mixture and mixed vigorously for another 30 minutes. The PF mixture can be coagulated by alkali (diamine or triamine), and the gelation time is about 20-40 minutes, depending on the concentration of the alkali. In this case, in the presence of silicon, the gelation time should be shorter (less than 1 minute) to avoid any silicon precipitation during the gelation process. Hydrochloric acid (HCl) is used to catalyze PF gelation, and the gelation time is as short as 20 seconds. Therefore, 0.012 g of concentrated HCl / 100 mL of the mixture was added to the mixture, mixed for 20 seconds, and cast between Teflon plates for gel fabrication. After aging and solvent exchange, the PF gel composite was dried with supercritical CO2. The obtained PF / Si aerogel had the following properties:
[0506] Two thicknesses of composite material: ~0.2mm and ~0.1mm
[0507] Final density aerogel: ~0.7g / cc
[0508] After pyrolysis at 1050°C / 2h under inert gas, the obtained C / Si aerogel had a density of 0.77 g / cc and an adjusted %Si of 10 wt%. 2 )(See Fig.42 ).
[0509] The specific surface area of C / Si aerogel tested by liquid nitrogen adsorption-desorption was 541 m 2 / g and a pore volume of 0.32cc / g. Interestingly, the micropore area accounts for 80% of the total surface area, which confirms the dense and compact structure in the SEM image (see Fig.43 ). In addition, Si-containing carbon aerogel composite samples, in which the carbon originates from PF, result in high capacity loss after the first cycle and very low total capacity (see Fig.44 ). These results highlight the unique properties of Si that perform better in fibrous morphologies, such as those seen in polyimide-derived nanoporous carbon / carbon aerogels.
[0510] Example 10: Nanoindentation as a measure of mechanical strength
[0511] Multiple CPI composite samples were prepared using the above method, where the variables in the samples included silicon content and density. The Young's modulus of each sample was measured using nanoindentation, which tests the hardness of the material. More specifically, twenty (20) indentations were run on the sample surface. About 8-10 indentations were selected to obtain average data and standard deviations for each mechanical property. The indentation locations were selected under a microscope, where the surface was relatively clean and smooth, and there were not many surface features, thus providing more reliable data. Since samples 1 and 2 were softer than the other samples, a 50-mN maximum load was selected for samples 1 and 2. A 300-mN indentation load was used for samples 3-7. The results and other properties are shown in Table 20. Fig.45 plots the modulus as a function of density, and Fig.46 The modulus is plotted as a function of density.
[0512] Table 20. Physical properties of CPI samples tested by nanoindentation method.
[0513]
[0514]
[0515] Example 11: CPI beads doped with 45% silicon
[0516] Polyimide gel beads with a target density of 0.10 g / cc were prepared. PMDA and PDA precursors were mixed in DMAC solvent at room temperature for 3 hours. AA was then added and mixed with the solution for 2 hours. Separately, 30 nm particle size silicon powder was ultrasonically treated in DMAC solvent for 1 minute and added to the mixture 5 minutes before the addition of pyridine catalyst. Silicon was added at ~24% / total solids. The doped mixture was catalyzed using a 3.2 molar ratio of Py:PMDA. Prior to gelation, the catalytic sol containing silicon particles was poured into a stirred silicone oil container as a dispersion medium (with a volume ratio of 10:1 silicone oil:catalytic sol). The gelled PI beads were separated from the silicone oil by filtration, subsequently rinsed with ethanol, and then dried by supercritical CO2 extraction. The PI aerogel-silicon composite beads were then pyrolyzed at 1050°C for 2 hours to form CPI silicon composite beads having a tap density of 0.7 g / cc and D50=15 μm.
[0517] Example 12: Electrodes prepared from CPI beads
[0518] The anode electrode was prepared using CPI silicon composite beads prepared according to Example 11 on Cu foil as the current collector, using a slurry containing 80 wt% CPI silicon composite beads, 10 wt% polyacrylic acid (PAA) binder and 10 wt% hard carbon conductive additive (C65) (mixed in water, total solid content of about 36 wt%). The slurry was cast on the Cu foil with a doctor blade. After drying and calendering, a loading of 3.1 mg / cm 2 And the electrode has a density of 0.7g / cc.
[0519] Example 13: Half-cell constructed from CPI electrodes
[0520] Half-cells (2032 coin cells) were constructed with CPI composite electrodes prepared according to Example 12, with lithium foil as the counter electrode and CELGARD 2500 as the microporous separator between the electrodes. The electrolyte was 1.0 M LiPF6 in ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (3:7 mass ratio) and 5 wt % fluoroethylene carbonate (FEC). All cells were tested using an ARBIN BT2043 tester. The protocol for testing the cells included 4 formation cycles with a charge / discharge rate of C / 20. Subsequent cycles occurred at various rates between C / 20 and 5C. Fig.48 The half-cell cycling performance of a CPI composite electrode containing 30 wt % silicon particles is shown, the electrode being prepared as an electrode from a slurry containing 80 wt % CPI silicon composite beads, 10 wt % polyacrylic acid (PAA) binder, and 10 wt % hard carbon conductive additive (C65). Fig.48 The graph shows the discharge capacity (mAh / g based on total electrode weight) and coulombic efficiency versus cycle number in 1.0 M LiPF6 in ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (3:7 weight ratio) and 5 wt% fluoroethylene carbonate (FEC).
[0521] Example 14: Low density silicon doped carbonized polyimide beads using standard precursor addition and splicing bead process grain
[0522] Prepare a silicon-doped polyimide (PI) sol of a target density of 0.03-0.05g / cc. Pyromellitic anhydride (PMDA) and o-phenylenediamine (PDA) are mixed in a dimethylacetamide (DMAC) solvent in a 1:1 molar ratio to obtain a polyamic acid (PAA) sol. The PMDA precursor is stirred in DMAC at room temperature for 5-30 minutes, during which time complete dissolution occurs. PDA powder is added to the PMDA solution, and the mixture is stirred at room temperature for 2-17 hours. The process of adding diamine to the dianhydride is called the standard addition method. Polyamic acid is chemically imidized into polyimide using acetic anhydride and pyridine. Acetic anhydride (AA) is added to the sol at a 4.3 molar ratio relative to PMDA and mixed for 2-4 hours. Separately, a 30nm-sized silicon (Si) nanopowder from ACS Material is dispersed in DMAC using an ultrasonic generator bath for 1 hour. Silicon: PMDA in an approximately 2:1 molar ratio is used for doping the sol. The Si dispersion was mixed with the sol at room temperature for 5 to 30 minutes. Pyridine (Py) catalyst was added to the sol at a molar ratio of Py:PMDA of 2.4 to 5.4. The catalyst was mixed with the sol for 2 minutes before casting.
[0523] To prepare the gel beads, the silicon-doped PI sol is poured into a silicone oil with a viscosity of 10 cSt and stirred at 400 rpm with a magnetic bar or a mechanical stirrer. The volume ratio of silicone oil to sol is 10 / 1 or 20 / 1. Higher oil:sol ratios produce beads with less agglomeration and larger bead size. When light brown spherical beads emerge from the emulsion, gelation occurs at room temperature within 20-45 minutes. The beads are stirred overnight in oil at room temperature, decanted from the oil, and filtered through a 20-micron filter paper. The beads are kept moist by washing with ethanol during filtration. The gel beads collected from the filter paper are placed in an ethanol bath, aged and rinsed at 68°C for 1-3 days. After two hot ethanol rinses, the gel beads are filtered again and dried. Drying is performed at ambient temperature for 1 day by exposing the gel beads to the air as if diffused into the air in an open container. Occasionally, the beads are manually stirred and loosened with a spatula during drying.
[0524] After drying, the beads were placed in a graphite crucible and pyrolyzed in a CM box furnace under a nitrogen flow of 10-40 scfh. Most samples were pyrolyzed at 1050°C for 2 hours using a 3° / min ramp rate. One sample was pyrolyzed to 690°C using a 3° / min ramp rate. These formulations target 10-35 wt% Si in the carbonized beads.
[0525] Example 15: Low density silicon doped carbonized polyimide beads using reverse precursor addition and low shearing bead process grain
[0526] The silicon-doped polyimide (PI) sol of 0.03g / cc target density was prepared using the same precursor as in Example 14. After PDA was dissolved in DMAC, PMDA powder was added to the solution. The process of adding diacid anhydride to diamine is called reverse addition. The viscosity of the sol increased significantly and was significantly higher than the standard addition method. The mixture was stirred at room temperature overnight, and then acetic anhydride was added to PMDA in a 4.3 molar ratio. After 3 hours, a silicon-doped sol with a particle size of 30nm from ACS Material was used. Silicon dispersions were prepared using Dual Asymmetric Centrifugal Mixer and 1mm zirconium oxide beads from FlackTek Inc. The amount of silicon corresponding to a 2.0 molar ratio of PMDA was dispersed in a total DMAC amount of 40% by weight for 5 minutes at 3000rpm. After the resulting Si dispersion was mixed with the sol for 1 minute, a pyridine catalyst was added with a 5.4 molar ratio relative to PMDA.
[0527] The silicon-doped PI sol was poured into a silicone oil of 10 cSt viscosity (stirred at 400 rpm by a mechanical mixer). The gelation time was 21 minutes at room temperature, which was about twice as fast as the corresponding formulation prepared by the standard addition process. The gel beads were processed as in Example 14. After drying, the dry gel beads were pyrolyzed under nitrogen up to 690°C at a ramp rate of 3° / min. The PI beads lost 39% of their weight after pyrolysis. These formulations target 30 wt% of Si in the carbonized beads.
[0528] Example 16: Low density silicon doped carbonized polyimide beads using standard precursor addition and high shearing bead process grain
[0529] Silicon-doped polyimide (PI) sol was prepared from the same precursor as Example 14 using a standard addition process to a target density of 0.05 g / cc. The PMDA precursor was stirred at room temperature in DMAC for 30 minutes, during which time complete dissolution occurred. The mixing time was critical to the outcome of the process. Mixing PMDA in DMAC for less than 30 minutes produced a sol of higher viscosity, which then produced beads of larger size. PDA was added to a dianhydride solution in DMAC and stirred at room temperature for 2-17 hours. The resulting polyamic acid sol was chemically imidized with acetic anhydride (4.3 molar ratio vs. PMDA) and pyridine (4.2-8.1 molar ratio vs. PMDA).
[0530] Various silicon sources and particle sizes were used to dope the PI beads. Polycrystalline silicon of 30 nm size from ACS Material was dispersed in DMAC solvent and either sonicated in a bath for 1 hour or stirred at 2500-3000 rpm for 5 minutes using a FlackTek mixer. Zirconia beads of 1 or 2 mm diameter were used at 5-20% weight ratio vs. silicon weight. Amorphous silicon with a particle size D50 of 230 nm from Evonik (VP Sia) was dispersed in a polyamic acid sol using a FlackTek mixer for 5 minutes.
[0531] Polycrystalline silicon with a particle size of 1-5 microns from Silrec was prepared by different grinding methods. Using AcrossInternational high-energy ball mill, the Silrec Si particle size was reduced to about 500nm. FlackTek mixer is also used to reduce the Si particle size in DMAC by operating with zirconium oxide beads in a time range of about 20 to about 60 minutes. By this method, the particle size is reduced to about 700-1000nm. In another embodiment, Si is ground in ethanol using FlackTek mixer and ceramic media, and then the same FlackTek process is used to dry and redisperse in DMAC. In these embodiments, the particle size of the Si particles is about 760nm.
[0532] The Si particle dispersion prepared as described above was mixed with the PAA sol at room temperature for 2-20 minutes. After chemical imidization with acetic anhydride and pyridine, the sol was stirred for 1-2 minutes and slowly poured into a stirring oil bath. The viscosity of the silicone oil was 10 or 100 cSt, and the volume ratio of oil to PI sol was 5 / 1 or 10 / 1. The higher the oil viscosity and the lower the sol viscosity, the smaller the bead size produced. Although a 5 / 1 oil:sol ratio resulted in some bead agglomeration, this is preferred for scale-up purposes and also facilitates the separation of beads from the oil relative to a 10 / 1 ratio.
[0533] The oil bath containing the PAA sol was stirred at 3800–9400 rpm using a Ross mixer under high shear. Generally, higher shearing resulted in smaller beads. Due to high shearing, the temperature of the oil increased rapidly to 50-70°C within 5-10 minutes. During this period, the beads gelled and usually aggregated together. Generally, due to overheating, the total time of stirring with the Ross mixer was less than 30 minutes. After a few minutes of gelling, ethanol was poured on the oil and stirred for a few more minutes to minimize bead agglomeration and aggregation. The beads remained in the top ethanol layer and could be separated from the oil. Especially in the case of higher viscosity oils of 100 cSt, separation could be performed by decantation or by a separatory funnel. After filtering through 20 micron filter paper and washing multiple times with ethanol, the gel beads were placed in ethanol at 68°C for one to two days and then rinsed with ethanol twice at the same temperature.
[0534] Drying was performed at ambient pressure to form xerogels or under subcritical CO2 conditions to form aerogels. Several drying methods were used at ambient pressure: occasionally stirring the wet cake spread on a surface at room temperature for 1–3 days, heating in a 110 °C oven in a sealed container with a small vent for several hours, and finally heating the flat wet cake on a hot plate at 100 °C for 2–5 minutes followed by drying at room temperature overnight. A fluidized bed method was also used for room temperature drying of the gels. A sintered Buchner funnel was fixed to the top of a filter flask. The wet cake or gel slurry was placed on the frit and the top of the funnel was covered with a laboratory paper towel. Compressed air connected to the inlet of the filter flask was allowed to pass through the holes of the frit. The beads were maintained in the fluidized bed until the volatiles were removed and the xerogel was then collected from the funnel. Yields of PI xerogel or aerogel beads of 75–96% were obtained.
[0535] After drying, the beads placed in a graphite crucible were pyrolyzed in a box furnace at 1050°C for 2 hours at a ramp rate of 3° / min. The PI beads lost 42-47% weight after pyrolysis. The target Si in the carbonized beads was 30%.
[0536] Example 17: Low density silicon doped carbonized polyimide beads using a surfactant mediated process
[0537] Silicon-doped polyimide (PI) sols were prepared to a target density of 0.05 g / cc using a standard addition method with the addition of surfactant from the same precursor as in Example 14. Typically, surfactants are added to modify the surface of the beads in order to reduce their aggregation during or after gelation while stirring in an oil bath.
[0538] In one embodiment, after acetic anhydride is added, hexadecyl trimethyl ammonium bromide (CTAB) surfactant of 0.09mol / mol PMDA concentration is added to the sol. The surfactant is not completely dissolved in the sol. The 1-micron-sized silicon particles from US Nano Research that were previously ultrasonically treated in a part of the total DMAC solvent are added to the CTAB / sol mixture. Silicon is added with 2.1mol / mol PMDA. After mixing with pyridine for 2 minutes, the sol is cast in an oil bath and stirred with 6500rpm using a Ross homogenizer. Before, the oil was cooled to 10 ℃, and within 7 minutes of gelling, the temperature of the oil rose to 50 ℃. After processing beads by separating from the oil, rinsing and aging them in 68 ℃ of ethanol, the beads were ultrasonically treated with an ultrasonic generator probe for 1 minute in ethanol to disperse the gel clusters. The drying of beads is carried out in ambient air, as described in Example 16.
[0539] The PI xerogel beads lost 46 wt% C during pyrolysis at 1050° C. The target mass of Si in the pyrolyzed beads was 30 wt%. The tap density of the beads was 0.65 g / cc.
[0540] Example 18: Low density silicon doped carbonized polyimide beads using reverse precursor addition and high shearing bead process grain
[0541] Aerogels with a target density of 0.02 g / cc were prepared by a reverse addition scheme, as shown in Example 15. The precursors were mixed for 17 hours, then acetic anhydride was added and mixed for 2.5 hours. The 1-5 micron-sized Si powder from Silrec was first dried and ground with zirconium oxide beads in FlackTek, then dispersed for 5 minutes at 2500 rpm in a portion of the PAA sol using the same device. The Si dispersion (after the zirconium oxide beads were removed by filtration) was mixed with the remainder of the sol, and a pyridine catalyst was added with respect to a 10.1 molar ratio of PMDA. The mixture was stirred for 25 minutes before casting.
[0542] The silicon-doped PI sol was slowly poured into silicone oil of 100 cSt viscosity (stirred at 6000 rpm by a Ross mixer). The beads gelled after 5 minutes in an oil bath at 50°C. After stirring in the oil for another 2 minutes, the beads were decanted from the oil, washed 3 times with ethanol at room temperature, and then placed in ethanol at 68°C for 1 day. The hot rinse procedure was repeated 3 times using a volume ratio of 800 / 1 ethanol: gel beads. The beads filtered from the ethanol were exposed to air for 25 minutes to form a skin with less porosity than the core. These beads were extracted using subcritical CO2 conditions. The resulting beads were measured to have a porosity of approximately 200 m 2 The high surface area of 1.34 nm / g indicates that the beads are mostly aerogel-like.
[0543] The beads were pyrolyzed under nitrogen up to 1050°C using a 3 deg / min ramp rate. The PI beads lost 40% weight after pyrolysis. The target weight of Si was 50% by weight in the carbonized beads. The tap density of the beads was 0.37 g / cc
[0544] Example 19: High density silicon doped carbonized polyimide beads with standard precursor addition
[0545] Silicon-doped polyimide (PI) sol was prepared under 0.1g / cc target density and 60 wt % silicon loading. PMDA precursor was dissolved in DMAC by stirring for about 30 minutes with a magnetic stirrer. PDA was added to PMDA solution with a 1:1 mol ratio of PDA:PMDA, and stirred for 2-17 hours using a magnetic mixture at room temperature. The gained polyamic acid sol was chemically imidized and mixed for 1-4 hours with acetic anhydride (4.3 mol ratio vs.PMDA). Individually, 1 micron-sized silicon was dispersed in a part of polyamic acid sol with a mol ratio of 9:1 silicon:PMDA. In this embodiment, 10g silicon was dispersed in 70g polyamic acid sol with a ratio of 1:1 in the presence of 25g 1mm and 0.25mm zirconium beads, to prevent agglomeration and provide silicon dispersion. Silicon dispersion was mixed with sol for about 5 minutes using a Flackteck mixer at about 2500rpm. The dispersed silicon solution was poured back into the mother solution (the other part of the polyamic acid sol) and stirred for another 30-60 minutes using a magnetic mixer.
[0546] Pyridine (Py) catalyst is added to the sol with a 5: 1 molar ratio of Py:PMDA. Py is mixed with the sol for about 1 minute and then poured into silicone oil under high shear mixing (using Ross mixer). Silicone oil (polydimethylsiloxane, 100cSt) is used as a medium for bead gel formation, and the volume ratio of oil to sol is about 10: 1. For this embodiment, about 100ml of catalytic silicon-doped polyamic acid sol is poured into about 1000ml of silicone oil and mixed at about 9400rpm. The suspension of gel beads begins to form at a temperature within the range of about 9400rpm and about 60-70°C in about 2-3 minutes. For comparison, the remaining sol in a separate unmixed container gels in about 7 minutes at room temperature. After the gel beads are formed, the mixture is kept at high rpm (about 9400rpm) for 4-5 minutes.
[0547] Most of the oil was decanted and the gel beads were then filtered from the remaining oil using a 20 micron filter paper. The gel beads were rinsed with ethanol during filtration. The gel beads collected from the filter paper were placed in an ethanol bath and aged and rinsed at 68°C for 1-3 days.
[0548] After completing aging and flushing process, the silicon-doped polyimide gel beads are filtered, collected and fixed in 2 layers of laboratory tissues. Before being loaded in a high pressure container and carrying out subcritical drying, the gel beads protected by the laboratory tissue are placed in a filter bag of 5 microns. Then subcritical liquid CO is used by exchanging the solvent in the gel beads with the liquid CO in the container under a pressure in the range of about 800 to 1200psi for at least about 15 minutes, dry silicon-doped polyimide gel beads. Then the container is decompressed to atmospheric pressure. The size of the aerogel-like silicon-doped polyimide beads of gained is less than about 70 microns, and there is no agglomerate or cluster of beads.
[0549] The aerogel-like silicon-doped polyimide beads were carbonized at 1050° C. for 2 hours under a nitrogen flow. The physical and structural properties (surface area, pore size, and average pore diameter) of the silicon-doped carbonized polyimide beads are reported in Tables 21 and 22 below.
[0550] Table 21. Physical properties of beads of Example 18
[0551]
[0552] Table 22. Structural properties of beads from Example 18
[0553]
[0554] Example 20. C / Si composite beads prepared from polyimide in DMAC / silicone oil emulsion; 0 ppm water
[0555] Carbon / Si composite beads containing 55 wt% silicon were prepared from polyimide to a target density of 0.085. Benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic dianhydride; PMDA; 8.30 g) was added to dimethylacetamide (97.6 mL; anhydrous). The mixture was heated at 35°C until all solids dissolved and then stirred at room temperature for 30 minutes. Solid p-phenylenediamine (PDA; 4.1 g; 1 molar equivalent) was added to the solution and the resulting mixture was stirred for 2 hours. Acetic anhydride (16.7 g, 4.3 molar equivalents) was added to the stirred solution and then stirred for 2 hours. Silicon particles (6.2 g) and 1 mm diameter zirconia beads (7 g) were dispersed in 12 g of the above sol by stirring at 2500 rpm for 2 minutes. After removing the zirconia medium by filtration, the Si suspension was added to the above sol and then stirred for 10 minutes.
[0556] Pyridine (10.8mL; 8 volume %) is added to start gelation to form a polyamic acid presol. After 1 minute, the presol is quickly poured into silicone oil (polydimethylsiloxane; 100cSt; 650mL), while stirring with a Ross mixer at 9000rpm. About 6 minutes after adding pyridine, when gelation occurs, 750mL of ethanol is added and the stirring speed is reduced to 7000rpm. After stirring for another 2 minutes, each phase is separated and the beads are separated with a separatory funnel. The gel beads accumulate in the lighter ethanol phase, and the oil is separated as a heavier phase. After filtering from ethanol, the beads are mixed with heptane (150mL) for about 10 minutes and then collected by filtration. Repeat the heptane wash and then wash with a mixture of 120mL heptane and 120mL ethanol. The resulting filter cake is stirred in 150mL ethanol for 15 minutes and allowed to stand overnight at room temperature.
[0557] A portion of the polyimide / Si gel beads is dried using subcritical liquid CO2 by exchanging the solvent in the gel beads with liquid CO2 in a container at a pressure in the range of about 800 to 1200 psi for at least about 15 minutes. The container is then depressurized to atmospheric pressure to obtain polyimide / Si aerogel beads. The polyimide / Si aerogel beads are then carbonized at 1050°C under a nitrogen stream for 2 hours to provide C / Si aerogel beads (Example 20A). The properties of the aerogel beads are provided in Table 1 below. Fig.50 SEM images showing the inner surface of C / Si aerogel beads are provided.
[0558] Another portion of the beads was dried at 68° C. to obtain polyimide / Si xerogel beads. The polyimide / Si xerogel beads were then carbonized at 1050° C. for 2 hours under a nitrogen flow to provide C / Si xerogel beads (Example 20B).
[0559] Example 21. Preparation of C / Si composite beads from polyimide in DMAC / silicone oil emulsion; 716 ppm water
[0560] Carbon / Si composite beads containing 35 wt% silicon were prepared from polyimide at a target density of 0.085. Water (0.07 g) and benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic dianhydride; PMDA; 8.30 g) were added to dimethylacetamide (88.5 mL; containing 237 ppm water) and then stirred for 30 minutes. Solid p-phenylenediamine (PDA; 4.1 g; 1 molar equivalent) was added to the solution and the mixture was stirred for 2 hours. Acetic anhydride (16.7 g, 4.3 molar equivalents) was added to the stirred solution and then stirred for 2 hours.
[0561] Separately, a silicon dispersion was prepared in dimethylacetamide (14.6 g) by suspending a dispersion of silicon in isopropanol (71 wt %; 9.4 g). The mixture was heated at 120° C. with stirring until the isopropanol was completely evaporated (measured as 6.7 g weight loss; about 30 minutes). The silicon dispersion was added to the PDA / PMDA / acetic anhydride mixture. After stirring for 5 minutes, pyridine (10.4 mL; 8 volume %) was added to initiate gelation to form a polyamic acid presol. The presol was quickly poured into silicone oil (polydimethylsiloxane; 100 cSt; 650 mL; precooled to 14° C.) while stirring at 9000 rpm with a Ross stirrer. About 5 minutes after the addition of pyridine, 200 mL of ethanol was added. About 9 minutes after the presol was added to the silicone oil, the temperature had risen to about 65° C. and gelation occurred. The polyimide / Si beads suspension is transferred to a 2L beaker, and ethanol (400mL) is added, and then stirred at 7000rpm for 3 minutes. Each phase is separated and the beads are separated by filtration. The beads are mixed with heptane (150mL) for about 10 minutes and collected by filtration. The heptane washing is repeated, and then washed with a mixture of 120mL heptane and 120mL ethanol. The resulting filter cake is stirred in 400mL ethanol for 30 minutes, and allowed to stand overnight at room temperature. This is followed by further ethanol exchange (400mL; 3 hours at room temperature).
[0562] A portion of the polyimide / Si gel beads is dried using subcritical liquid CO2 by exchanging the solvent in the gel beads with liquid CO2 in a container at a pressure in the range of about 800 to 1200 psi for at least about 15 minutes. The container is then depressurized to atmospheric pressure to obtain polyimide / Si aerogel beads. The polyimide / Si aerogel beads are then carbonized at 1050°C under a nitrogen flow for 2 hours to provide C / Si aerogel beads (Example 21A). The properties of the aerogel beads are provided in Table 21 below. SEM images showing the outer and inner surfaces of the C / Si aerogel beads are provided at Fig.51A and 51B middle.
[0563] Another portion of the beads was dried at 68°C to obtain polyimide / Si xerogel beads. The polyimide / Si xerogel beads were then carbonized at 1050°C under nitrogen flow for 2 hours to provide C / Si xerogel beads (Example 21B). SEM images of the C / Si xerogel beads are provided at Fig.52 middle.
[0564] Example 22. Polyimide from DMAC / mineral extract emulsion (containing surfactant); 550 ppm water Preparation of C / Si composite beads
[0565] Carbon / Si composite gel beads containing 14 wt% silicon were prepared to a target density of 0.085. Water (0.07 g) and benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic dianhydride; PMDA; 8.30 g) were added to dimethylacetamide (104 mL; containing 145 ppm water) and stirred for 30 minutes. Solid p-phenylenediamine (PDA; 4.1 g; 1 molar equivalent) was added to the solution and the mixture was stirred for 2 hours. Acetic anhydride (16.7 g, 4.3 molar equivalents) was added to the stirred solution and stirred for 2 hours to provide a polyamic acid sol.
[0566] Separately, the mineral concentrate (650 mL) was stirred at room temperature with a magnetic stir bar and a Hypermer (13 g) was stirred for 1 hour.
[0567] Silicon particles (2.74 g) and 1 mm diameter zirconia beads (4 g) were dispersed in 40 g of the above sol by stirring at 2500 rpm for 5 minutes. This suspension (after removing the zirconia beads by filtration) was then added to the above sol, followed by stirring for 10 minutes.
[0568] Pyridine (10.4 mL; 8% by volume) was then added to the sol while stirring (4500 rpm), and the mixture was stirred for 50 seconds to begin gelation of the sol. The sol was then quickly poured into the mineral refinery / surfactant mixture. Six minutes after the addition of pyridine, ethanol (150 ml) was added and then stirred at 5500 rpm for 3 minutes. Stirring was stopped and the polyimide / Si gel bead suspension was allowed to stand for 30 minutes. The polyimide / Si gel beads were separated by filtration and washed in 400 mL of ethanol. Three additional ethanol washes were performed. Microphotographs of the resulting polyimide / Si gel beads are provided in Fig.53A middle.
[0569] A portion of the polyimide / Si gel beads is dried using subcritical liquid CO2 by exchanging the solvent in the gel beads with liquid CO2 in a container at a pressure in the range of about 800 to 1200 psi for at least about 15 minutes. The container is then depressurized to atmospheric pressure to obtain polyimide aerogel beads. The polyimide / Si aerogel beads are then carbonized at 1050°C under a nitrogen flow for 2 hours to provide C / Si aerogel beads (Example 22A). The properties of the aerogel and xerogel beads are provided in Table 23 below. SEM images showing the outer and inner surfaces of the C / Si aerogel beads are provided at Fig.54A and 54B middle.
[0570] Another portion of the beads was dried at 68°C to obtain polyimide / Si xerogel beads. The polyimide / Si xerogel beads were then carbonized at 1050°C under nitrogen flow for 2 hours to provide C / Si xerogel beads (Example 22B). SEM images of the C / Si xerogel beads are provided at Fig.55 It is noteworthy that compared with those prepared according to Example 21 ( Fig.52 ) compared to reference Fig.55 , less xerogel agglomeration and larger bead size were obtained for the beads prepared according to Example 22. SEM images showing the outer and inner surfaces of the C / Si xerogel beads are provided at Fig.56A and 56B The BET surface area of the xerogel prepared according to Example 22B was not detected.
[0571] Example 23. Polyimide from DMAC / mineral extract emulsion (without surfactant); 550 ppm water Preparation of polyimide / silicon composite beads
[0572] Polyimide / Si composite gel beads containing 14 wt% silicon were prepared using the procedure of Example 22A, but in the absence of surfactant, to a target density of 0.085. A micrograph of the resulting polyimide / Si gel beads is shown in FIG. Fig.53B provided, which showed that the bead size was 2 to 5 times larger than that produced when the surfactant was present ( Fig.53A ).
[0573] Example 24. Carbon beads prepared from polyimide in DMAC / mineral oil emulsion; 330 ppm water
[0574] Carbon aerogel and xerogel beads were prepared from polyimide at a target density of 0.085. Benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic dianhydride; PMDA; 8.30 g) was added to dimethylacetamide (106.7 mL; containing 145 ppm water). The mixture was heated at 35 ° C until all solids dissolved and then stirred at room temperature for 30 minutes. After stirring at room temperature for 28 minutes, water (0.042 g) was added to the mixture. Solid p-phenylenediamine (PDA; 4.1 g; 1 molar equivalent) was added to the solution, and the mixture was stirred for 2 hours. Acetic anhydride (16.7 g, 4.3 molar equivalents) was added to the stirred solution, which was then stirred for 2 hours. Pyridine (7.8 mL; 6 volume %) was added to the initial gelation to form a polyamic acid presol. After stirring for 1 minute, the presol was quickly poured into mineral oil while stirring at 9000 rpm with a Ross mixer. Add about 4.5 minutes after pyridine, add 100mL ethanol, and continue stirring for another 2 minutes at 9000rpm. Room temperature gelation occurs within 7.5 minutes after adding pyridine. The polyimide gel beads suspension is transferred to a 2L beaker, and ethanol (500mL) is added, and then stirred for 3 minutes at 6500rpm. After stirring stops, the gel beads are deposited on the beaker bottom. Remove the top oil layer, and rinse the gel beads 3 times with ethanol. The beads are mixed with ethanol (500mL) for about 10 minutes, and then allowed to stand. After decanting ethanol, wash the beads twice with heptane (150ml). The gel is separated from the heptane phase by filtration.
[0575] A portion of the polyimide gel beads is dried using subcritical liquid CO2 by exchanging the solvent in the gel beads with liquid CO2 in a container at a pressure in the range of about 800 to 1200 psi for at least about 15 minutes. The container is then depressurized to atmospheric pressure to obtain polyimide aerogel beads. The polyimide aerogel beads are then carbonized at 1050°C under a nitrogen flow for 2 hours to provide carbon aerogel beads (Example 24A). The properties of the aerogel beads are provided in Table 23. SEM images showing the outer and inner surfaces of the carbon aerogel beads are provided in Table 24, respectively. Fig.57A and 57B middle.
[0576] Another portion of the polyimide gel beads was dried at 68°C to obtain polyimide xerogel beads. The polyimide xerogel beads were then carbonized at 1050°C under a nitrogen stream for 2 hours to provide the carbon xerogel beads (Example 24B) below. SEM images showing the outer and inner surfaces of the carbon xerogel beads are provided at Fig.58A and 58B middle.
[0577] Table 23. C and C / Si aerogel bead properties
[0578]
[0579] Example 25. C / Si composite beads prepared from polyimide in DMAC / mineral oil emulsion; 330 ppm water
[0580] Carbon / Si composite beads containing 14 wt% silicon were prepared to a target density of 0.085. 8.30 g of benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic dianhydride; PMDA) were added to dimethylacetamide (106.7 mL, containing 145 ppm water). The mixture was heated at 35 °C until all solids dissolved and then stirred at room temperature for 30 minutes. After stirring at room temperature for 28 minutes, water (0.042 g) was added to the mixture. Solid p-phenylenediamine (PDA; 4.1 g; 1 molar equivalent) was added to the solution, and the mixture was stirred for 2 hours. Acetic anhydride (16.7 g, 4.3 molar equivalents) was added to the stirred solution and then stirred for 2 hours.
[0581] Silicon particles (2.74 g) and 1 mm diameter zirconium oxide beads (4 g) were dispersed in 40 g of the above sol by stirring at 2500 rpm for 5 minutes. The zirconium oxide beads were used to break down silicon agglomerates (if any) and ensure better dispersion of silicon in the sol. The suspension (after removing the zirconium oxide beads by filtration) was then added to the above sol, followed by stirring for 10 minutes.
[0582] Pyridine (7.8mL; 6 volume %) is added to start gelation to form a polyamic acid presol. After stirring for 1 minute, the presol is quickly poured into mineral oil while stirring at 9000rpm with a Ross mixer. About 4.5 minutes after adding pyridine, 100mL of ethanol is added, and stirring is continued for another 2 minutes at 9000rpm. The polyimide / Si gel bead suspension is transferred to a 2L beaker, and ethanol (500mL) is added, and then stirred at 6500rpm for 3 minutes. After stirring stops, the gel beads are deposited at the bottom of the beaker. The top oil layer is removed, and the gel beads are rinsed 3 times with ethanol. The beads are mixed with ethanol (500mL) for about 10 minutes, and then allowed to stand. After decanting the ethanol, the beads are washed twice with heptane (150ml). The gel is separated from the heptane phase by filtration.
[0583] A portion of the polyimide / Si gel beads is dried using subcritical liquid CO2 by exchanging the solvent in the gel beads with liquid CO2 in a container at a pressure in the range of about 800 to 1200 psi for at least about 15 minutes. The container is then depressurized to atmospheric pressure to obtain polyimide aerogel beads. The polyimide / Si aerogel beads are then carbonized at 1050°C under a nitrogen flow for 2 hours to provide C / Si aerogel beads.
[0584] Example 26. C / Si composite beads prepared from polyimide in DMAC / silicone oil emulsion; 0 ppm water
[0585] Carbon / Si composite beads containing 35 wt% silicon were prepared from polyimide at a target density of 0.085. Benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic dianhydride; PMDA; 8.0 g) was added to dimethylacetamide (79.7 mL) and then stirred for 30 minutes. Solid p-phenylenediamine (PDA; 4.0 g; 1 molar equivalent) was added to the solution and the mixture was stirred for 2 hours. Acetic anhydride (16.1 g, 4.3 molar equivalents) was added to the stirred solution and then stirred for 2 hours.
[0586] Separately, a silicon dispersion was prepared by suspending a dispersion of silicon in isopropanol (71 wt %; 9.1 g) in dimethylacetamide (14.1 g). The mixture was heated at 120° C. under stirring until the isopropanol was completely evaporated (measured with a 6.4 g weight loss; about 30 minutes). The silicon dispersion was added to the PDA / PMDA / acetic anhydride mixture. After stirring for 5 minutes, pyridine (10.0 mL; 8 volume %) was added to start gelation to form a polyamic acid presol. The presol was quickly poured into silicone oil (polydimethylsiloxane; 100 cSt; 625 mL) while stirring with a Ross mixer at 9000 rpm. About 5 minutes after the pyridine was added, when room temperature gelation occurred, 100 mL of ethanol was added and stirring was continued for another minute. Ethanol (300 mL) was added and then stirred at 7000 rpm for 3 minutes. The phases were separated and the beads were separated by filtration. The beads were mixed with heptane (150 mL) for about 10 minutes and collected by filtration. The heptane wash was repeated and then washed with a mixture of 120 mL heptane and 120 mL ethanol. The resulting filter cake was stirred in 300 mL ethanol overnight.
[0587] A portion of the polyimide / Si gel beads is dried using subcritical liquid CO2 by exchanging the solvent in the gel beads with liquid CO2 in a container at a pressure in the range of about 800 to 1200 psi for at least about 15 minutes. The container is then depressurized to atmospheric pressure to obtain polyimide / Si aerogel beads. The polyimide / Si aerogel beads are then carbonized at 1050°C under a nitrogen flow for 2 hours to provide C / Si aerogel beads.
[0588] Example 27. C / Si beads prepared from polyimide in DMAC / silicone oil emulsion; 530 ppm water
[0589] Carbon / Si composite beads containing 35 wt% silicon were prepared from polyimide at a target density of 0.085. Water (0.046 g) and benzene-1,2,4,5-tetracarboxylic anhydride (pyromellitic dianhydride; PMDA; 6.4 g) were added to dimethylacetamide (63.8 mL) and then stirred for 30 minutes. Solid p-phenylenediamine (PDA; 3.2 g; 1 molar equivalent) was added to the solution and the mixture was stirred for 2 hours. Acetic anhydride (12.8 g, 4.3 molar equivalents) was added to the stirred solution and then stirred for 2 hours.
[0590] Separately, a silicon dispersion was prepared by suspending a dispersion of silicon in isopropanol (71 wt %; 7.3 g) in dimethylacetamide (11.3 g). The mixture was heated at 120° C. under stirring until the isopropanol was completely evaporated (measured with a 4.6 g weight loss; about 30 minutes). The silicon dispersion was added to the PDA / PMDA / acetic anhydride mixture. After stirring for 5 minutes, pyridine (8.0 mL; 8 volume %) was added to start gelation to form a polyamic acid presol. The presol was quickly poured into silicone oil (polydimethylsiloxane; 100 cSt; 450 mL) while stirring at 9000 rpm with a Ross mixer. About 5 minutes after the pyridine was added, 100 mL of ethanol was added and stirring was continued for another minute. Room temperature gelation occurred within 7 minutes. Ethanol (300 mL) was added and then stirred at 7000 rpm for 3 minutes. The phases were separated and the beads were separated by filtration. The beads were mixed with heptane (150 mL) for about 10 minutes and collected by filtration. The heptane wash was repeated and then washed with a mixture of 120 mL heptane and 120 mL ethanol. The resulting filter cake was stirred in 300 mL ethanol for 30 minutes.
[0591] A portion of the polyimide / Si gel beads is dried using subcritical liquid CO2 by exchanging the solvent in the gel beads with liquid CO2 in a container at a pressure in the range of about 800 to 1200 psi for at least about 15 minutes. The container is then depressurized to atmospheric pressure to obtain polyimide / Si aerogel beads. The polyimide / Si aerogel beads are then carbonized at 1050°C under a nitrogen flow for 2 hours to provide C / Si aerogel beads.
[0592] Example 28. C / Si beads prepared from polyimide in DMAC / silicone oil emulsion; 1190 ppm water
[0593] Carbon / Si composite beads containing 35 wt% silicon were prepared according to Example 27, but with a sol water content of 1190 ppm from polyimide at a target density of 0.085.
[0594] Example 29. C / Si beads prepared from polyimide in DMAC / silicone oil emulsion; 620 ppm water
[0595] Carbon / Si composite beads containing 35 wt% silicon were prepared according to Example 27, but with a sol water content of 620 ppm from polyimide at a target density of 0.06.
[0596] result
[0597] In Example 26, beads were prepared without water addition, and ethanol was added at the gel point (5.3 minutes after pyridine addition). In contrast, in Example 27, 530 ppm of water was added to the sol solvent, which both reduced the viscosity and delayed gelation. Thus, the addition of ethanol at 5.3 minutes after pyridine addition was before the gel point was reached. SEM images showing C / Si aerogel beads prepared according to Examples 26 and 27 are provided at Fig.59A and 59B , which shows that the beads produced in the presence of 530 ppm water are about 50% smaller than those prepared in the absence of water. The average bead size distributions for Examples 26 and 27 are provided in Fig.60 (average sizes of 23 and 11 μm, respectively). Data for bead sizes D10, D50, and D90 are provided in Table 24, which illustrates that the addition of about 500 to 600 ppm of water reduces the bead size relative to the bead size obtained in the absence of water, and further increases in the water content in the sol (such as 1190 ppm) do not further reduce the bead size. Without wishing to be bound by theory, it is believed that the addition of water reduces the molecular weight of the polyamic acid, resulting in a reduction in the sol viscosity, followed by a reduction in bead size.
[0598] Table 24. Particle size vs. water content
[0599]
[0600]
[0601] Example 30: Alternative Method for Producing Polyimide Aerogels
[0602] The previous embodiments discussed herein teach certain methods of forming PI gels (such as aerogels or xerogels). In certain embodiments, the present invention further contemplates alternative methods of forming PI gels, which can be converted into carbon aerogels or xerogels by pyrolysis. A non-exhaustive and non-limiting set of examples of such alternative methods will now be discussed.
[0603] For example, U.S. Patent No. 6,399,669 to Suzuki et al. teaches four (4) related methods for preparing PI dry gels (aerogels). In the first method, a PI precursor is synthesized, and then an imide is formed from the PI precursor to produce a polyimide. A PI solution or a swell body is prepared, and the solution / swell body is gelled to produce a PI wet gel. This wet gel is dried to produce a PI dry gel (aerogel).
[0604] In the second method, a PI precursor is synthesized, and then a PI precursor solution or a dilatant is prepared. The solution / dilatant is gelled to produce a PI precursor wet gel. Imide is then formed from the PI precursor to form a PI wet gel. This wet gel is dried to produce a PI dry gel (aerogel). In the third method, a PI precursor is synthesized, and then a PI precursor solution or a dilatant is prepared. Imide is then formed from the PI precursor and simultaneously gelled to produce a PI wet gel.
[0605] In the third method, a PI precursor is synthesized, and then a PI precursor solution or a dilatant is prepared. The solution / dilatant is gelled to produce a PI precursor wet gel. The wet gel is then dried to produce a PI precursor dry gel. Imide is then formed from the PI precursor dry gel to form a PI dry gel (aerogel).
[0606] As another example, Leventis et al. ("Polyimide Aerogels by Ring-Opening Metathesis Polymerization (ROMP)", Chem. Mater. 2011, 23, 8, 2250-2261) discussed the use of ROMP method to form PI aerogels. Generally, a low molecular weight imidized oligomer capped with a polymerizable group is provided and mixed with a polymerization (e.g., ROMP) catalyst. Polymerization is initiated to form a cross-linked polyimide. The polyimide is gelled and dried to form a PI aerogel.
[0607] As another example, U.S. Pat. No. 9,745,198, issued to Leventis et al. and Chidambareswarapattar et al., "One-step room-temperature synthesis of fibrous polyimide aerogels from anhydrides and isocyanates and conversion to isomorphic carbons," J. Mater. Chem., 2010, 20, 9666–9678, teaches forming PI aerogels by mixing a dianhydride (e.g., PMDA) with an isocyanate (e.g., 4,4′-diisocyanatodiphenylmethane or di-p-phenylene diisocyanate) to form a sol-gel material. The sol-gel material is then dried to produce a PI aerogel. Leventis et al. ("Isocyanate-Derived Organic Aerogels: Polyureas, Polyimides, Polyamides", MRS Proceedings, 1306 (2011), Mrsf10-1306-bb03-01.doi:10.1557 / opl.2011.90) also noted N 3300A, RE and CD, both purchased from Covestro AG, Pittsburgh, PA, US, can be used as isocyanate.
[0608] In an alternative approach, Guo et al. ("Polyimide Aerogels Cross-Linked through Amine Functionalized Polyoligomeric Silsesquioxane," ACS Appl. Mater. Interfaces 2011, 3, 546–552) discuss the formation of PI aerogels by reacting aminosilsesquioxane with polyamic acid oligomers terminated with anhydride groups. The product is imidized using pyridine (although thermal imidization is also considered) and gelled, then dried to obtain the PI aerogel. Nguyen et al. ("Development of High Temperature, Flexible Polyimide Aerogels," American Chemical Society, proceedings published 2011" discuss the production of branched polyimides by mixing diamines and dianhydrides and imidizing after reaction with polyamino compounds (e.g., 1,3,5-tris(4-aminophenoxybenzene)). The product is then reacted with 4,4'-methylene diisocyanate and dried to form a PI-urea aerogel.
[0609] In other embodiments, Meador et al. ("Mechanically Strong, Flexible Polyimide Aerogels Cross-Linked with Aromatic Triamine", ACS Appl. Mater. Interfaces, 2012, 4 (2), pp. 536–544) discuss the production of PI gels by cross-linking polyamic acid oligomers terminated with anhydride groups with aromatic triamines in solution, followed by imidization. The resulting wet material is dried to form a PI aerogel. In addition, Meador et al. ("Polyimide Aerogels with Amide Cross-Links: A Low Cost Alternative for Mechanically Strong Polymer Aerogels," ACS Appl. Mater. Interfaces 2015, 7, 1240-1249) discuss the formation of PI gels by cross-linking amino-terminated oligomers with 1,3,5-benzenetrichlorocarbonyl trichloride. The resulting gel is dried to form a PI aerogel.
[0610] In yet another embodiment, Pei et al. ("Preparation and Characterization of Highly Cross-Linked Polyimide Aerogels Based on Polyimide Containing Trimethoxysilane Side Groups," Langmuir 2014, 30, 13375-13383) produced PI aerogels from polyimide containing trimethoxysilane side groups, which are condensation products of polyimide containing acid chloride side groups and 3-aminopropyltrimethoxysilane. The resulting gel is dried to form a PI aerogel.
[0611] In any of these methods, a suspension of graphene can be added (see Zhang et al., "Graphene / carbon aerogels derived from graphene crosslinked polyimide as electrode materials for supercapacitors," RSC Adv., 2015, 5, 1301).
[0612] Each of these methods can result in a polyimide aerogel, and the present invention contemplates any suitable method for producing such a polyimide aerogel. According to certain embodiments of the present invention, regardless of which method is used to produce the PI aerogel, the resulting PI aerogel can be pyrolyzed to form a PI-derived carbon aerogel. According to certain embodiments discussed herein, additives such as silicon can also be introduced.
[0613] All cited publications are incorporated herein by reference in their entirety. In addition, if a definition or use of a term in a reference incorporated herein by reference is inconsistent or contrary to the definition of that term provided herein, the definition of that term provided herein applies, and the definition of that term in the reference should be disregarded.
[0614] The advantages shown above and those obvious from the foregoing description can be effectively achieved.Since certain modifications can be made to the above grammatical structure without departing from the scope of the present invention, all matters contained in the above description or shown in the accompanying drawings should be interpreted as illustrative rather than limiting.
[0615] It is also to be understood that the following claims are intended to cover all generic and specific features of the invention described herein, together with all statements of the scope of the invention which as a matter of language might be construed as falling therebetween.
Claims
1. A method for forming a porous carbon composition in the form of beads, the method comprising: providing an organogel precursor in an organic solvent; Initiating gelation of the organogel precursor to obtain an organogel sol; combining the organogel sol with a medium immiscible with the organogel sol, wherein the combining comprises stirring under high shear conditions, thereby forming droplets of the organogel; separating droplets of the organogel; drying the droplets to produce porous organogel beads; and The porous organogel beads are pyrolyzed to produce a porous carbon composition in the form of the beads, wherein the porous carbon composition has a porosity between 10% and 90%.
2. The method of claim 1, wherein the porous carbon composition has an average pillar width of 2 to 5 nm.
3. The method of claim 1, wherein the organogel precursor is polyamic acid.
4. The method of claim 3, wherein the gelling is chemical imidization, thermal imidization, or a combination of chemical imidization and thermal imidization.
5. The method of claim 3, wherein the polyamic acid comprises a tetracarboxylic acid and a polyfunctional amine.
6. The method of claim 5, wherein the tetracarboxylic acid is selected from the group consisting of benzene-1,2,4,5-tetracarboxylic acid, [1,1'-biphenyl]-3,3',4,4'-tetracarboxylic acid, 4,4'-oxydiphthalic acid, 4,4'-sulfonyldiphthalic acid, 4,4'-carbonyldiphthalic acid, 4,4'-(propane-2,2-diyl)diphthalic acid, 4,4'-(perfluoropropane-2,2-diyl)diphthalic acid, naphthalene-1,4,5,8-tetracarboxylic acid, 4-(2-(4-(3,4-dicarboxyphenoxy)phenyl)propan-2-yl)phthalic acid, perylenetetracarboxylic acid, and combinations thereof.
7. The method of claim 5, wherein the polyfunctional amine is an alkanediamine or an aryldiamine.
8. The method of claim 7, wherein the alkanediamine is ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, or a combination thereof. 9 . The method of claim 7 , wherein the aryl diamine is 1,4-phenylenediamine, 4,4′-diaminodiphenyl ether, 4,4′-methylenedianiline, or a combination thereof.
10. The method of claim 4, wherein the chemical imidization comprises adding a dehydrating agent and an amine base.
11. The method of claim 10, wherein the dehydrating agent is acetic anhydride.
12. The method of claim 10, wherein the amine base is pyridine.
13. The method of claim 1, wherein the organic solvent is N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran or ethyl acetate.
14. The method of claim 1, wherein the organic solvent is N,N-dimethylacetamide.
15. The method of claim 1, wherein the organic solvent further comprises water in an amount of 100 to 1500 parts per million (ppm).
16. The method of claim 15, wherein the organic solvent further comprises water in an amount of 500 to 1200 ppm or 500 to 700 ppm.
17. The method of claim 1, wherein the medium has a viscosity of 100 to 150 cP.
18. The method of claim 1, wherein the medium is mineral oil, silicone oil or C5-C12 hydrocarbon.
19. The method of claim 18, further comprising adding one or more surfactants to the medium.
20. The method of claim 1, wherein the organogel sol has a viscosity of 5 to 30 cP.
21. The method of claim 1, further comprising adding a low viscosity solvent to the medium.
22. The method of claim 21, wherein the low viscosity solvent is added all at once in an amount of at most 10% by volume of the medium.
23. The method of claim 21, wherein the low viscosity solvent is added in two or more portions, including a first portion in an amount of up to 10% by volume of the medium and one or more additional portions, wherein the total amount of the low viscosity solvent added is up to 50% by volume of the medium.
24. The method of claim 21, wherein the low viscosity solvent is added in a continuous manner, wherein the total amount of the low viscosity solvent added is at most 50% by volume of the medium.
25. The method of claim 21, wherein the low viscosity solvent is a C1 to C3 alcohol.
26. The method of claim 1, wherein the stirring under high shear conditions comprises stirring at a speed in the range of 4000 rpm to 9000 rpm.
27. The method of claim 1, wherein drying comprises freeze-drying the organogel beads, exposing the organogel beads to elevated temperature conditions, contacting the organogel beads with supercritical fluid CO2, or contacting the organogel beads with liquid CO2 and evaporating the CO2 as a gas.
28. The method of claim 1, further comprising aging the porous organogel beads prior to pyrolyzing.
29. The method of claim 1, wherein the porous carbon composition comprises a carbon aerogel.
30. The method of claim 1, wherein the porous carbon composition comprises a carbon xerogel.
31. The method of claim 1, wherein the beads of the porous carbon composition have a diameter in the range of 1 micron to 50 microns.
32. The method of claim 1, wherein the porous carbon composition is a porous carbon-silicon composition comprising greater than 10 weight percent silicon based on the total weight of the composition, the method further comprising providing silicon mixed with the organogel precursor in the organic solvent.
33. The method of claim 32, wherein the porous carbon-silicon composition comprises 20 wt% to 65 wt% silicon based on the total weight of the composition.
34. The method of claim 32, wherein the porous carbon-silicon composition comprises a pore structure, and wherein the silicon resides at least partially within the pore structure.
35. The method of claim 34, wherein the pore structure comprises a fibrous morphology and an array of pores surrounding the silicon.
36. The method of claim 32, wherein the porous carbon-silicon composition has a capacity of at least 800 mAh / g.
37. The method of claim 32, wherein the porous carbon-silicon composition has a silicon utilization efficiency of at least 20%.
38. A porous carbon composition in the form of beads, the porous carbon composition comprising a composite material comprising a carbonized polyimide aerogel or a carbonized polyimide xerogel, the carbonized polyimide aerogel or the carbonized polyimide xerogel comprising a pore structure comprising a fibrous morphology and an array of pores, the composite material further comprising greater than 10 wt % silicon based on the total weight of the composition, and wherein the silicon is at least partially present within the pore structure, wherein the beads have a diameter in the range of 1 μm to 15 μm and a tap density of 0.3 g / cm 3 Up to 1.3g / cm 3 within the range.
39. The porous carbon composition of claim 38, having a pre-lithiation porosity between 10% and 80%.
40. The porous carbon composition of claim 38, wherein the carbonized polyimide aerogel or carbonized polyimide xerogel has a residual nitrogen content of at least 4 wt%.
41. The porous carbon composition of claim 38, wherein the composite material comprises 25 wt% to 65 wt% silicon based on the total weight of the composition.
42. The porous carbon composition of claim 38, wherein the fibrous morphology comprises struts having an average strut width of 2 to 10 nm.
43. The porous carbon composition of claim 38, wherein the composite material has a silicon utilization efficiency of at least 20%.
44. The porous carbon composition of claim 38, wherein the silicon has a particle size of less than 150 nm.
45. The porous carbon composition of claim 38, wherein the silicon has a particle size in the range of 150 nm to 500 nm.
46. The porous carbon composition of claim 38, wherein the silicon has a particle size greater than 500 nm.
47. The porous carbon composition of claim 38, wherein the composite material comprises silicon in the range of 25 to 65 wt. %, the silicon having a particle size in the range of 30 nm to 800 nm; and wherein the beads have: At 0.2g / cm 3 Up to 1.5g / cm 3 Tap density within the range; Diameter in the range of 1 μm to 15 μm; An average pore size in the range of 10 nm to 50 nm; and 0 to 500m 2 The BET surface area is in the range of / g.
48. The porous carbon composition of claim 38, having a capacity of at least 800 mAh / g.
49. An energy storage device comprising the porous carbon composition according to claim 38.
50. The energy storage device of claim 49, which is a lithium-ion battery pack.
Citation Information
Patent Citations
Carbon aerogel-based electrode materials and methods of manufacture thereof
US11648521B2
Polyimide bead materials and methods of manufacture thereof
US12034151B2
Process for forming transparent aerogel insulating arrays
US4610863A
Method for producing metal oxide aerogels having densities less than 0.02 g / cc
US5275796A
Method for making monolithic metal oxide aerogels
US5395805A